3D convolutional neural network-based autosegmentation improves brain metastases detection and quantification for brain stereotactic radiotherapy treatment planning - Putz, Florian; Weissmann, Thomas; Mansoorian, Sina; Schmidt, Manuel; Heiß, Rafael; Semrau, Sabine; Frey, Benjamin; Bert, Christoph; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

49th Annual Conference of the German Society for Medical Physics and 21st Annual Conference of the German Section of the ISMRM - Bert, Christoph; Wucherer, Michael; Laun, Frederik B. (Zeitschrift für Medizinische Physik, 2018)
EVALuna2:36480

4D optimization of scanned ion beam tracking therapy for moving tumors - Eley, John Gordon; Newhauser, Wayne David; Lüchtenborg, Robert; Graeff, Christian; Bert, Christoph (Physics in Medicine and Biology, 2014)
Motion mitigation strategies are needed to fully realize the theoretical advantages of scanned ion beam therapy for patients with moving tumors. The purpose of this study was to determine whether a new four-dimensional (4D) optimization approach for scanned-ion-beam tracking could reduce dose to avoidance volumes near a moving target while maintaining target dose coverage, compared to an existing 3D-optimized beam tracking approach. We tested these approaches computationally using a simple 4D geometrical phantom and a complex anatomic phantom, that is, a 4D computed tomogram of the thorax of a lung cancer patient. We also validated our findings using measurements of carbon-ion beams with a motorized film phantom. Relative to 3D-optimized beam tracking, 4D-optimized beam tracking reduced the maximum predicted dose to avoidance volumes by 53% in the simple phantom and by 13% in the thorax phantom. 4D-optimized beam tracking provided similar target dose homogeneity in the simple phantom (standard deviation of target dose was 0.4% versus 0.3%) and dramatically superior homogeneity in the thorax phantom (D5-D95 was 1.9% versus 38.7%). Measurements demonstrated that delivery of 4D-optimized beam tracking was technically feasible and confirmed a 42% decrease in maximum film exposure in the avoidance region compared with 3D-optimized beam tracking. In conclusion, we found that 4D-optimized beam tracking can reduce the maximum dose to avoidance volumes near a moving target while maintaining target dose coverage, compared with 3D-optimized beam tracking.
EVALuna2:18202

AAPM Task Group Report 290: Respiratory motion management for particle therapy - Li, Heng; Dong, Lei; Bert, Christoph; Chang, Joe; Flampouri, Stella; Jee, Kyung-Wook; Lin, Liyong; Moyers, Michael; Mori, Shinichiro; Rottmann, Joerg; Tryggestad, Erik; Vedam, Sastry (Medical Physics, 2022)
Dose uncertainty induced by respiratory motion remains a major concern for treating thoracic and abdominal lesions using particle beams. This Task Group report reviews the impact of tumor motion and dosimetric considerations in particle radiotherapy, current motion-management techniques, and limitations for different particle-beam delivery modes (i.e., passive scattering, uniform scanning, and pencil-beam scanning). Furthermore, the report provides guidance and risk analysis for quality assurance of the motion-management procedures to ensure consistency and accuracy, and discusses future development and emerging motion-management strategies. This report supplements previously published AAPM report TG76, and considers aspects of motion management that are crucial to the accurate and safe delivery of particle-beam therapy. To that end, this report produces general recommendations for commissioning and facility-specific dosimetric characterization, motion assessment, treatment planning, active and passive motion-management techniques, image guidance and related decision-making, monitoring throughout therapy, and recommendations for vendors. Key among these recommendations are that: (1) facilities should perform thorough planning studies (using retrospective data) and develop standard operating procedures that address all aspects of therapy for any treatment site involving respiratory motion; (2) a risk-based methodology should be adopted for quality management and ongoing process improvement.
CRIS-Team Scopus Importer:2022-02-11

Accumulation of the delivered treatment dose in volumetric modulated arc therapy with breath-hold for pancreatic cancer patients based on daily cone beam computed tomography images with limited field-of-view - Ziegler, Marc; Nakamura, Mitsuhiro; Hirashima, Hideaki; Ashida, Ryo; Yoshimura, Michio; Bert, Christoph; Mizowaki, Takashi (Medical Physics, 2019)
Background and purpose: Inter-fractional changes of the daily anatomy of the patient are a source of error in radiotherapy. This effect is especially present in the abdomen, where there are daily differences in the filling of the stomach or the intestines. This study investigated the impact of inter-fractional changes of pancreatic cancer patients who underwent breath-hold volumetric modulated arc therapy on the applied dose by using deformable image registration. Material and methods: Deformable image registration was used to determine a displacement field which maps the computed tomography (CT) used for treatment planning onto daily breath-hold cone-beam CT images with limited field-of-view (FOV) which were acquired at the beginning of every treatment fraction. Different B-spline registration methods utilizing different metrics and regularizations were used and compared. The resulting deformed planning CT images were used to calculate the dose distributions on the anatomy of the day which can therefore be seen as a good estimation of the actually delivered dose during the treatment fractions. Additionally, the accumulated dose distribution was determined by accumulating all daily dose distributions using inverted deformation fields. The calculated dose distributions were then compared to the planned dose by comparison of dose volume histograms and dosimetric volumetric indices. Results: Best registration results were obtained using a gradient magnitude metric and a regularization of λ = 0.05. The accumulated dose distributions showed that the mean dose delivered to the clinical target volume was on median reduced by 0.61 Gy after 15 fractions from the planned dose. For the organs at risk, the accumulated dose distributions were still fulfilling all clinical goals for the patient cohort used in this study. It was found that rotating and shearing motions of the tumor led to a greater reduction in the mean target dose which correlated with the proximity of the target to the spine (r = 0.54, P = 0.038). Conclusion: With the proposed method, it is possible to generate a deformed planning CT image which matches the anatomy of the day based on cone beam computed tomography images with a limited FOV and calculating the dose distribution of the day. The dosimetric impact of the inter-fractional variations was small for most patients but showed larger deviations if the tumor is located in close proximity to the spine.
CRIS-Team Scopus Importer:2019-06-28
Keywords: breath-hold; deformable image registration; inter-fractional changes; pancreatic cancer

Accuracy of MRI-CT registration in brain stereotactic radiotherapy: Impact of MRI acquisition setup and registration method - Masitho, Siti; Putz, Florian; Mengling, Veit; Reißig, Lisa; Voigt, Raphaela; Bäuerle, Tobias; Janka, Rolf Matthias; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2022)
Background: In MR-based radiotherapy (RT), MRI images are co-registered to the planning CT to leverage MR image information for RT planning. Especially in brain stereotactic RT, where typical CTV-PTV margins are 1-2 mm, high registration accuracy is critical. Several factors influence the registration accuracy, including the acquisition setup during MR simulation and the registration methods. Purpose: In this work, the impact of the MRI acquisition setup and registration method was evaluated in the context of brain RT, both geometrically and dosimetrically. Methods and Materials: MRI of 20 brain radiotherapy patients was acquired in two MRI acquisition setups (RT and diagnostic). Three different automatic registration tools provided by three treatment planning systems were used to rigidly register both MRIs and CT in addition to the clinical registration. Segmentation-based evaluation using Hausdorff Distance (HD)/Dice Similarity Coefficient and landmark-based evaluation were used as evaluation metrics. Dose-volume-histograms were evaluated for target volumes and various organs at risks. Results: MRI acquisition in the RT setup provided a similar head extension as compared to the planning CT. The registration method had a more significant influence than the acquisition setup (Wilcoxon signed-rank test, p<0.05). When registering using a less optimal registration method, the RT setup improved the registration accuracy compared to the diagnostic setup (Difference: ΔMHD = 0.16 mm, ΔHDP95 = 0.64 mm, mean Euclidean distance (ΔmEuD) = 2.65 mm). Different registration methods and acquisition setups lead to the variation of the clinical DVH. Acquiring MRI in the RT setup can improve PTV and GTV coverage compared to the diagnostic setup. Conclusions: Both MRI acquisition setup and registration method influence the MRI-CT registration accuracy in brain RT patients geometrically and dosimetrically. MR-simulation in the RT setup assures optimal registration accuracy if automatic registration is impaired, and therefore recommended for brain RT.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Brain radiotherapy; Intracranial stereotactic radiotherapy; Magnetic-resonance imaging; Patient immobilization; Registration

A comprehensive quality assurance protocol for electromagnetic tracking in brachytherapy - Dürrbeck, Christopher; Gomez-Sarmiento, Isaac Neri; Androulakis, Ioannis; Sauer, Birte; Kolkman-Deurloo, Inger Karine; Bert, Christoph; Beaulieu, Luc (Medical Physics, 2024)
Background: Electromagnetic tracking (EMT) systems have proven to be a valuable source of information regarding the location and geometry of applicators in patients undergoing brachytherapy (BT). As an important element of an enhanced and individualized pre-treatment verification, EMT can play a pivotal role in detecting treatment errors and uncertainties to increase patient safety. Purpose: The purpose of this study is two-fold: to design, develop and test a dedicated measurement protocol for the use of EMT-enabled afterloaders in BT and to collect and compare the data acquired from three different radiation oncology centers in different clinical environments. Methods: A novel quality assurance (QA) phantom composed of a scaffold with supports to fix the field generator, different BT applicators, and reference sensors (sensor verification tools) was used to assess the precision (jitter error) and accuracy (relative distance errors and target registration error) of the EMT sensor integrated into an afterloader prototype. Measurements were repeated in different environments where EMT measurements are likely to be performed, namely an electromagnetically clean laboratory, a BT suite, an operating room, and, if available, a CT suite and an MRI suite dedicated to BT. Results: The mean positional jitter was consistently under 0.1 mm across all measurement points, with a slight trend of increased jitter at greater distances from the field generator. The mean variability of sensor positioning in the tested tandem and ring gynecological applicator was also below 0.1 mm. The tracking accuracy close to the center of the measurement volume was higher than at its edges. The relative distance error at the center was 0.2-0.3 mm with maximum values reaching 1.2-1.8 mm, but up to 5.5 mm for measurement points close to the edges. In general, similar accuracy results were obtained in the clinical environments and in all investigated institutions (median distance error 0.1-0.4 mm, maximum error 1.0-2.0 mm), however, errors were found to be larger in the CT suite (median distance error up to 1.0 mm, maximum error up to 3.6 mm). Conclusion: The presented quality assessment protocol for EMT systems in BT has demonstrated that EMT offers a high-accuracy determination of the applicator/implant geometry even in clinical environments. In addition to that, it has provided valuable insights into the performance of EMT-enabled afterloaders across different radiation oncology centers.
CRIS-Team Scopus Importer:2024-05-17
Keywords: brachytherapy; electromagnetic tracking; quality assurance

Adaptive radiotherapy and the dosimetric impact of inter- and intrafractional motion on the planning target volume for prostate cancer patients - Böckelmann, Felix; Putz, Florian; Kallis, Karoline; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (Strahlentherapie und Onkologie, 2020)
Purpose: To investigate the dosimetric influence of daily interfractional (inter) setup errors and intrafractional (intra) target motion on the planning target volume (PTV) and the possibility of an offline adaptive radiotherapy (ART) method to correct larger patient positioning uncertainties in image-guided radiotherapy for prostate cancer (PCa). Materials and methods: A CTV (clinical target volume)-to-PTV margin ranging from 15 mm in LR (left-right) and SI (superior-inferior) and 5–10 mm in AP (anterior-posterior) direction was applied to all patients. The dosimetric influence of this margin was retrospectively calculated by analysing systematic and random components of inter and intra errors of 31 consecutive intermediate- and high-risk localized PCa patients using daily cone beam computed tomography and kV/kV (kilo-Voltage) imaging. For each patient inter variation was assessed by observing the first 4 treatment days, which led to an offline ART-based treatment plan in case of larger variations. Results:: Systematic inter uncertainties were larger (1.12 in LR, 2.28 in SI and 1.48 mm in AP) than intra systematic errors (0.44 in LR, 0.69 in SI and 0.80 mm in AP). Same findings for the random error in SI direction with 3.19 (inter) and 2.30 mm (intra), whereas in LR and AP results were alike with 1.89 (inter) and 1.91 mm (intra) and 2.10 (inter) and 2.27 mm (intra), respectively. The calculated margin revealed dimensions of 4–5 mm in LR, 8–9 mm in SI and 6–7 mm in AP direction. Treatment plans which had to be adapted showed smaller variations with 1.12 (LR) and 1.72 mm (SI) for Σ and 4.17 (LR) and 3.75 mm (SI) for σ compared to initial plans with 1.77 and 2.62 mm for Σ and 4.46 and 5.39 mm for σ in LR and SI, respectively. Conclusion: The currently clinically used margin of 15 mm in LR and SI and 5–10 mm in AP direction includes inter and intra uncertainties. The results show that offline ART is feasible which becomes a necessity with further reductions in PTV margins.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Cone beam computed tomography; Drinking protocol; Endorectal balloon; Margin calculation

Advanced Multimodal Methods for Cranial Pseudo-CT Generation Validated by IMRT and VMAT Radiation Therapy Plans - Speier, Christoph; Pileggi, Giampaolo; Izquierdo-Garcia, David; Catana, Ciprian; Sharp, Gregory C.; Spadea, Maria Francesca; Bert, Christoph; Seco, Joao (International Journal of Radiation Oncology Biology Physics, 2018)
PURPOSE: To investigate advanced multimodal methods for pseudo-computed tomography (CT) generation from standard magnetic resonance imaging sequences and to validate the results by intensity-modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT) plans. We present 2 novel methods that employ key techniques to enhance pseudo-CTs and investigate the effect on image quality and applicability for IMRT and VMAT planning. MATERIALS AND METHODS: The data set contains CT and magnetic resonance image scans from 15 patients who underwent cranial radiation therapy. For each patient, pseudo-CTs of the head were generated with a patch-based and a voxel-based algorithm. The accuracy of the pseudo-CTs in comparison to clinical CTs was evaluated by mean absolute error, bias, and the Dice coefficient (of bone). IMRT and VMAT plans were created for each patient. Dose distributions were calculated with both the pseudo-CT and the clinical CT scans and compared by gamma tests, dose-volume histograms, and isocenter doses. RESULTS: The generated pseudo-CTs exhibited average mean absolute errors of 118.7 ± 10.4 HU for the voxel-based algorithm and 73.0 ± 6.4 HU for the patch-based algorithm. The dose calculations were in good agreement and showed gamma test (2 mm, 2%) pass rates for both beam setups (IMRT and VMAT) of over 99% for 14 patients and over 98% for 1 patient. CONCLUSIONS: We showed that the key techniques of our 2 novel algorithms advance the quality of pseudo-CT significantly and generate very competitive pseudo-CTs compared with previously published methods. This quality was confirmed by low dose error in comparison to the ground-truth CT. With the achieved level of accuracy, our patch-based algorithm especially is a candidate for clinical routine use in IMRT and VMAT planning.
EVALuna2:36471

Advances in 4D treatment planning for scanned particle beam therapy - report of dedicated workshops - Bert, Christoph; Graeff, Christian; Riboldi, Marco; Nill, Simeon; Baroni, Guido; Knopf, Antje-Christin (Technology in Cancer Research & Treatment, 2014)
We report on recent progress in the field of mobile tumor treatment with scanned particle beams, as discussed in the latest editions of the 4D treatment planning workshop. The workshop series started in 2009, with about 20 people from 4 research institutes involved, all actively working on particle therapy delivery and development. The first workshop resulted in a summary of recommendations for the treatment of mobile targets, along with a list of requirements to apply these guidelines clinically. The increased interest in the treatment of mobile tumors led to a continuously growing number of attendees: the 2012 edition counted more than 60 participants from 20 institutions and commercial vendors. The focus of research discussions among workshop participants progressively moved from 4D treatment planning to complete 4D treatments, aiming at effective and safe treatment delivery. Current research perspectives on 4D treatments include all critical aspects of time resolved delivery, such as in-room imaging, motion detection, beam application, and quality assurance techniques. This was motivated by the start of first clinical treatments of hepato cellular tumors with a scanned particle beam, relying on gating or abdominal compression for motion mitigation. Up to date research activities emphasize significant efforts in investigating advanced motion mitigation techniques, with a specific interest in the development of dedicated tools for experimental validation. Potential improvements will be made possible in the near future through 4D optimized treatment plans that require upgrades of the currently established therapy control systems for time resolved delivery. But since also these novel optimization techniques rely on the validity of the 4DCT, research focusing on alternative 4D imaging technique, such as MRI based 4DCT generation will continue.
EVALuna2:18197

A generic curriculum development model for the biomedical physics component of the educational and training programmes of the non-physics healthcare professions - Caruana, C. J.; Karenauskaite, V.; Mornstein, V.; Vano, E.; Pace, E.; Lammertsma, A. A.; Maas, A. J.J.; Bert, Christoph; Byrne, B.; Colgan, N.; Essers, M.; Isidoro, J.; et al. (Physica Medica, 2021)
The objective of the study was the construction of a generic curriculum development model for the use of biomedical physics (BMP) educators teaching the non-physics healthcare professions (HCP) in Europe. A comprehensive, qualitative cross-sectional Europe-wide survey of the curricula delivered by BMP in Faculties of Medicine and Health Sciences (FMHS) was carried out. Curricular content was collected from faculty web-sites, curricular documents and textbooks. The survey data was supplemented with semi-structured interviews and direct observation during onsite visits. The number of faculties studied was 118 from 67 universities spread all over Europe, whilst the number of onsite visits/interviews was 15 (geographically distributed as follows: Eastern Europe 6, North Western Europe 5, and South Western Europe 4). EU legislation, recommendations by European national medical councils, educational benchmark statements by higher education quality assurance agencies, research journals concerning HCP education and other documents relevant to standards in clinical practice and undergraduate education were also analyzed. Best practices and BMP learning outcomes were elicited from the curricular materials, interviews and documentation and these were subsequently used to construct the curriculum development model. A structured, comprehensive BMP learning outcomes inventory was designed in the format required by the European Qualifications Framework (EQF). The structures of the inventory and curriculum development model make them ideally suited for use by BMP involved in European curriculum development initiatives for the HCP.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Biomedical physics; Curriculum development; Healthcare professions; Medical devices

A Kernel-based Framework for Intra-fractional Respiratory Motion Estimation in Radiation Therapy - Geimer, Tobias; Unberath, Mathias; Birlutiu, Adriana; Taubmann, Oliver; Wölfelschneider, Jens; Bert, Christoph; Maier, Andreas (Proceedings of the 2017 IEEE International Symposium on Biomedical Imaging, 2017)
In radiation therapy, tumor tracking allows to adjust the beam such that it follows the respiration-induced tumor motion. However, most clinical approaches rely on implanted fiducial markers to locate the tumor and, thus, only provide sparse information. Motion models have been investigated to estimate dense internal displacement fields from an external surrogate signal, such as range imaging. With increasing surrogate complexity, we propose a respiratory motion estimation framework based on kernel ridge regression to cope with high-dimensional domains. This approach was validated on five patient datasets, consisting of a planning 4DCT and a follow-up 4DCT for each patient. Mean residual error was at best 2.73 ± 0.25 mm, but varied greatly between patients.<br
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.akerne_4
Keywords: Motion Models; Range Imaging; Radiation Therapy; Kernel Trick; Active Shape Models

A Kernel Ridge Regression Model for Respiratory Motion Estimation in Radiotherapy - Geimer, Tobias; Birlutiu, Adriana; Unberath, Mathias; Taubmann, Oliver; Bert, Christoph; Maier, Andreas (Bildverarbeitung für die Medizin 2017 - Algorithmen - Systeme - Anwendungen, 2017)
This paper discusses a kernel ridge regression (KRR) model for motion estimation in radiotherapy. Using KRR, dense internal motion fields are estimated from high-dimensional surrogates without the need for prior dimensionality reduction. We compare the proposed model to a related approach with dimensionality reduction in the form of principal component analysis and principle component regression. Evaluation was performed in a simulation study based on nine 4D CT patient data sets achieving a mean estimation error of 0.84 ± 0.21 mm for our approach.<br
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.akerne_3

Analysis of Head and Neck Lymph Node Metastasis Distribution by using Deep Learning automated Lymph Node Level Contouring - Weissmann, Thomas; Huang, Yixing; Speer, Stefan; Semrau, Sabine; Bert, Christoph; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

An Experimental Survey of Incremental Transfer Learning for Multicenter Collaboration - Huang, Yixing; Bert, Christoph; Gomaa, Ahmed; Fietkau, Rainer; Maier, Andreas; Putz, Florian (IEEE Access, 2024)
Keywords: Continual learning; multicenter collaboration; federated learning; data privacy; deep learning; peer-to-peer; domain incremental learning; incremental transfer learning

An extension to the OVH concept for knowledge-based dose volume histogram prediction in lung tumor volumetric-modulated arc therapy - Brand, Johann; Szkitsak, Juliane; Ott, Oliver; Bert, Christoph; Speer, Stefan (Journal of Applied Clinical Medical Physics, 2025)
Purpose: Volumetric-modulated arc therapy (VMAT) treatment planning allows a compromise between a sufficient coverage of the planning target volume (PTV) and a simultaneous sparing of organs-at-risk (OARs). Particularly in the case of lung tumors, deciding whether it is possible or worth spending more time on further improvements of a treatment plan is difficult. Therefore, this work aims to develop a knowledge-based, structure-dependent, automated dose volume histogram (DVH) prediction module for lung tumors. Methods: The module is based on comparing geometric relationships between the PTV and the surrounding OARs. Therefore, treatment plan and structure data of 106 lung cancer cases, each treated in 28 fractions and 180 cGy/fx, were collected. To access the spatial information, a two-dimensional metric named overlap volume histogram (OVH) was used. Due to the rotational symmetry of the OVH and the typically coplanar setup of the VMAT technique, OVH is complemented by the so-called overlap-z-histogram (OZH). A set of achievable DVHs is predicted by identifying plans in the database with similar OVH and OZH. By splitting the dataset into a test set of 22 patients and a training set of 84 patients, the prediction capability of the OVH-OZH combination was evaluated. For comparison between the predicted and achieved DVH curves the coefficient of determination R2 was calculated. Results: The total lung showed strong linearity between predicted and achieved DVH curves for the OVH-OZH combination, resulting in a (Formula presented.) value close to 1 (0.975 ± 0.022). The heart benefits the most of the OZH resulting in a high prediction capability, with a higher (Formula presented.) of 0.962 ± 0.036 compared to the prediction with OVH only (0.897 ± 0.087). Conclusion: The combination of OZH and OVH was suitable for building a knowledge-based automated DVH prediction module. Implementing this method into the clinical workflow of treatment planning will contribute to advancing the quality of VMAT plans.
CRIS-Team Scopus Importer:2025-04-18
Keywords: DVH prediction; lung tumor; VMAT

An Investigation of Feature-based Nonrigid Image Registration using Gaussian Process - Bayer, Siming; Spiske, Ute; Geimer, Tobias; Luo, Jie; Wells III, William M.; Ostermeier, Martin; Fahrig, Rebecca; Arya, Nabavi; Bert, Christoph; Eyüpoglu, Ilker Yasin; Maier, Andreas (Algorithmen – Systeme – Anwendungen. Proceedings des Workshops, 2020)
For a wide range of clinical applications, such as adaptive treatment planning or intraoperative image update, feature-based deformable registration (FDR) approaches are widely employed because of their simplicity and low computational complexity. FDR algorithms estimate a dense displacement field by interpolating a sparse field, which is given by the established correspondence between selected features. In this paper, we consider the deformation field as a Gaussian Process (GP), whereas the selected features are regarded as prior information on the valid deformations. Using GP, we are able to estimate the both dense displacement field and a corresponding uncertainty map at once. Furthermore, we evaluated the performance of different hyperparameter settings for squared exponential kernels with synthetic, phantom and clinical data respectively. The quantitative comparison shows, GP-based interpolation has performance on par with state-of-the-art B-spline interpolation. The greatest clinical benefit of GP-based interpolation is that it gives a reliable estimate of the mathematical uncertainty of the calculated dense displacement map.<br

Announcement of the scientific Awards to be awarded in 2020 - Bert, Christoph (Zeitschrift für Medizinische Physik, 2019)
EVALuna2:213673

A novel concept for CT with fixed anodes (FACT): Medical imaging based on the feasibility of thermal load capacity - Kellermeier, Markus; Bert, Christoph; Müller, Reinhold (Physica Medica, 2015)
Focussing primarily on thermal load capacity, we describe the performance of a novel fixed anode CT (FACT) compared with a 100 kW reference CT. Being a fixed system, FACT has no focal spot blurring of the X-ray source during projection. Monte Carlo and finite element methods were used to determine the fluence proportional to thermal capacity. Studies of repeated short-time exposures showed that FACT could operate in pulsed mode for an unlimited period. A virtual model for FACT was constructed to analyse various temporal sequences for the X-ray source ring, representing a circular array of 1160 fixed anodes in the gantry. Assuming similar detector properties at a very small integration time, image quality was investigated using an image reconstruction library. Our model showed that approximately 60 gantry rounds per second, i.e. 60 sequential targetings of the 1160 anodes per second, were required to achieve a performance level equivalent to that of the reference CT (relative performance, RP = 1) at equivalent image quality. The optimal projection duration in each direction was about 10 ?s. With a beam pause of 1 ?s between projections, 78.4 gantry rounds per second with consecutive source activity were thermally possible at a given thermal focal spot. The settings allowed for a 1.3-fold (RP = 1.3) shorter scan time than conventional CT while maintaining radiation exposure and image quality. Based on the high number of rounds, FACT supports a high image frame rate at low doses, which would be beneficial in a wide range of diagnostic and technical applications.
EVALuna2:18269

Assessing Organ-at-risk Auto-contouring Solutions: Which Metrics are most predictive of clinical Time Savings? - Putz, Florian; Huang, Yixing; Weissmann, Thomas; Mansoorian, Sina; Lamrani, Allison; Sommer, P.; Fischer, S.; Srinivasan, A.; Frey, Benjamin; Gaipl, Udo; Ott, Oliver; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Assessment of needle bending and tracking requirements for optimized needle placement in combined intracavitary/interstitial gynecologic brachytherapy - Karius, Andre; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Merten, Ricarda; Fietkau, Rainer; Bert, Christoph; Schweizer, Claudia (Strahlentherapie und Onkologie, 2025)
Purpose: Needle tracking using external prediction techniques such as optical tracking is a modern approach aimed at improving implantation accuracy in gynecologic brachytherapy. This study aims to investigate the corresponding impact of needle bending in situ and to analyze needle path deviations from the intended locations occurring in our current clinical workflow that only considers ultrasound imaging without tracking. Methods: We developed a semi-automated approach for reconstructing brachytherapy needles based on planning CTs and compared the respective accuracy to the also determined intra-observer variability of manual reconstructions. Based on this, we measured needle bending in situ for 89 patients and calculated the Euclidean distances between actual needle tips and needle tip predictions both longitudinally and laterally to the insertion direction. Furthermore, we compared actual and intended spacings between inserted needles to estimate implantation uncertainties with respect to our current clinical workflow. Results: Our developed reconstruction featured an accuracy of 0.17 ± 0.08 mm, which was improved compared to the intra-observer variability of 0.21 ± 0.11 mm. Needle bending depended strongly on needle length and ranged from 3.6 ± 2.1 mm for 100–120 mm needles up to 7.9 ± 3.0 mm for 200–220 mm needles. Deflections in the transverse direction were substantially higher than tip deviations in the longitudinal direction. Furthermore, we found deviations from an equidistant spacing between needle paths of 1.4 ± 1.2 mm in the transverse direction. Conclusion: Inserting brachytherapy needles can be substantially affected by transverse needle bending in situ, which should therefore be corrected for in prediction approaches such as optical tracking.
CRIS-Team Scopus Importer:2025-02-21
Keywords: Adaptive brachytherapy; Image guidance; Intraoperative navigation; Needle displacement; Optical infrared tracking

Assessment of segmentation dependence in macroscopic lung cavity extraction - Khdeir, Asmaa; Geimer, Tobias; Chen, Shuqing; Goppert, Eric; Dankbar, Maximilian; Bert, Christoph; Maier, Andreas (Informatik aktuell, 2018)
Training of respiratory motion models and population-based patient phantoms of the lung often requires the definition of the entire lung cavity region in the 4D-CT. To ease the workload of clinical experts, automatic selection is highly desirable. Many lung cavity extraction methods rely on a pre-segmented lung volume.
CRIS-Team Scopus Importer:2022-06-05

Assessment of the implant geometry in fractionated interstitial HDR breast brachytherapy using an electromagnetic tracking system - Kellermeier, Markus; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (Brachytherapy, 2018)
PURPOSE: During the partial-breast treatment course by interstitial brachytherapy, electromagnetic tracking (EMT) was applied to measure the implant geometry. Implant-geometry variation, choice of reference data, and three registration methods were assessed. METHODS AND MATERIALS: The implant geometry was measured in 28 patients after catheter implantation (EMTbed), during CT imaging (EMTCT), and in each of up to n = 9 treatment fractions (EMTF(k), k = 1, 2,… n). EMTF(k) were registered to the planned implant reconstruction (CTplan) by using all dwell positions (DPs), the button centers, or three fiducial sensors on the patient's skin. Variation in implant geometry obtained from EMTF(k) was assessed for EMTbed, EMTCT, and CTplan. RESULTS: EMT was used to measure 3932 catheters. A duration of 6.5 ± 1.7 min was needed for each implant measurement (mean, 17 catheters) plus setup of the EMT system. Data registration based on the DP deviated significantly lower than registration on button centers or fiducial sensors. Within a registration group, there was a <0.5-mm difference in the choice of reference data. Using CTplan as reference for registration, the mean residual distance of DPs on EMT-derived DPs was found at 2.1 ± 1.6 mm (EMTbed), 1.3 ± 0.9 mm (EMTCT), and 2.5 ± 1.5 mm (EMTF(k)). CONCLUSIONS: EMT can assess the implant geometry in high-dose-rate interstitial brachytherapy breast treatments. EMTbed, EMTCT, and CTplan data can serve as reference for assessment of implant changes.
EVALuna2:36444

A tool to automatically analyze electromagnetic tracking data from high dose rate brachytherapy of breast cancer patients - Goetz, Th. I.; Lahmer, Godehard; Strnad, Vratislav; Bert, Christoph; Hensel, Bernhard; Tome, A. M.; Lang, E. W. (PLoS ONE, 2017)
During High Dose Rate Brachytherapy (HDR-BT) the spatial position of the radiation source inside catheters implanted into a female breast is determined via electromagnetic tracking (EMT). Dwell positions and dwell times of the radiation source are established, relative to the patient's anatomy, from an initial X-ray-CT-image. During the irradiation treatment, catheter displacements can occur due to patient movements. The current study develops an automatic analysis tool of EMT data sets recorded with a solenoid sensor to assure concordance of the source movement with the treatment plan. The tool combines machine learning techniques such as multi-dimensional scaling (MDS), ensemble empirical mode decomposition (EEMD), singular spectrum analysis (SSA) and particle filter (PF) to precisely detect and quantify any mismatch between the treatment plan and actual EMT measurements. We demonstrate that movement artifacts as well as technical signal distortions can be removed automatically and reliably, resulting in artifact-free reconstructed signals. This is a prerequisite for a highly accurate determination of any deviations of dwell positions from the treatment plan.
EVALuna2:33034

Atrioventricular node ablation in Langendorff-perfused porcine hearts using carbon ion particle therapy: methods and an in vivo feasibility investigation for catheter-free ablation of cardiac arrhythmias - Lehmann, H. Immo; Richter, Daniel; Prokesch, Hannah; Graeff, Christian; Prall, Matthias; Simoniello, Palma; Fournier, Claudia; Bauer, Julia; Kaderka, Robert; Weymann, Alexander; Szabó, Gábor; Sonnenberg, Karin; et al. (Circulation-Arrhythmia and Electrophysiology, 2015)
Particle therapy, with heavy ions such as carbon-12 ((12)C), delivered to arrhythmogenic locations of the heart could be a promising new means for catheter-free ablation. As a first investigation, we tested the feasibility of in vivo atrioventricular node ablation, in Langendorff-perfused porcine hearts, using a scanned 12C beam.Intact hearts were explanted from 4 (30-40 kg) pigs and were perfused in a Langendorff organ bath. Computed tomographic scans (1 mm voxel and slice spacing) were acquired and (12)C ion beam treatment planning (optimal accelerator energies, beam positions, and particle numbers) for atrioventricular node ablation was conducted. Orthogonal x-rays with matching of 4 implanted clips were used for positioning. Ten Gray treatment plans were repeatedly administered, using pencil beam scanning. After delivery, positron emission tomography-computed tomographic scans for detection of ?(+) ((11)C) activity were obtained. A (12)C beam with a full width at half maximum of 10 mm was delivered to the atrioventricular node. Delivery of 130 Gy caused disturbance of atrioventricular conduction with transition into complete heart block after 160 Gy. Positron emission computed tomography demonstrated dose delivery into the intended area. Application did not induce arrhythmias. Macroscopic inspection did not reveal damage to myocardium. Immunostaining revealed strong ?H2AX signals in the target region, whereas no ?H2AX signals were detected in the unirradiated control heart.This is the first report of the application of a (12)C beam for ablation of cardiac tissue to treat arrhythmias. Catheter-free ablation using 12C beams is feasible and merits exploration in intact animal studies as an energy source for arrhythmia elimination.
EVALuna2:18308

Automated data processing and BigData in radiation therapy - Schmidt, O.; Ballmann, N.; Bert, Christoph; Fietkau, Rainer (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Automating implant reconstruction in interstitial brachytherapy of the breast: A hybrid approach combining electromagnetic tracking and image segmentation - Dürrbeck, Christopher; Sauer, Birte; Lotter, Michael; Kreppner, Stephan; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2022)
Background and purpose: To develop a method for automatic reconstruction of catheter implants in interstitial brachytherapy (iBT) of the breast by means of electromagnetic tracking (EMT) with the goal of making treatment planning as time-effective and accurate as possible. Materials and methods: The implant geometry of 64 patients was recorded using an afterloader prototype with EMT functionality immediately after the planning CT. EMT data were transferred to the CT image space by rigidly registering the catheter fixation buttons as landmarks. To further improve reconstruction accuracy, the EMT reconstruction points were used as starting points to define small regions of interest (ROI) in the CT image. Within these ROIs, the catheter track was segmented in the CT using image processing operations such as thresholding and blob detection, thus refining the reconstruction. The perpendicular distance between the refined EMT implant reconstruction points and the manually reconstructed catheters by an experienced treatment planner was calculated as a measure of their geometric agreement. Results: Geometrically, the refined EMT based implant reconstruction shows excellent agreement with the manual reconstruction. The median distance across all patients is 0.25 mm and the 95th percentile is 1 mm. Refinement takes approximately 0.5 s per reconstruction point and typically does not exceed 3 min per implant at no user interaction. Conclusion: The refined EMT based implant reconstruction proved to be extremely accurate and fast compared to manual reconstruction. The presented procedure can in principle be easily transferred to clinical routine and therefore has enormous potential to provide significant time savings in iBT treatment planning whilst improving reconstruction accuracy.
CRIS-Team Scopus Importer:2022-10-28
Keywords: Breast cancer; Electromagnetic tracking; Implant reconstruction; Interstitial brachytherapy

Automation of Implant Reconstruction in Interstitial Brachytherapy of the Breast Using Electromagnetic Tracking - Dürrbeck, Christopher; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (MEDICAL PHYSICS, 2022)
CRIS-Team WoS Importer:2022-07-08

Automation of radiation treatment planning : Evaluation of head and neck cancer patient plans created by the Pinnacle3scripting and Auto-Planning functions - Speer, Stefan; Klein, Andreas; Kober, Lukas; Weiss, Alexander; Yohannes, Indra; Bert, Christoph (Strahlentherapie und Onkologie, 2017)
BACKGROUND: Intensity-modulated radiotherapy (IMRT) techniques are now standard practice. IMRT or volumetric-modulated arc therapy (VMAT) allow treatment of the tumor while simultaneously sparing organs at risk. Nevertheless, treatment plan quality still depends on the physicist's individual skills, experiences, and personal preferences. It would therefore be advantageous to automate the planning process. This possibility is offered by the Pinnacle3treatment planning system (Philips Healthcare, Hamburg, Germany) via its scripting language or Auto-Planning (AP) module. MATERIALS AND METHODS: AP module results were compared to in-house scripts and manually optimized treatment plans for standard head and neck cancer plans. Multiple treatment parameters were scored to judge plan quality (100 points = optimum plan). Patients were initially planned manually by different physicists and re-planned using scripts or AP. RESULTS AND DISCUSSION: Script-based head and neck plans achieved a mean of 67.0 points and were, on average, superior to manually created (59.1 points) and AP plans (62.3 points). Moreover, they are characterized by reproducibility and lower standard deviation of treatment parameters. Even less experienced staff are able to create at least a good starting point for further optimization in a short time. However, for particular plans, experienced planners perform even better than scripts or AP. Experienced-user input is needed when setting up scripts or AP templates for the first time. Moreover, some minor drawbacks exist, such as the increase of monitor units (+35.5% for scripted plans). CONCLUSION: On average, automatically created plans are superior to manually created treatment plans. For particular plans, experienced physicists were able to perform better than scripts or AP; thus, the benefit is greatest when time is short or staff inexperienced.
EVALuna2:33035

Automatisation of catheter reconstruction in interstitial breast BT using electromagnetic tracking - Dürrbeck, Christopher; Abu-Hossin, N.; Lotter, M.; Kreppner, Stephan; Lubgan, Dorota; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-07-15

Benchmarking ChatGPT-4 on a radiation oncology in-training exam and Red Journal Gray Zone cases: potentials and challenges for AI-assisted medical education and decision making in radiation oncology - Huang, Yixing; Gomaa, Ahmed; Semrau, Sabine; Haderlein, Marlen; Lettmaier, Sebastian; Weissmann, Thomas; Grigo, Johanna; Ben Tkhayat, Hassen; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Maier, Andreas; et al. (Frontiers in Oncology, 2023)
Keywords: Large language model; Radiotherapy; Natural language processing; Artificial intelligence; Gray Zone; Clinical decision support (CDS)

Breakthroughs in modern brachytherapy are transforming cancer care - Fröhlich, Georgina; Gomez-Iturriaga, Alfonso; Eminowicz, Gemma; Bert, Christoph; Tedgren, Åsa Carlsson; Stewart, Alexandra J.; Wisgrill, Bernd; Muren, Ludvig P. (Physics and Imaging in Radiation Oncology, 2025)
CRIS-Team Scopus Importer:2025-05-30

CBCT-based Detection and Analysis of the Positional Stability of implanted Gold Markers and Changes in the Shape of the Rectal Balloon during the Radiotherapy of the Prostate-Ca - Kallis, Karoline; Brandt, Tobias; Strnad, Vratislav; Lettmaier, S.; Fietkau, Rainer; Maier, Anne-Kathrin; Bert, Christoph (2017)
EVALuna2:32885

Challenges of radiotherapy: report on the 4D treatment planning workshop 2013 - Knopf, Antje; Nill, Simeon; Yohannes, Indra; Graeff, Christian; Dowdell, Stephen; Kurz, Christopher; Sonke, Jan-Jakob; Biegun, Aleksandra K.; Lang, Stephanie; Mcclelland, Jamie; Champion, Benjamin; Fast, Martin; et al. (Physica Medica, 2014)
This report, compiled by experts on the treatment of mobile targets with advanced radiotherapy, summarizes the main conclusions and innovations achieved during the 4D treatment planning workshop 2013. This annual workshop focuses on research aiming to advance 4D radiotherapy treatments, including all critical aspects of time resolved delivery, such as in-room imaging, motion detection, motion managing, beam application, and quality assurance techniques. The report aims to revise achievements in the field and to discuss remaining challenges and potential solutions. As main achievements advances in the development of a standardized 4D phantom and in the area of 4D-treatment plan optimization were identified. Furthermore, it was noticed that MR imaging gains importance and high interest for sequential 4DCT/MR data sets was expressed, which represents a general trend of the field towards data covering a longer time period of motion. A new point of attention was work related to dose reconstructions, which may play a major role in verification of 4D treatment deliveries. The experimental validation of results achieved by 4D treatment planning and the systematic evaluation of different deformable image registration methods especially for inter-modality fusions were identified as major remaining challenges. A challenge that was also suggested as focus for future 4D workshops was the adaptation of image guidance approaches from conventional radiotherapy into particle therapy. Besides summarizing the last workshop, the authors also want to point out new evolving demands and give an outlook on the focus of the next workshop.
EVALuna2:18242

Change in the radio-oncological Treatment Concept for Brain Metastases through a dedicated Radiotherapy Planning MRI - Voigt, R.; Masitho, Siti; Grigo, Johanna; Reissig, L.; Uder, Michael; Semrau, Sabine; Fietkau, Rainer; Bert, Christoph; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Choosing a reference phase for a dynamic tumor tracking treatment: A new degree of freedom? - Ziegler, Marc; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (Medical Physics, 2019)
Purpose: With the introduction of dynamic tumor tracking in radiotherapy, it is possible to irradiate moving targets with minimal safety margins. However, most dynamic tumor tracking techniques rely on changing the beam geometry by, for example, adapting the multileaf collimator (MLC) positions or rotating the LINAC head. These changes are relative to a reference position which is determined by a specific breathing phase. Since these changes in the beam path also influence the delivered dose, choosing a different reference position based on a different breathing phase impacts the applied dose to the patient. This work investigates the influence of choosing different reference breathing phases on the dose distribution. Methods: The Vero system tracks the moving target by performing a pan and tilt rotation of the LINAC head. For 13 patients, the target position was extracted from every phase of a four-dimensional computed tomography (4DCT) and the pan and tilt values were determined with respect to three different reference phases. These reference phases were inspiration, expiration, and the midventilation. For all reference phases, a 4D dose calculation was performed on the 4DCT regarding the respective pan and tilt values. Furthermore, the applied dose to the target and surrounding organs at risk was calculated. To accumulate the dose distribution, weights from the actual patient breathing motion were determined. The weights were calculated from the breathing motions from different days to investigate the impact of daily variations in the breathing motion onto the accumulated dose distribution. All obtained values were then compared to the static treatment plan. Results: The mean and maximum doses applied to the target or surrounding organs at risk show no general behavior depending on the different reference phases. Nevertheless, for some patients, large differences (approx. 30%) in the applied dose to certain organs at risk could be observed, whereas the applied dose to the target shows no dependency on the different reference phases. However, the mean target dose is in all cases approx. 1.5% below the reference value from the static treatment plan. Conclusion: Although no general dependency of the applied dose on the selected reference phase could be found, the choice of the reference phase can have great impact on the organ at risk dose for some patients. Thus, the choice of the reference phase used for patient positioning should be considered during treatment planning since it can be seen as a new degree of freedom of a treatment based on tracking.
CRIS-Team Scopus Importer:2019-07-16
Keywords: 4D dose calculation; dynamic tumor tracking; liver cancer; lung cancer

Clinical application of breathing-adapted 4D CT: image quality comparison to conventional 4D CT - Werner, René; Szkitsak, Juliane; Madesta, Frederic; Büttgen, Laura; Wimmert, Lukas; Sentker, Thilo; Fietkau, Rainer; Haderlein, Marlen; Bert, Christoph; Gauer, Tobias; Hofmann, Christian (Strahlentherapie und Onkologie, 2023)
Purpose: 4D CT imaging is an integral part of 4D radiotherapy workflows. However, 4D CT data often contain motion artifacts that mitigate treatment planning. Recently, breathing-adapted 4D CT (i4DCT) was introduced into clinical practice, promising artifact reduction in in-silico and phantom studies. Here, we present an image quality comparison study, pooling clinical patient data from two centers: a new i4DCT and a conventional spiral 4D CT patient cohort. Methods: The i4DCT cohort comprises 129 and the conventional spiral 4D CT cohort 417 4D CT data sets of lung and liver tumor patients. All data were acquired for treatment planning. The study consists of three parts: illustration of image quality in selected patients of the two cohorts with similar breathing patterns; an image quality expert rater study; and automated analysis of the artifact frequency. Results: Image data of the patients with similar breathing patterns underline artifact reduction by i4DCT compared to conventional spiral 4D CT. Based on a subgroup of 50 patients with irregular breathing patterns, the rater study reveals a fraction of almost artifact-free scans of 89% for i4DCT and only 25% for conventional 4D CT; the quantitative analysis indicated a reduction of artifact frequency by 31% for i4DCT. Conclusion: The results demonstrate 4D CT image quality improvement for patients with irregular breathing patterns by breathing-adapted 4D CT in this first corresponding clinical data image quality comparison study.
CRIS-Team Scopus Importer:2023-04-14
Keywords: 4D CT; 4D radiotherapy; Image artifacts; Image quality

Clinical experience with markerless tumor tracking - Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Clinical implementations of 4D pencil beam scanned particle therapy: Report on the 4D treatment planning workshop 2016 and 2017 - Trnkova, Petra; Knaeusl, Barbara; Actis, Oxana; Bert, Christoph; Biegun, Aleksandra K.; Boehlen, Till T.; Furtado, Hugo; Mcclelland, Jamie; Mori, Shinichiro; Rinaldi, Ilaria; Rucinski, Antoni; Knopf, Antje C. (Physica Medica, 2018)
In 2016 and 2017, the 8th and 9th 4D treatment planning workshop took place in Groningen (the Netherlands) and Vienna (Austria), respectively. This annual workshop brings together international experts to discuss research, advances in clinical implementation as well as problems and challenges in 4D treatment planning, mainly in spot scanned proton therapy. In the last two years several aspects like treatment planning, beam delivery, Monte Carlo simulations, motion modeling and monitoring, QA phantoms as well as 4D imaging were thoroughly discussed. This report provides an overview of discussed topics, recent findings and literature review from the last two years. Its main focus is to highlight translation of 4D research into clinical practice and to discuss remaining challenges and pitfalls that still need to be addressed and to be overcome.
EVALuna2:36473

Combination of Markerless Surrogates for Motion Estimation in Radiation Therapy - Geimer, Tobias; Unberath, Mathias; Taubmann, Oliver; Bert, Christoph; Maier, Andreas (Computer Assisted Radiology and Surgery (CARS) 2016: Proceedings of the 30th International Congress and Exhibition, 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.IMMD5.combin_2
Keywords: Motion Modeling; X-ray; Range Imaging; Dimensionality Reduction; Regression

Commissioning of an integrated platform for time-resolved treatment delivery in scanned ion beam therapy by means of optical motion monitoring - Fattori, Giovanni; Saito, N.; Seregni, M.; Kaderka, R.; Pella, A.; Constantinescu, A.; Riboldi, Marco; Steidl, P.; Cerveri, P.; Bert, Christoph; Durante, Marco; Baroni, G. (Technology in Cancer Research & Treatment, 2014)
The integrated use of optical technologies for patient monitoring is addressed in the framework of time-resolved treatment delivery for scanned ion beam therapy. A software application has been designed to provide the therapy control system (TCS) with a continuous geometrical feedback by processing the external surrogates tridimensional data, detected in real-time via optical tracking. Conventional procedures for phase-based respiratory phase detection were implemented, as well as the interface to patient specific correlation models, in order to estimate internal tumor motion from surface markers. In this paper, particular attention is dedicated to the quantification of time delays resulting from system integration and its compensation by means of polynomial interpolation in the time domain. Dedicated tests to assess the separate delay contributions due to optical signal processing, digital data transfer to the TCS and passive beam energy modulation actuation have been performed. We report the system technological commissioning activities reporting dose distribution errors in a phantom study, where the treatment of a lung lesion was simulated, with both lateral and range beam position compensation. The zero-delay systems integration with a specific active scanning delivery machine was achieved by tuning the amount of time prediction applied to lateral (14.61 ± 0.98 ms) and depth (34.1 ± 6.29 ms) beam position correction signals, featuring sub-millimeter accuracy in forward estimation. Direct optical target observation and motion phase (MPh) based tumor motion discretization strategies were tested, resulting in 20.3(2.3)% and 21.2(9.3)% median (IQR) percentual relative dose difference with respect to static irradiation, respectively. Results confirm the technical feasibility of the implemented strategy towards 4D treatment delivery, with negligible percentual dose deviations with respect to static irradiation.
EVALuna2:18207

Comparison of dose calculation approaches and clinical dose–response in image-guided head&neck brachytherapy of the oral cavity - Schaller, Sabrina; Strnad, Vratislav; Schweizer, Claudia; Lubgan, Dorota; Merten, Ricarda; Fietkau, Rainer; Bert, Christoph; Karius, Andre (Clinical and Translational Radiation Oncology, 2025)
Purpose: Model-based dose calculation algorithms (MBDCAs) are increasingly applied in brachytherapy, but their considerations in dose–response analyses is still lacking. This study aimed to assess correlations between both TG-43 and MBDCA dosimetry and reports on clinical outcomes for oral cavity brachytherapy. Methods: We considered 158 patients with oral cavity cancer treated in our institution between 2012 and 2021. Survival outcomes and toxicity (soft tissue necrosis, osteoradionecrosis, mucositis, xerostomia) were reported for a median follow-up of 80 months (2–152 months). All clinical, TG-43 based treatment plans were re-calculated using a MBDCA integrated into our planning system. Differences considering several target volume, tissue, and bone dose parameters were evaluated. Parameter correlations with clinical outcomes and thresholds associated with increased toxicity were investigated. Results: Cumulative local recurrence, soft-tissue necrosis, osteoradionecrosis, mucositis, and xerostomia rate were 21 %, 22 %, 28 % and 79 % considering all patients. Substantial differences between MBDCA and TG-43 were observed, especially regarding high-dose areas with changes up to 19 %. A number of dose-toxicity correlations were observed, as for osteoradionecrosis (1.6 % vs. 10.3 % for bone D2ccm ≥ 59.3 Gy), soft tissue necrosis (16 % vs. 32 % for tissue D5ccm ≥ 87.7 Gy), and local recurrence (13 % vs. 25 % for dose non-uniformity ratio < 0.29) (using the MBDCA). Target volumes ≥ 10.2–11.8ccm were associated with increased rates of soft tissue necrosis and mucositis. Dosimetric thresholds and correlations differed between TG-43 and MBDCA. Conclusion: For oral cavity brachytherapy, several important dosimetric thresholds associated with increased toxicity were determined. MBDCAs for corresponding dose calculations should be advanced and used in clinical practice.
CRIS-Team Scopus Importer:2025-05-16

Comparison of intelligent 4D CT sequence scanning and conventional spiral 4D CT: A first comprehensive phantom study - Werner, René; Szkitsak, Juliane; Sentker, Thilo; Madesta, Frederic; Schwarz, Annette; Fernolendt, Susanne; Vornehm, Marc; Gauer, Tobias; Bert, Christoph; Hofmann, Christian (Physics in Medicine and Biology, 2021)
4D CT imaging is a cornerstone of 4D radiotherapy treatment. Clinical 4D CT data are, however, often affected by severe artifacts. The artifacts are mainly caused by breathing irregularity and retrospective correlation of breathing phase information and acquired projection data, which leads to insufficient projection data coverage to allow for proper reconstruction of 4D CT phase images. The recently introduced 4D CT approach i4DCT (intelligent 4D CT sequence scanning) aims to overcome this problem by breathing signal-driven tube control. The present motion phantom study describes the first in-depth evaluation of i4DCT in a real-world scenario. Twenty-eight 4D CT breathing curves of lung and liver tumor patients with pronounced breathing irregularity were selected to program the motion phantom. For every motion pattern, 4D CT imaging was performed with i4DCT and a conventional spiral 4D CT mode. For qualitative evaluation, the reconstructed 4D CT images were presented to clinical experts, who scored image quality. Further quantitative evaluation was based on established image intensity-based artifact metrics to measure (dis)similarity of neighboring image slices. In addition, beam-on and scan times of the scan modes were analyzed. The expert rating revealed a significantly higher image quality for the i4DCT data. The quantitative evaluation further supported the qualitative: While 20% of the slices of the conventional spiral 4D CT images were found to be artifact-affected, the corresponding fraction was only 4% for i4DCT. The beam-on time (surrogate of imaging dose) did not significantly differ between i4DCT and spiral 4D CT. Overall i4DCT scan times (time between first beam-on and last beam-on event, including scan breaks to compensate for breathing irregularity) were, on average, 53% longer compared to spiral CT. Thus, the results underline that i4DCT significantly improves 4D CT image quality compared to standard spiral CT scanning in the case of breathing irregularity during scanning.
CRIS-Team Scopus Importer:2021-02-12
Keywords: 4D CT; I4DCT; Motion artifacts; Radiotherapy

Comparison of MRI coils and RT-positioning systems for optimal MRI scanning in SRS cases - Mengling, Veit; Perrin, R.; Putz, Florian; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Complex-valued neural networks to speed-up MR thermometry during hyperthermia using Fourier PD and PDUNet - Khatun, Rupali; Chatterjee, Soumick; Bert, Christoph; Wadepohl, Martin; Ott, Oliver; Semrau, Sabine; Fietkau, Rainer; Nürnberger, Andreas; Gaipl, Udo; Frey, Benjamin (Scientific Reports, 2025)
Hyperthermia (HT) in combination with radio- and/or chemotherapy has become an accepted cancer treatment for distinct solid tumour entities. In HT, tumour tissue is exogenously heated to temperatures between 39 and 43 °C for 60 min. Temperature monitoring can be performed non-invasively using dynamic magnetic resonance imaging (MRI). However, the slow nature of MRI leads to motion artefacts in the images due to the movements of patients during image acquisition. By discarding parts of the data, the speed of the acquisition can be increased - known as undersampling. However, due to the invalidation of the Nyquist criterion, the acquired images might be blurry and can also produce aliasing artefacts. The aim of this work was, therefore, to reconstruct highly undersampled MR thermometry acquisitions with better resolution and with fewer artefacts compared to conventional methods. The use of deep learning in the medical field has emerged in recent times, and various studies have shown that deep learning has the potential to solve inverse problems such as MR image reconstruction. However, most of the published work only focuses on the magnitude images, while the phase images are ignored, which are fundamental requirements for MR thermometry. This work, for the first time, presents deep learning-based solutions for reconstructing undersampled MR thermometry data. Two different deep learning models have been employed here, the Fourier Primal-Dual network and the Fourier Primal-Dual UNet, to reconstruct highly undersampled complex images of MR thermometry. MR images of 44 patients with different sarcoma types who received HT treatment in combination with radiotherapy and/or chemotherapy were used in this study. The method reduced the temperature difference between the undersampled MRIs and the fully sampled MRIs from 1.3 to 0.6 °C in full volume and 0.49 °C to 0.06 °C in the tumour region for a theoretical acceleration factor of 10.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Complex image; Deep learning; Hyperthermia; MR image reconstruction; MR reconstruction; MR thermometry; MRI; Undersampled; Undersampled MRI

Comprehensive Multimodal Deep Learning Survival Prediction Enabled by a Transformer Architecture: A Multicenter Study in Glioblastoma - Gomaa, Ahmed; Huang, Yixing; Hagag, Amr; Schmitter, Charlotte; Höfler, Daniel; Weissmann, Thomas; Breininger, Katharina; Schmidt, Manuel; Stritzelberger, Jenny; Delev, Daniel; Coras, Roland; Dörfler, Arnd; et al. (Neuro-Oncology Advances, 2024)
Keywords: Survival prediction; deep learning; glioblastoma; MR; prognosis; multimodal data

Cone-beam CT imaging with laterally enlarged field of view based on independently movable source and detector - Karius, Andre; Szkitsak, Juliane; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Medical Physics, 2023)
Background: CBCT imaging with field of views (FOVs) exceeding the size of scans acquired in the conventional imaging geometry, i.e. with opposing source and detector, is of high clinical importance for many medical fields. A novel approach for enlarged FOV scanning with one full-scan (EnFOV360) or two short-scans (EnFOV180) using an O-arm system arises from non-isocentric imaging based on independent source and detector rotations. Purpose: The presentation, description, and experimental validation of this novel approach and the novel scanning techniques EnFOV360 and EnFOV180 for an O-arm system forms the scope of this work. Methods: We describe the EnFOV360, EnFOV180, and non-isocentric imaging techniques for the acquisition of laterally extended FOVs. For their experimental validation, scans of dedicated quality assurance as well as anthropomorphic phantoms were acquired, with the phantoms being placed both within the tomographic plane and at the longitudinal FOV border with and without lateral shifts from the gantry center. Based on this, geometric accuracy, contrast-noise-ratio (CNR) of different materials, spatial resolution, noise characteristics, as well as CT number profiles were quantitatively assessed. Results were compared to scans performed with the conventional imaging geometry. Results: With EnFOV360 and EnFOV180, we increased the in-plane size of acquired FOVs from 250 × 250 mm2 obtained for the conventional imaging geometry to up to 400 × 400 mm2 for the performed measurements. Geometric accuracy was very high for all scanning techniques with mean values ≤0.21 ± 0.11 mm. CNR and spatial resolution were comparable between isocentric and non-isocentric full-scans as well as EnFOV360, whereas substantial image quality deteriorations in this respect were observed for EnFOV180. Image noise in the isocenter was lowest for conventional full-scans with 13.4 ± 0.2 HU. For laterally shifted phantom positions, noise increased for conventional scans and EnFOV360, whereas noise reductions were observed for EnFOV180. Considering the anthropomorphic phantom scans, both EnFOV360 and EnFOV180 were comparable to conventional full-scans. Conclusion: Both enlarged FOV techniques have high potential for imaging laterally extended FOVs. EnFOV360 revealed an image quality comparable to conventional full-scans in general. EnFOV180 showed an inferior performance particularly regarding CNR and spatial resolution.
CRIS-Team Scopus Importer:2023-05-26
Keywords: cone-beam computed tomography; extended field of view; independent gantry rotations

Correction to: Recent advances in Surface Guided Radiation Therapy (Radiation Oncology, (2020), 15, 1, (187), 10.1186/s13014-020-01629-w) - Freislederer, P.; Kügele, M.; Öllers, M.; Swinnen, A.; Sauer, Tim-Oliver; Bert, Christoph; Giantsoudi, D.; Corradini, S.; Batista, V. (Radiation Oncology, 2020)
Following publication of the original article [1], the authors identified an error in the order of Figs. 2 and 3. The correct representation of figures is provided below. The original article [1] has been corrected.
CRIS-Team Scopus Importer:2020-10-30

Creation of an Electro-magnetic Heat Simulation for Planning Hyperthermia Treatments for Mice - Kahlert, B.; Bert, Christoph; Rückert, Michael; Hensel, Bernhard; Root, Konstantin; Vossiek, Martin; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Decoupling Respiratory and Angular Variation in Rotational X-ray Scans Using a Prior Bilinear Model - Geimer, Tobias; Keall, Paul; Breininger, Katharina; Caillet, Vincent; Dunbar, Michelle; Bert, Christoph; Maier, Andreas (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2019)
Data-driven respiratory signal extraction from rotational X-ray scans is a challenge as angular effects overlap with respiration-induced change in the scene. In this paper, we use the linearity of the X-ray transform to propose a bilinear model based on a prior 4D scan to separate angular and respiratory variation. The bilinear estimation process is supported by a B-spline interpolation using prior knowledge about the trajectory angle. Consequently, extraction of respiratory features simplifies to a linear problem. Though the need for a prior 4D CT seems steep, our proposed use-case of driving a respiratory motion model in radiation therapy usually meets this requirement. We evaluate on DRRs of 5 patient 4D CTs in a leave-one-phase-out manner and achieve a mean estimation error of 3.01% in the gray values for unseen viewing angles. We further demonstrate suitability of the extracted weights to drive a motion model for treatments with a continuously rotating gantry.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Bilinear model; Feature extraction; Motion model; Respiratory signal; X-ray projection

Deep Learning and Registration-Based Mapping for Analyzing the Distribution of Nodal Metastases in Head and Neck Cancer Cohorts: Informing Optimal Radiotherapy Target Volume Design - Weissmann, Thomas; Mansoorian, Sina; May, Matthias; Lettmaier, Sebastian; Höfler, Daniel; Deloch, Lisa; Speer, Stefan; Balk, Matthias; Frey, Benjamin; Gaipl, Udo; Bert, Christoph; Distel, Luitpold; et al. (Cancers, 2023)
We introduce a deep-learning- and a registration-based method for automatically analyzing the spatial distribution of nodal metastases (LNs) in head and neck (H/N) cancer cohorts to inform radiotherapy (RT) target volume design. The two methods are evaluated in a cohort of 193 H/N patients/planning CTs with a total of 449 LNs. In the deep learning method, a previously developed nnU-Net 3D/2D ensemble model is used to autosegment 20 H/N levels, with each LN subsequently being algorithmically assigned to the closest-level autosegmentation. In the nonrigid-registration-based mapping method, LNs are mapped into a calculated template CT representing the cohort-average patient anatomy, and kernel density estimation is employed to estimate the underlying average 3D-LN probability distribution allowing for analysis and visualization without prespecified level definitions. Multireader assessment by three radio-oncologists with majority voting was used to evaluate the deep learning method and obtain the ground-truth distribution. For the mapping technique, the proportion of LNs predicted by the 3D probability distribution for each level was calculated and compared to the deep learning and ground-truth distributions. As determined by a multireader review with majority voting, the deep learning method correctly categorized all 449 LNs to their respective levels. Level 2 showed the highest LN involvement (59.0%). The level involvement predicted by the mapping technique was consistent with the ground-truth distribution (p for difference 0.915). Application of the proposed methods to multicenter cohorts with selected H/N tumor subtypes for informing optimal RT target volume design is promising.<br
Keywords: deep learning; artificial intelligence; nodal metastasis; head and neck cancer; radiotherapy; target volume design; atlas; mapping; autosegmentation; lymph node level classification

Deep Learning-assisted delineation of brain metastases: a workflow focusing on AI-expert interaction - Putz, Florian; Szkitsak, Juliane; Grigo, Johanna; Masitho, Siti; Weissmann, Thomas; Frey, Benjamin; Gaipl, Udo; Fietkau, Rainer; Bert, Christoph; Huang, Yixing (Radiotherapy and Oncology, 2023)

Deep Learning-based Auto-contouring of Lymph Node Levels in Head and Neck Area - Weissmann, Thomas; Huang, Yixing; Sommer, Phillip; Roesch, Johannes; Mansoorian, Sina; Ayala, H.; Fischer, Stefan; Srinivasan, Aishwarya Lakshmi; Haderlein, Marlen; Hecht, Markus; Speer, Stefan; Schweizer, Claudia; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Deep Learning-based automatic longitudinal volumetric Analysis in Acoustic Neuroma - Putz, Florian; Chen, Hui-Fen; Huang, Yixing; Weissmann, Thomas; Mansoorian, Sina; Schmidt, M.; Semrau, Sabine; Lettmaier, Sebastian; Bert, Christoph; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Deep Learning based fully automated volumetric Progression Assessment in Patients with Brain Metastases after stereotactic Radiotherapy - Putz, Florian; Huang, Yixing; Weissmann, Thomas; Mansoorian, Sina; Sommer, P.; Fischer, S.; Srinivasan, A.; Frey, Benjamin; Gaipl, Udo; Schmidt, M.; Semrau, Sabine; Bert, Christoph; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Deep Learning based Prediction of Glioma Growth by using "Growing Neural Cellular Automata" - Huang, Yixing; Maier, Andreas; Sommer, Philipp; Fischer, Stefan; Srinivasan, Aishwarya Lakshmi; Fietkau, Rainer; Bert, Christoph; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Deep Learning basierte Vorhersage von Gliomwachstum mittels Growing Neural Cellular Automata - Huang, Yixing; Maier, Andreas; Sommer, Phillip; Fischer, Stefan; Srinivasan, Aishwarya Lakshmi; Fietkau, Rainer; Bert, Christoph; Putz, Florian (Strahlentherapie und Onkologie, 2022)
Keywords: deep learning; cellular automata; tumor growth

Deep learning for automatic head and neck lymph node level delineation provides expert-level accuracy - Weissmann, Thomas; Huang, Yixing; Fischer, Stefan; Roesch, Johannes; Mansoorian, Sina; Gaona, Horacio Ayala; Gostian, Antoniu-Oreste; Hecht, Markus; Lettmaier, Sebastian; Deloch, Lisa; Frey, Benjamin; Gaipl, Udo; et al. (Frontiers in Oncology, 2023)
Background: Deep learning-based head and neck lymph node level (HN_LNL) autodelineation is of high relevance to radiotherapy research and clinical treatment planning but still underinvestigated in academic literature. In particular, there is no publicly available open-source solution for large-scale autosegmentation of HN_LNL in the research setting. Methods: An expert-delineated cohort of 35 planning CTs was used for training of an nnU-net 3D-fullres/2D-ensemble model for autosegmentation of 20 different HN_LNL. A second cohort acquired at the same institution later in time served as the test set (n = 20). In a completely blinded evaluation, 3 clinical experts rated the quality of deep learning autosegmentations in a head-to-head comparison with expert-created contours. For a subgroup of 10 cases, intraobserver variability was compared to the average deep learning autosegmentation accuracy on the original and recontoured set of expert segmentations. A postprocessing step to adjust craniocaudal boundaries of level autosegmentations to the CT slice plane was introduced and the effect of autocontour consistency with CT slice plane orientation on geometric accuracy and expert rating was investigated. Results: Blinded expert ratings for deep learning segmentations and expert-created contours were not significantly different. Deep learning segmentations with slice plane adjustment were rated numerically higher (mean, 81.0 vs. 79.6, p = 0.185) and deep learning segmentations without slice plane adjustment were rated numerically lower (77.2 vs. 79.6, p = 0.167) than manually drawn contours. In a head-to-head comparison, deep learning segmentations with CT slice plane adjustment were rated significantly better than deep learning contours without slice plane adjustment (81.0 vs. 77.2, p = 0.004). Geometric accuracy of deep learning segmentations was not different from intraobserver variability (mean Dice per level, 0.76 vs. 0.77, p = 0.307). Clinical significance of contour consistency with CT slice plane orientation was not represented by geometric accuracy metrics (volumetric Dice, 0.78 vs. 0.78, p = 0.703). Conclusions: We show that a nnU-net 3D-fullres/2D-ensemble model can be used for highly accurate autodelineation of HN_LNL using only a limited training dataset that is ideally suited for large-scale standardized autodelineation of HN_LNL in the research setting. Geometric accuracy metrics are only an imperfect surrogate for blinded expert rating. <
Keywords: Deep learning; lymph node level; segmentation

Deep learning for brain metastasis detection and segmentation in longitudinal MRI data - Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Dörfler, Arnd; Maier, Andreas; Fietkau, Rainer; et al. (Medical Physics, 2022)
Keywords: Deep learning; brain metastasis; MRI; loss function; sensitivity specificity

Deep Learning for Cancer Prognosis Prediction Using Portrait Photos by StyleGAN Embedding - Hagag, Amr; Gomaa, Ahmed; Kornek, Dominik; Maier, Andreas; Fietkau, Rainer; Bert, Christoph; Huang, Yixing; Putz, Florian (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2024)
Survival prediction for cancer patients is critical for optimal treatment selection and patient management. Current patient survival prediction methods typically extract survival information from patients’ clinical record data or biological and imaging data. In practice, experienced clinicians can have a preliminary assessment of patients’ health status based on patients’ observable physical appearances, which are mainly facial features. However, such assessment is highly subjective. In this work, the efficacy of objectively capturing and using prognostic information contained in conventional portrait photographs using deep learning for survival prediction purposes is investigated for the first time. A pre-trained StyleGAN2 model is fine-tuned on a custom dataset of our cancer patients’ photos to empower its generator with generative ability suitable for patients’ photos. The StyleGAN2 is then used to embed the photographs to its highly expressive latent space. Utilizing state-of-the-art survival analysis models and StyleGAN’s latent space embeddings, this approach predicts the overall survival for single as well as pan-cancer, achieving a C-index of 0.680 in a pan-cancer analysis, showcasing the prognostic value embedded in simple 2D facial images. In addition, thanks to StyleGAN’s interpretable latent space, our survival prediction model can be validated for relying on essential facial features, eliminating any biases from extraneous information like clothing or background. Moreover, our approach provides a novel health attribute obtained from StyleGAN’s extracted features, allowing the modification of face photographs to either a healthier or more severe illness appearance, which has significant prognostic value for patient care and societal perception, underscoring its potential important clinical value.
CRIS-Team Scopus Importer:2024-10-25
Keywords: cancer; deep learning; explainable AI; face prognosis; latent space; StyleGAN; Survival prediction

Deep learning for perspective deformation correction in X-ray imaging - Huang, Yixing; Maier, Andreas; Fan, Fuxin; Kreher, Björn W.; Huang, Xiaolin; Fietkau, Rainer; Bert, Christoph; Putz, Florian (Radiotherapy and Oncology, 2023)
Keywords: Deep learning; perspective deformation; X-ray imaging

DEGRO practical guidelines for radiotherapy of non-malignant disorders: Part I: physical principles, radiobiological mechanisms, and radiogenic risk - Reichl, Berthold; Block, Andreas; Schäfer, Ulrich; Bert, Christoph; Müller, Reinhold; Jung, Horst; Rödel, Franz (Strahlentherapie und Onkologie, 2015)
Synopsis of the introductory paragraph of the DEGRO consensus S2e-guideline recommendations for the radiotherapy of benign disorders, including physical principles, radiobiological mechanisms, and radiogenic risk.This work is based on the S2e-guideline recommendations published November 14, 2013. The basic principles of radiation physics and treatment delivery, evaluation of putative underlying radiobiological mechanisms, and the assessment of genetic and cancer risk following low-dose irradiation will be presented.Radiation therapy of benign diseases is performed according to similar physical principles as those governing treatment of malignant diseases in radiation oncology, using the same techniques and workflows. These methods comprise usage of orthovoltage X-ray units, gamma irradiation facilities, linear accelerators (LINACs), and brachytherapy. Experimental in vitro and in vivo models recently confirmed the clinically observed anti-inflammatory effect of low-dose X-irradiation, and implicated a multitude of radiobiological mechanisms. These include modulation of different immunological pathways, as well as the activities of endothelial cells, mono- and polymorphonuclear leukocytes, and macrophages. The use of effective dose for radiogenic risk assessment and the corresponding tumor incidence rate of 5.5%/Sv are currently controversially discussed. Some authors argue that the risk of radiation-induced cancers should be estimated on the basis of epidemiological data. However, such data are rarely available at present and associated with high variability.Current radiobiological studies clearly demonstrate a therapeutic effectiveness of radiation therapy used to treat benign diseases and implicate various molecular mechanisms. Radiogenic risks should be taken into account when applying radiation treatment for benign diseases.
EVALuna2:18282

Dense feature-based motion estimation in MV fluoroscopy during dynamic tumor tracking treatment: preliminary study on reduced aperture and partial occlusion handling - Serpa, Marco; Bert, Christoph (Physics in Medicine and Biology, 2020)
Quality assurance solutions to complement available motion compensation technologies are central for their safe routine implementation and success of treatment. This work presents a dense feature-based method for soft-tissue tumor motion estimation in megavoltage (MV) beam's-eye-view (BEV) projections for potential intra-treatment monitoring during dynamic tumor tracking (DTT). Dense sampling and matching principles were employed to track a gridded set of features landmarks (FLs) in MV-BEV projections and estimate tumor motion, capable to overcome reduced field aperture and partial occlusion challenges. The algorithm's performance was evaluated by retrospectively applying it to fluoroscopic sequences acquired at similar to 2 frames s(-1) (fps) for a dynamic phantom and two lung stereotactic body radiation therapy (SBRT) patients treated with DTT on the Vero SBRT system. First, a field-specific train image is initialized by sampling the tumor region at, S, pixel intervals on a grid using a representative frame from a stream of query frames. Sampled FLs are locally characterized in the form of descriptor vectors and geometric attributes representing the target. For motion tracking, subsequent query frames are likewise sampled, corresponding feature descriptors determined, and then patch-wise matched to the training set based on their descriptors and geometric relationships. FLs with high correspondence are pruned and used to estimate tumor displacement. In scenarios of partial occlusions, position is estimated from the set of correctly (visible) FLs on past observations. Reconstructed trajectories were benchmarked against ground-truth manual tracking using the root-mean-square (RMS) as a metric of positional accuracy. A total of 19 fluoroscopy sequences were analyzed. This included scenarios of field aperture obstruction during three-dimensional conformal, as well as step-and-shoot intensity modulated radiotherapy (IMRT) delivery assisted with DTT. The algorithm resolved target motion satisfactorily. The RMS was <1.2 mm and <1.8 mm for the phantom and the clinical dataset, respectively. Dense tracking showed promising results to overcome localization challenges at the field penumbra and partial obstruction by multi-leaf collimator (MLC). Motion retrieval was possible in similar to 66% of the control points studied. In addition to MLC obstruction, changes in the external/internal breathing dynamics and baseline drifts were a major source of estimation bias. Dense feature-based tracking is a viable alternative. The algorithm is rotation-/scale-invariant and robust to photometric changes. Tracking multiple features may help overcome partial occlusion challenges by the MLC. This in turn opens up new possibilities for motion detection and intra-treatment monitoring during IMRT and potentially VMAT.
CRIS-Team WoS Importer:2021-01-15

Development and clinical implementation of a digital system for risk assessments for radiation therapy - Kornek, Dominik; Menichelli, David; Leske, Jörg; Hofmann, Michael; Antkiewicz, David; Brandt, Tobias; Ott, Oliver; Lotter, Michael; Lang-Welzenbach, Marga; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2023)
Before introducing new treatment techniques, an investigation of hazards due to unintentional radiation exposures is a reasonable activity for proactively increasing patient safety. As dedicated software is scarce, we developed a tool for risk assessment to design a quality management program based on best practice methods, i.e., process mapping, failure modes and effects analysis and fault tree analysis. Implemented as a web database application, a single dataset was used to describe the treatment process and its failure modes. The design of the system and dataset allowed failure modes to be represented both visually as fault trees and in a tabular form. Following the commissioning of the software for our department, previously conducted risk assessments were migrated to the new system after being fully re-assessed which revealed a shift in risk priorities. Furthermore, a weighting factor was investigated to bring risk levels of the migrated assessments into perspective. The compensation did not affect high priorities but did re-prioritize in the midrange of the ranking. We conclude that the tool is suitable to conduct multiple risk assessments and concomitantly keep track of the overall quality management activities.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Failure modes and effects analysis (FMEA); Fault tree analysis (FTA); Process throughput; Radiation therapy; Risk analysis; Risk-based quality management

Differences in Dose Coverage and Uniformity in Fractionated High-Dose-Rate Interstitial Breast Brachytherapy Based on EMT Measurements - Kellermeier, Markus; Hofmann, B.; Strnad, Vratislav; Bert, Christoph (2016)
EVALuna2:33047

Distinguishing Progression and Radionecrosis in large progressive Brain Metastases after Stereotaxy by integrating Radiomics, Dose Radiomics and clinical Risk Factors - Sommer, Phillip; Huang, Yixing; Srinivasan, Aishwarya Lakshmi; Fischer, Stefan; Dörfler, Arnd; Schmidt, Manuel; Frey, Benjamin; Maier, Andreas; Fietkau, Rainer; Bert, Christoph; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Does a dedicated Radiation Planning MRI add Value to cranial Stereotaxy? - Mengling, Veit; Putz, Florian; Perrin, R.; Fietkau, Rainer; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Does the Planning MRI for cranial Stereotaxy have to be performed in the Irradiation Position? An Examination of Brain Tissue Deformations between MR Imaging in diagnostic and Radiation Positions - Putz, Florian; Mengling, Veit; Masitho, Siti; Perrin, R.; Roesch, Johannes; Weissmann, T.; Bäuerle, Tobias; Fietkau, Rainer; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Dose calculation and verification of the Vero gimbal tracking treatment delivery - Prasetio, Heru; Wölfelschneider, Jens; Ziegler, Marc; Serpa, M.; Witulla, Barbara; Bert, Christoph (Physics in Medicine and Biology, 2018)
The Vero linear accelerator delivers dynamic tumor tracking (DTT) treatment using a gimbal motion. However, the availability of treatment planning systems (TPS) to simulate DTT is limited. This study aims to implement and verify the gimbal tracking beam geometry in the dose calculation. Gimbal tracking was implemented by rotating the reference CT outside the TPS according to the ring, gantry, and gimbal tracking position obtained from the tracking log file. The dose was calculated using these rotated CTs. The geometric accuracy was verified by comparing calculated and measured film response using a ball bearing phantom. The dose was verified by comparing calculated 2D dose distributions and film measurements in a ball bearing and a homogeneous phantom using a gamma criterion of 2%/2 mm. The effect of implementing the gimbal tracking beam geometry in a 3D patient data dose calculation was evaluated using dose volume histograms (DVH). Geometrically, the gimbal tracking implementation accuracy was <0.94 mm. The isodose lines agreed with the film measurement. The largest dose difference of 9.4% was observed at maximum tilt positions with an isocenter and target separation of 17.51 mm. Dosimetrically, gamma passing rates were >98.4%. The introduction of the gimbal tracking beam geometry in the dose calculation shifted the DVH curves by 0.05%-1.26% for the phantom geometry and by 5.59% for the patient CT dataset. This study successfully demonstrates a method to incorporate the gimbal tracking beam geometry into dose calculations. By combining CT rotation and MU distribution according to the log file, the TPS was able to simulate the Vero tracking treatment dose delivery. The DVH analysis from the gimbal tracking dose calculation revealed changes in the dose distribution during gimbal DTT that are not visible with static dose calculations.
EVALuna2:33026

Dosimetric evaluation of 6-DOF intra-fraction motion for SGRT of breast cancer patients - Sauer, Tim-Oliver; Ott, O.; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-07-08

Dosimetry, Optimization and FMEA of Total Skin Electron Irradiation (TSEI) - Shariff, Maya; Stillkrieg, Willi; Lotter, Michael; Lohmann, Daniel; Weissmann, Thomas; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2022)
Purpose: Total Skin Electron Irradiation (TSEI) is a method for treating malignant cutaneous T-cell lymphomas. This work aims to implement and optimize the total skin technique established at Strahlenklinik Erlangen, Germany on two new linear accelerators and to quantify the risks using failure mode and effects (FMEA) analysis. Material and methods: TSEI is performed at a VersaHD accelerator (Elekta, Stockholm) with 6 MeV in the “high dose rate mode” HDRE and a nominal field size of 40 × 40 cm2. To reach the entire skin surface, the patients perform 6 different body positions at a distance of 330 cm behind an acrylic scatter plate, with two overlapping irradiation fields being radiated at 2 gantry angles per position. The irradiation technique was commissioned according to the recommendation of AAPM report 23. With the help of a reference profile at 270°, 2 gantry angles were calculated, which in total resulted in an optimal dose distribution. This was metrologically verified with ion-chamber measurements in the patient's longitudinal axis. The influence of the shape of the acrylic scatter plate and the distance between the acrylic scatter plate and patient was determined by measurements. The dose homogeneity was verified using an anthropomorphic disc phantom equipped with GafChromic films. The workflows and failure modes of the total skin technique were described in a process map and subsequently quantified with a FMEA analysis. Results: An optimal dose distribution is achieved at a distance of SSD = 330 cm, using the gantry angles 289° and 251°. The previously used segmented acrylic scatter plate was replaced by a flat plate (200 × 120 × 0.5 cm3), which is placed at a distance of 50 cm in front of the patient. The densitometric evaluation of the GafChromic films in the anthropomorphic disc phantom revealed an expected dose distribution of 3 Gy at a depth of up to 1.5 cm below the skin surface, with a homogeneity of ±10% over the phantom's longitudinal axis. By FMEA a maximum risk priority number of 30 was determined. Conclusion: Based on the calculations and measurements performed on the new accelerators as well as the risk analysis, we concluded that total skin therapy can be implemented clinically.
CRIS-Team Scopus Importer:2022-06-17
Keywords: Dosimetry; FMEA; HDRE; Mycosis fungoides; Quality assurance; Total Skin Electron Irradiation (TSEI)

ECG-based 4D-dose reconstruction of cardiac arrhythmia ablation with carbon ion beams: application in a porcine model - Richter, Daniel; Lehmann, H. Immo; Eichhorn, Anna; Constantinescu, Anna M.; Kaderka, Robert; Prall, Matthias; Lugenbiel, Patrick; Takami, Mitsuru; Thomas, Dierk; Bert, Christoph; Durante, Marco; Packer, Douglas L.; et al. (Physics in Medicine and Biology, 2017)
Noninvasive ablation of cardiac arrhythmia by scanned particle radiotherapy is highly promising, but especially challenging due to cardiac and respiratory motion. Irradiations for catheter-free ablation in intact pigs were carried out at the GSI Helmholtz Center in Darmstadt using scanned carbon ions. Here, we present real-time electrocardiogram (ECG) data to estimate time-resolved (4D) delivered dose. For 11 animals, surface ECGs and temporal structure of beam delivery were acquired during irradiation. R waves were automatically detected from surface ECGs. Pre-treatment ECG-triggered 4D-CT phases were synchronized to the R-R interval. 4D-dose calculation was performed using GSI's in-house 4D treatment planning system. Resulting dose distributions were assessed with respect to coverage (D95 and V95), heterogeneity (HI = D5-D95) and normal tissue exposure. Final results shown here were performed offline, but first calculations were started shortly after irradiation The D95 for TV and PTV was above 95% for 10 and 8 out of 11 animals, respectively. HI was reduced for PTV versus TV volumes, especially for some of the animals targeted at the atrioventricular junction, indicating residual interplay effects due to cardiac motion. Risk structure exposure was comparable to static and 4D treatment planning simulations. ECG-based 4D-dose reconstruction is technically feasible in a patient treatment-like setting. Further development of the presented approach, such as real-time dose calculation, may contribute to safe, successful treatments using scanned ion beams for cardiac arrhythmia ablation.
EVALuna2:36481

Education, training and registration of Medical Physics Experts across Europe - Maas, Ad J.J.; Lammertsma, Adriaan A.; Agius, Sam; Bert, Christoph; Byrne, Brenda; Caruana, Carmel J.; Gilligan, Paddy; Koutsouveli, Efi; Pace, Eric; Brambilla, Marco (Physica Medica, 2021)
From its inception, EFOMP has pursued a policy to improve and coordinate education and training of medical physicists across all its participating European countries. Several EFOMP policy statements on education and training have been published and surveys have been held to get an overview of the actual situation. At the beginning of 2020 a new survey was distributed amongst the 36 National Member Organizations (NMOs), in which questions were based on recommendations published in the most recent policy statements. Thirty-three of the NMOs (91%) responded, of which 22 indicated having a National Registration Scheme (NRS) for Medical Physics Experts (MPEs) in place. Another 6 indicated considering such a scheme. Results of the questionnaire showed that there was good correspondence between education and training programmes, i.e. a division between a BSc phase, an MSc phase and a clinical phase after completion of the MSc. Differences between NRSs were primarily seen in the availability and composition of a supervising committee and in the availability of guidelines for handling professional misconduct. In addition, some differences were seen in the topics that were part of the education and training programme. The goal of a universal (registered) MPE accepted by all European countries is still far away despite the progress being made. The new procedure for approving an existing NRS, which fulfils all EFOMP criteria is seen as an important step forward. Exchange of experience, knowledge, ideas and, above all, MPE trainees between European countries is seen as the best approach to achieve this goal.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Education and training; European Federation of Organizations for Medical Physics; Medical Physics Expert; National registration scheme; Professional misconduct; Supervising committee

Electromagnetic tracking for integrated quality assurance in breast interstitial brachytherapy: The impact of registration method - Sauer, Birte; Dürrbeck, Christopher; Bert, Christoph (Journal of Contemporary Brachytherapy, 2024)
Purpose: Electromagnetic tracking (EMT) has great potential as a quality assurance tool in interstitial brachytherapy. Since its clinical application in most cases comprises a comparison with brachytherapy plan data, EMT registration and plan data are crucial. Registration uncertainties influence EMT outcomes and further decision-making processes. The impact of registration using four algorithms on the resulting data was investigated. Material and methods: Registration abilities of four sub-algorithms, which share the same principle of an iterative closest point approach were considered. Sub-algorithms differ regarding underlying mathematical norms, and also include a non-geometric implementation focusing on stochastic optimization. This study focused on the registration of point clouds originating from data obtained during treatment with interstitial brachytherapy in breast cancer patients. Data were acquired from a hybrid device prototype, capable of EMT measurements and data extracted from treatment plan. Main criteria for good registration performance were good geometric agreement, including low Euclidean distances between registered data sets as well as short registration time. In addition, previously published patient data with different than employed in the original publication algorithm were re-analyzed to further investigate the impact of registration method on clinically influential results. Results: The stochastic algorithm presented much higher registration times, and earliest implementation of geometric approaches occasionally misaligned patient data. The remaining two algorithms performed almost identically resulted in sufficiently accurate registration performance. The re-analysis of previously published data demonstrated minor inconsistencies between former registration method and different algorithm; however, the overall trends with almost identical mean Euclidean distance of 2.22 mm (2.19 mm in the original work) could be reproduced. Conclusions: The choice of registration algorithm can influence the quality of registration. Therefore, it is advised to regularly examine the registration performance, especially in in-house programs.
CRIS-Team Scopus Importer:2024-10-25
Keywords: electromagnetic measurement; image registration; performance optimization

Electromagnetic tracking for treatment verification in interstitial brachytherapy - Bert, Christoph; Kellermeier, Markus; Tanderup, Kari (Journal of Contemporary Brachytherapy, 2016)
Electromagnetic tracking (EMT) is used in several medical fields to determine the position and orientation of dedicated sensors, e.g., attached to surgical tools. Recently, EMT has been introduced to brachytherapy for implant reconstruction and error detection. The manuscript briefly summarizes the main issues of EMT and error detection in brachytherapy. The potential and complementarity of EMT as treatment verification technology will be discussed in relation toin vivodosimetry and imaging.
EVALuna2:33051

Electromagnetic tracking in interstitial brachytherapy: A systematic review - Sauer, Birte; Dürrbeck, Christopher; Bert, Christoph (Frontiers in Physics, 2022)
Brachytherapy is a well-established treatment option for different cancer types. One treatment option, namely temporary afterloading brachytherapy, utilizes an encapsulated radioactive source, which is guided through implanted applicators to pre-defined dwell positions, to deliver highly conformal and concentrated doses to the target volume. However, treatment errors and uncertainties might still occur. The treatment therefore requires a stringent verification on an individual patient level, particularly in the form of applicator reconstruction. Electromagnetic tracking (EMT) is a possible verification option whose application neither relies on direct line of sight nor does it increase the radiation exposure. However, its systematic clinical application is not yet realized. This review will separate the concept of treatment verification through the use of electromagnetic tracking into four focus groups and categorize the relevant papers within said groups. The four focus groups are geometric assessment, applicator reconstruction, patient-individual quality assurance and adaptive treatment planning. The reviewed papers can be mainly sorted into the focus groups of geometric assessment and applicator reconstruction underlining the potential of EMT as an asset for reconstruction and localization. A smaller group of papers can be associated with patient-individual quality assurance where the detection of implant variations such as swaps within the connector cohort or single catheter shifts take center stage. The final focus group, adaptive treatment planning, is sparsely represented, yet the feasibility of an adaptive treatment course can be derived. This review will close with a discussion of possible improvements and illustrate the path ahead to clinical implementation.
CRIS-Team WoS Importer:2022-10-14

End-to-end testing for stereotactic radiotherapy including the development of a MULTI-MODALITY phantom - Shariff, Maya; Grigo, Johanna; Masitho, Siti; Brandt, Tobias; Weiß, Alexander; Lambrecht, Ulrike; Stillkrieg, Willi; Lotter, Michael; Putz, Florian; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2024)
Purpose: A new insert for a commercially available end-to-end test phantom was designed and in-house manufactured by 3D printing. Subsequently, the insert was tested for different stereotactic radiation therapy workflows (SRS, SBRT, FSRT, and Multimet) also in comparison to the original insert. Material and methods: Workflows contained imaging (MR, CT), treatment planning, positioning, and irradiation. Positioning accuracy was evaluated for non-coplanar x-ray, kV- and MV-CBCT systems, as well as surface guided radiation therapy. Dosimetric accuracy of the irradiation was measured with an ionization chamber at four different linear accelerators including dynamic tumor tracking for SBRT. Results: CT parameters of the insert were within the specification. For MR images, the new insert allowed quantitative analysis of the MR distortion. Positioning accuracy of the phantom with the new insert using the imaging systems of the different linacs was < 1 mm/degree also for MV-CBCT and a non-coplanar imaging system which caused > 3 mm deviation with the original insert. Deviation of point dose values was < 3% for SRS, FSRT, and SBRT for both inserts. For the Multimet plans deviations exceeded 10% because the ionization chamber was not positioned in each metastasis, but in the center of phantom and treatment plan. Conclusion: The in-house manufactured insert performed well in all steps of four stereotactic treatment end-to-end tests. Advantages over the commercially available alternative were seen for quantitative analysis of deformation correction in MR images, applicability for non-coplanar x-ray imaging, and dynamic tumor tracking.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Dynamic Tumor Tracking; End-to-End testing; MRI distortion; Quality Assurance; SBRT; SRS

Error detection using an electromagnetic tracking system in multi-catheter breast interstitial brachytherapy - Masitho, Siti; Kallis, Karoline; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Physics in Medicine and Biology, 2019)
The hybrid treatment delivery system (HTDS) has been proposed as a possible option for a quality assurance in the multi-catheter interstitial brachytherapy for breast cancer patients. The system, which consists out of a prototype afterloader with an integrated electromagnetic tracking (EMT) sensor and an EMT system, allows the automatic measurement of implanted catheters. To test the feasibility of the system for error detection, possible treatment planning errors and treatment delivery errors were simulated. Planning errors such as an incorrect offset value, an incorrect indexer length, tip/connector end swaps, and partial swaps, and; treatment delivery errors such as catheter shifts and catheter connection swaps were manually simulated using phantoms. An in-house Matlab routine was used to assess geometrical deviations between the dwell positions defined based on CT and EMT measurement. Additionally, the influence of implant motion on the detection ability of the system was assessed. An algorithm for the detection and specification of errors based on the error simulation results was developed. At the University Hospital Erlangen, a patient study is ongoing, where errors in patient data were analyzed using the proposed algorithm. All simulated planning errors were detected. Catheter connection swaps can be detected 100% of the time. A shift detection rate of >97% was observed for shifts larger than 1.1 mm, both in the static and the motion measurements. Catheter reconstruction uncertainties and catheter shifts <2 mm were found to be the most common treatment planning and delivery errors in patient data. HTDS proved to be a reliable method for error detection.
CRIS-Team Scopus Importer:2019-10-29

Error detection using an electromagnetic tracking system in multicatheter interstitial brachytherapy - Masitho, S.; Kallis, Karoline; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Establishing an intraoperative, mobile CBCT-based workflow for gynecologic brachytherapy: primary experience and benefit assessment - Karius, Andre; Strnad, Vratislav; Bert, Christoph; Fietkau, Rainer; Merten, Ricarda; Schweizer, Claudia (Frontiers in Oncology, 2025)
Background and purpose: In the brachytherapy of cervical cancer, creating a suitable implant based on ultrasound guidance may be impacted by imaging limitations. To validate the implant if ultrasound is not sufficient, we implemented a new workflow utilizing additional intraoperative cone-beam computed tomography (CBCT). The aims of this work were to describe the newly established workflow, reflect associated (dis)advantages, and assess geometric and dosimetric benefits compared to the previous solely ultrasound-guided workflow. Materials and methods: We report the establishment of our new workflow utilizing mobile CBCT during interventions and corresponding experiences for 26 consecutive patients. Image quality was assessed by considering the applicator visualization and contrast–noise ratio (CNR) between tissues. Implant changes based on CBCT scans were analyzed with respect to the enhanced insertion depths (EIDs) of needles and their tip distances to target volume borders. Dosimetric effects were evaluated by calculating common dose–volume parameters for target volume and organs at risk (OARs) and comparing them in both a previous patient cohort and scenarios simulating sole ultrasound guidance. Implant uncertainties between intra- and postoperative imaging were analyzed using a corresponding registration as well. Results: Implementing intraoperative CBCT was associated with clinical challenges but increased safety feeling during interventions and resulted in geometric as well as dosimetric benefits. Needles could be shifted deeper into the pelvis by an EID of 14 ± 11 mm based on CBCT, associated with corresponding significant dose improvements for target volume and OARs with a mean tradeoff increase of up to 4.8 Gy. With a reasonable CNR between tissues up to 8.5 ± 3.6 and clear detectability of applicators, image quality was sufficient to fulfill intraoperative intentions. Furthermore, the CBCT scans were suitable for treatment planning purposes from a geometric uncertainty perspective. Conclusion: The implementation of intraoperative CBCT can substantially improve the quality and safety of image-guided gynecologic brachytherapy.
CRIS-Team Scopus Importer:2025-05-09
Keywords: adaptive brachytherapy; image-guidance; interventional radiotherapy; intraoperative imaging; mobile CT

Estimating follow-up CTs from geometric deformations of catheter implants in interstitial breast brachytherapy: A feasibility study using electromagnetic tracking - Dürrbeck, Christopher; Schulz, Moritz; Pflaum, Leonie; Kallis, Karoline; Geimer, Tobias; Abu-Hossin, Nadin; Strnad, Vratislav; Maier, Andreas; Fietkau, Rainer; Bert, Christoph (Medical Physics, 2023)
Background: Electromagnetic tracking (EMT) systems have been shown to provide valuable information on the geometry of catheter implants in breast cancer patients undergoing interstitial brachytherapy (iBT). In the context of an extended patient-specific, pre-treatment verification, EMT can play a key role in determining the potential need and, if applicable, the appropriate time for treatment adaptation. To detect dosimetric shortcomings the relative position between catheters, and target volume and critical structures must be known. Since EMT cannot provide the anatomical context and standard imaging techniques such as cone-beam CT are not yet available in most brachytherapy suites, it is not possible to detect anatomic changes on a daily or fraction basis, so the need for adaptive planning cannot be identified. Purpose: The aim of this feasibility study is to develop and evaluate a technique capable of estimating follow-up CTs at any time based on the initial treatment planning CT (PCT) and surrogate information about changes of the implant geometry from an EMT system. Methods: A deformation vector field is calculated from two different implant reconstructions acquired in treatment position through EMT, the first immediately after the PCT and the second at another time point during the course of treatment. The calculation is based on discrete displacement vectors of pairs of control and target points. These are extrapolated by means of different radial basis functions in order to cover the entire CT volume. The adequate parameters for the calculation of the deformation field were identified. By warping the PCT according to the deformation field, one obtains an estimated CT (ECT) that reflects the geometric changes. For the proof of concept, ECTs were computed for the time point of the clinical follow-up CT (FCT) that is embedded in the treatment workflow after the fourth fraction. Results: ECT and clinical FCTs of 20 patients were compared to each other quantitatively in terms of absolute Hounsfield unit differences in the planning target volume (PTV) and in a convex hull (CH) enclosing the catheters. The median differences were 31.2 and 29.5 HU for the CH and the PTV, respectively. Conclusion: The proposed ECT approach was able to approximate the “anatomy of the day” and therefore, in principle, allows a dosimetric appraisal of the treatment plan quality before each fraction. In this way, it can contribute to a more detailed patient-specific quality assurance in iBT of the breast and help to identify the timing for a potential treatment adaptation.
CRIS-Team Scopus Importer:2023-08-25
Keywords: assurance; breast cancer; electromagnetic tracking; interstitial brachytherapy

Estimation of inter-fractional variations in interstitial multi-catheter breast brachytherapy using a hybrid treatment delivery system - Kallis, Karoline; Abu-Hossin, Nadin; Kreppner, Stephan; Lotter, Michael; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2019)
Purpose: Irradiation of the tumor bed using interstitial multi-catheter brachytherapy is one of the treatment options for breast cancer patients. In order to ensure the planned dose delivery an advanced quality intervention method using an electromagnetic tracking (EMT) system is presented. The system is used to assess inter-fractional variations within the framework of a patient study. Methods and materials: Until now 41 patients were included in the study for the evaluation and overall 355 EMT measurements were performed. The catheter traces are measured automatically and sequentially using an afterloader prototype (Flexitron, Elekta, Veenendaal, The Netherlands) equipped with an EMT sensor. The implant geometry is tracked directly after implantation, after CT imaging and after each irradiation fraction. The acquired data is rigidly registered to the catheter traces defined in the treatment plan and the dwell positions (DP) are reconstructed. DPs defined in treatment planning serve as reference. Breathing motion was corrected and recorded using three reference 6DoF sensors placed on the patients’ skin. The Euclidean distance between the planned and reconstructed DPs provides information about possible inter-fractional deviations. Further, the influence of various factors on the occurrence of large deviations was investigated, like the patients’ age, the length of the catheter, the breast volume, etc. Results: Over all patient measurements a median Euclidean distance of 2.19 mm was determined between the reconstructed DPs and the reference DPs. The median deviation combining all datasets was minimal (1.67 mm) at the measurement directly after CT imaging. The deviations between the different fractions have a median distance of 2.31 mm which could be improved to 2.05 mm by adapting the treatment plan according to the follow-up CT. No correlation between the distance to the skin, ribs, mammilla or the breast volume and the occurrences of large deviations was found. The largest deviations were determined in the upper inner quadrant of the breast. Conclusion: The afterloader prototype could be well integrated into the clinical routine and is beneficial for ensuring the quality of the brachytherapy. Overall, a small median DP deviation, lower than the used step size of 2.5 mm, was detected.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Breast cancer; Electromagnetic tracking; Inter-fractional variations; Interstitial multi-catheter brachytherapy

ESTRO-ACROP guideline on surface guided radiation therapy - Freislederer, P.; Batista, V.; Ollers, M.; Buschmann, Martin; Steiner, E.; Kugele, M.; Fracchiolla, F.; Corradini, S.; De Smet, M.; Moura, F.; Perryck, S.; Dionisi, F.; et al. (Radiotherapy and Oncology, 2022)
Surface guidance systems enable patient positioning and motion monitoring without using ionising radiation. Surface Guided Radiation Therapy (SGRT) has therefore been widely adopted in radiation therapy in recent years, but guidelines on workflows and specific quality assurance (QA) are lacking. This ESTROACROP guideline aims to give recommendations concerning SGRT roles and responsibilities and highlights common challenges and potential errors. Comprehensive guidelines for procurement, acceptance, commissioning, and QA of SGRT systems installed on computed tomography (CT) simulators, C-arm linacs, closed-bore linacs, and particle therapy treatment systems are presented that will help move to a consensus among SGRT users and facilitate a safe and efficient implementation and clinical application of SGRT. (c) 2022 The Author(s). Published by Elsevier B.V. Radiotherapy and Oncology xxx (2022) xxx-xxx This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).
CRIS-Team WoS Importer:2022-07-29

Evaluation of a dedicated Treatment Planning-MRI for Patients with cranial Stereotaxy - Grigo, Johanna; Masitho, Siti; Putz, Florian; Fietkau, Rainer; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Evaluation of a high-resolution 3D T2-SPACE-FLAIR Sequence in Comparison to the conventional 2D T2-FLAIR Sequence for the Contouring of low malignant Tumor Parts in cerebral Gliomas - Siavooshhaghighi, H.; Mengling, Veit; Masitho, Siti; Filimonova, Irina; Mansoorian, S.; Weissmann, T.; Bert, Christoph; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Evaluation of a markerless SGRT-only workflow for breast cancer patients - Sauer, Tim-Oliver; Popp, D.; Ott, O. J.; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-11-26

Evaluation of the influence of susceptibility-induced magnetic field distortions on the precision of contouring intracranial organs at risk for stereotactic radiosurgery - Mengling, Veit; Putz, Florian; Laun, Frederik Bernd; Perrin, Rosalind; Eisenhut, Felix; Dörfler, Arnd; Fietkau, Rainer; Bert, Christoph (Physics and Imaging in Radiation Oncology, 2020)
Background and purpose: Magnetic resonance imaging (MRI) is a crucial factor in optimal treatment planning for stereotactic radiosurgery. To further the awareness of possible errors in MRI, this work aimed to investigate the magnitude of susceptibility induced MRI distortions for intracranial organs at risk (OARs) and test the effectiveness of actively shimming these distortions. Materials and methods: Distortion maps for 45 exams of 42 patients (18 on a 1.5 T MRI scanner, 27 on a 3 T MRI scanner) were calculated based on a high-bandwidth double-echo gradient echo sequence. The investigated OARs were brainstem, chiasm, eyes, and optic nerves. The influence of active shimming was investigated by comparing unshimmed 1.5 T data with shimmed 3 T data and comparing the results to a model based prediction. Results: The median distortion for the different OARs was found to be between 0.13 and 0.18 mm for 1.5 T and between 0.11 and 0.13 mm for 3 T. The maximum distortion was found to be between 1.3 and 1.7 mm for 1.5 T and between 1.1 and 1.4 mm for 3 T. The variation of values was much higher for 1.5 T than for 3 T across all investigated OARs. Active shimming was found to reduce distortions by a factor of 2.3 to 2.9 compared to the expected values. Conclusions: Using a safety margin for OARs of 1 mm would have encompassed 99.8% of the distortions. Since distortions are inversely proportional to the readout bandwidth, they can be further reduced by increasing the bandwidth. Additional error sources like gradient nonlinearities need to be addressed separately.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Brain; MRI; PRV; Safety margins; Stereotactic; Susceptibility artifacts

Examination of a deformable motion model for respiratory movements and 4D dose calculations using different driving surrogates - Wölfelschneider, Jens; Seregni, Matteo; Fassi, Aurora; Ziegler, Marc; Baroni, Guido; Fietkau, Rainer; Riboldi, Marco; Bert, Christoph (Medical Physics, 2017)
PURPOSE: The aim of this study was to evaluate a surrogate-driven motion model based on four-dimensional computed tomography that is able to predict CT volumes corresponding to arbitrary respiratory phases. Furthermore, the comparison of three different driving surrogates is examined and the feasibility of using the model for 4D dose re-calculation will be discussed. METHODS: The study is based on repeated 4DCTs of twenty patients treated for bronchial carcinoma and metastasis. The motion model was estimated from the planning 4DCT through deformable image registration. To predict a certain phase of a follow-up 4DCT, the model considers inter-fractional variations (baseline correction) and intra-fractional respiratory parameters (amplitude and phase) derived from surrogates. The estimated volumes resulting from the model were compared to ground-truth clinical 4DCTs using absolute HU differences in the lung region and landmarks localized using the Scale Invariant Feature Transform. Finally, the γ-index was used to evaluate the dosimetric effects of the intensity differences measured between the estimated and the ground-truth CT volumes. RESULTS: The results show absolute HU differences between estimated and ground-truth images with median value (± standard deviation) of (61.3 ± 16.7) HU. Median 3D distances, measured on about 400 matching landmarks in each volume, were (2.9 ± 3.0) mm. 3D errors up to 28.2 mm were found for CT images with artifacts or reduced quality. Pass rates for all surrogate approaches were above 98.9% with a γ-criterion of 2%/2 mm. CONCLUSION: The results depend mainly on the image quality of the initial 4DCT and the deformable image registration. All investigated surrogates can be used to estimate follow-up 4DCT phases, however, uncertainties decrease for volumetric approaches. Application of the model for 4D dose calculations is feasible.
EVALuna2:32902

Examination of Gold Marker Detection in Tracking Treatments of Liver Cancer Patients using Vero SBRT System - Ziegler, Marc; Brandt, Tobias; Lettmaier, S.; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (2018)
EVALuna2:36476

Examination of the automatic fiducial marker detection on the Vero system - Ziegler, Marc; Brandt, Tobias; Lettmaier, S.; Fietkau, Rainer; Bert, Christoph (2018)
EVALuna2:36478

Experimental investigation of irregular motion impact on 4D PET-based particle therapy monitoring. - Tian, Y.; Stuetzer, K.; Enghardt, W.; Priegnitz, M.; Helmbrecht, S.; Bert, Christoph; Fiedler, F. (Physics in Medicine and Biology, 2016)
Particle therapy positron emission tomography (PT-PET) is an in vivo and non-invasive imaging technique to monitor treatment delivery in particle therapy. The inevitable patient respiratory motion during irradiation causes artefacts and inaccurate activity distribution in PET images. Four-dimensional (4D) maximum likelihood expectation maximisation (4D MLEM) allows for a compensation of these effects, but has up to now been restricted to regular motion for PT-PET investigations. However, intra-fractional motion during treatment might differ from that during acquisition of the 4D-planning CT (e.g. amplitude variation, baseline drift) and therefore might induce inaccurate 4D PET reconstruction results. This study investigates the impact of different irregular analytical one-dimensional (1D) motion patterns on PT-PET imaging by means of experiments with a radioactive source and irradiated moving phantoms. Three sorting methods, namely phase sorting, equal amplitude sorting and event-based amplitude sorting, were applied to manage the PET list-mode data. The influence of these sorting methods on the motion compensating algorithm has been analysed. The event-based amplitude sorting showed a superior performance and it is applicable for irregular motions with ?4 mm amplitude elongation and drift. For motion with 10 mm baseline drift, the normalised root mean square error was as high as 10.5% and a 10 mm range deviation was observed.
EVALuna2:18310

Exploring surface-guided systems for intelligent breathing-adapted four-dimensional computed tomography: A comparison to infrared-based reflective marker systems - Lackner, Niklas; Karius, Andre; Fietkau, Rainer; Bert, Christoph; Szkitsak, Juliane (Journal of Applied Clinical Medical Physics, 2025)
Purpose: This study evaluates the technical feasibility of adapting a surface monitoring system, designed for conventional four-dimensional computed tomography (4DCT), to an intelligent, breathing-adapted 4DCT and examines its potential to expand the currently limited range of supported surrogate systems. Methods: In an experimental phantom setting, we compared breathing curve quality and its impact on breathing-adapted 4DCT generation between a surface monitoring camera and our clinical infrared (IR) system, using a research-grade IR camera coupled with a radiation detector as an independent reference. Breathing curves from the surface monitoring system and the research-grade camera were corrected for table motion. We assessed the influence of differences in breathing curves on the automatic selection of parameters before scanning, intelligent X-ray triggering during acquisition, and the differences of binning point selection for reconstruction as well as image quality. Additionally, we simulated the impact of latency on image quality and measured the observed latencies between the surrogate systems relative to an X-ray measurement. Results: During table movement, discrepancies were found in breathing signals from the surface monitoring system compared to the clinical and reference systems. After correcting for table motion, the surface monitoring system's curves aligned consistently with those of the other systems with amplitude (AMP) variations of less than 10% and breathing rate (BR) variations of less than 1%. Corrected curves showed improved performance in their ability to generate breathing-adapted 4DCTs. The clinical IR system showed a 45 ms latency advantage over the surface monitoring system, impacting image quality as simulated. Conclusions: After correcting surface monitoring breathing curves, satisfactory agreement with the clinical and independent reference systems was achieved. With modifications, the surface monitor solution could serve as a suitable surrogate for breathing-adapted 4DCT. In our experimental setting, the surface monitoring system had a 45 ms delay relative to the clinical system, potentially affecting image quality.
CRIS-Team Scopus Importer:2025-03-07
Keywords: 4DCT; respiratory motion; surrogate system; technical feasibility study

External-Beam-Accelerated Partial-Breast Irradiation Reduces Organ-at-Risk Doses Compared to Whole-Breast Irradiation after Breast-Conserving Surgery - Ott, Oliver; Stillkrieg, Willy; Lambrecht, Ulrike; Schweizer, Claudia; Lamrani, Allison; Sauer, Tim-Oliver; Strnad, Vratislav; Bert, Christoph; Hack, Carolin; Beckmann, Matthias; Fietkau, Rainer (Cancers, 2023)
In order to evaluate organ-at-risk (OAR) doses in external-beam-accelerated partial-breast irradiation (APBI) compared to standard whole-breast irradiation (WBI) after breast-conserving surgery. Between 2011 and 2021, 170 patients with early breast cancer received APBI within a prospective institutional single-arm trial. The prescribed dose to the planning treatment volume was 38 Gy in 10 fractions on 10 consecutive working days. OAR doses for the contralateral breast, the ipsilateral, contralateral, and whole lung, the whole heart, left ventricle (LV), and the left anterior descending coronary artery (LAD), and for the spinal cord and the skin were assessed and compared to a control group with real-world data from 116 patients who underwent WBI. The trial was registered at the German Clinical Trials Registry, DRKS-ID: DRKS00004417. Compared to WBI, APBI led to reduced OAR doses for the contralateral breast (0.4 ± 0.6 vs. 0.8 ± 0.9 Gy, p = 0.000), the ipsilateral (4.3 ± 1.4 vs. 9.2 ± 2.5 Gy, p = 0.000) and whole mean lung dose (2.5 ± 0.8 vs. 4.9 ± 1.5 Gy, p = 0.000), the mean heart dose (1.6 ± 1.6 vs. 1.7 ± 1.4 Gy, p = 0.007), the LV V23 (0.1 ± 0.4 vs. 1.4 ± 2.6%, p < 0.001), the mean LAD dose (2.5 ± 3.4 vs. 4.8 ± 5.5 Gy, p < 0.001), the maximum spinal cord dose (1.5 ± 1.1 vs. 4.5 ± 5.7 Gy, p = 0.016), and the maximum skin dose (39.6 ± 1.8 vs. 49.1 ± 5.8 Gy, p = 0.000). APBI should be recommended to suitable patients to minimize the risk of secondary tumor induction and the incidence of consecutive major cardiac events.
CRIS-Team Scopus Importer:2023-08-25
Keywords: accelerated partial-breast irradiation; breast cancer; mean heart dose; mean lung dose; organs-at-risk

Fast optimization and dose calculation in scanned ion beam therapy - Hild, S.; Graeff, Christian; Trautmann, J.; Kraemer, M.; Zink, Klemens; Durante, Marco; Bert, Christoph (Medical Physics, 2014)
Particle therapy (PT) has advantages over photon irradiation on static tumors. An increased biological effectiveness and active target conformal dose shaping are strong arguments for PT. However, the sensitivity to changes of internal geometry complicates the use of PT for moving organs. In case of interfractionally moving objects adaptive radiotherapy (ART) concepts known from intensity modulated radiotherapy (IMRT) can be adopted for PT treatments. One ART strategy is to optimize a new treatment plan based on daily image data directly before a radiation fraction is delivered [treatment replanning (TRP)]. Optimizing treatment plans for PT using a scanned beam is a time consuming problem especially for particles other than protons where the biological effective dose has to be calculated. For the purpose of TRP, fast optimization and fast dose calculation have been implemented into the GSI in-house treatment planning system (TPS) TRiP98.This work reports about the outcome of a code analysis that resulted in optimization of the calculation processes as well as implementation of routines supporting parallel execution of the code. To benchmark the new features, the calculation time for therapy treatment planning has been studied.Compared to the original version of the TPS, calculation times for treatment planning (optimization and dose calculation) have been improved by a factor of 10 with code optimization. The parallelization of the TPS resulted in a speedup factor of 12 and 5.5 for the original version and the code optimized version, respectively. Hence the total speedup of the new implementation of the authors' TPS yielded speedup factors up to 55.The improved TPS is capable of completing treatment planning for ion beam therapy of a prostate irradiation considering organs at risk in this has been overseen in the review process. Also see below 6 min.
EVALuna2:18191

Feasibility of artificial-intelligence-based synthetic computed tomography in a magnetic resonance-only radiotherapy workflow for brain radiotherapy: Two-way dose validation and 2D/2D kV-image-based positioning - Masitho, Siti; Szkitsak, Juliane; Grigo, Johanna; Fietkau, Rainer; Putz, Florian; Bert, Christoph (Physics and Imaging in Radiation Oncology, 2022)
Background and purpose: Magnetic Resonance Imaging (MRI)-only workflow eliminates the MRI-computed tomography (CT) registration inaccuracy, which degrades radiotherapy (RT) treatment accuracy. For an MRI-only workflow MRI sequences need to be converted to synthetic-CT (sCT). The purpose of this study was to evaluate a commercially available artificial intelligence (AI)-based sCT generation for dose calculation and 2D/2D kV-image daily positioning for brain RT workflow. Materials and methods: T1-VIBE DIXON was acquired at the 1.5 T MRI for 26 patients in RT setup for sCTs generation. For each patient, a volumetric modulated arc therapy (VMAT) plan was optimized on the CT, then recalculated on the sCT; and vice versa. sCT-based digitally reconstructed radiographs (DRRs) were fused with stereoscopic X-ray images recorded as image guidance for clinical treatments. Dosimetric differences between planned/recalculated doses and the differences between the calculated and recorded clinical couch shift/rotation were evaluated. Results: Mean ΔD50 between planned/recalculated doses for target volumes ranged between −0.2 % and 0.2 %; mean ΔD50 and ΔD0.01ccm were −0.6 % and 1.6 % and −1.4 % and 1.0 % for organ-at-risks, respectively. Differences were tested for clinical equivalence using intervals ±2 % (dose), ±1mm (translation), and ±1° (rotation). Dose equivalence was found using ±2 % interval (p < 0.001). The median differences between lat./long./vert. couch shift between CT-based/sCT-based DRRs were 0.3 mm/0.2 mm/0.3 mm (p < 0.05); median differences between lat./long./vert. couch rotation were −1.5°/0.1°/0.1° (after improvement of RT setup: −0.4°/−0.1°/−0.4°, p < 0.05). Conclusions: This in-silico study showed that the AI-based sCT provided equivalent results to the CT for dose calculation and daily stereoscopic X-ray positioning when using an optimal RT setup during MRI acquisition.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Artificial intelligence; Brain radiotherapy; kV-image-based positioning; MRI-only workflow; Synthetic CT

Feasibility of daily kV-Recording-based Positioning by using DRRs from an AI-based synthetic CT for MR-only intracranial Stereotactic Radiotherapy - Masitho, Siti; Grigo, Johanna; Szkitsak, Juliane; Reissig, L.; Fietkau, Rainer; Putz, Florian; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Feasibility Study on Cardiac Arrhythmia Ablation Using High-Energy Heavy Ion Beams - Lehmann, H. Immo; Graeff, Christian; Simoniello, Palma; Constantinescu, Anna; Takami, Mitsuru; Lugenbiel, Patrick; Richter, Daniel; Eichhorn, Anna; Prall, Matthias; Kaderka, Robert; Fiedler, Fine; Helmbrecht, Stephan; et al. (Scientific Reports, 2016)
High-energy ion beams are successfully used in cancer therapy and precisely deliver high doses of ionizing radiation to small deep-seated target volumes. A similar noninvasive treatment modality for cardiac arrhythmias was tested here. This study used high-energy carbon ions for ablation of cardiac tissue in pigs. Doses of 25, 40, and 55 Gy were applied in forced-breath-hold to the atrioventricular junction, left atrial pulmonary vein junction, and freewall left ventricle of intact animals. Procedural success was tracked by (1.) in-beam positron-emission tomography (PET) imaging; (2.) intracardiac voltage mapping with visible lesion on ultrasound; (3.) lesion outcomes in pathohistolgy. High doses (40-55 Gy) caused slowing and interruption of cardiac impulse propagation. Target fibrosis was the main mediator of the ablation effect. In irradiated tissue, apoptosis was present after 3, but not 6 months. Our study shows feasibility to use high-energy ion beams for creation of cardiac lesions that chronically interrupt cardiac conduction.
EVALuna2:33045

First clinical evaluation of breathing controlled four-dimensional computed tomography imaging - Szkitsak, Juliane; Werner, René; Fernolendt, Susanne; Schwarz, Annette; Ott, Oliver; Fietkau, Rainer; Hofmann, Christian; Bert, Christoph (Physics and Imaging in Radiation Oncology, 2021)
Background and Purpose: Four-dimensional computed tomography (4DCT) has become an essential part of radiotherapy planning but is often affected by artifacts. A new breathing controlled 4DCT (i4DCT) algorithm has been introduced. This study aims to present the first clinical data and to evaluate the achieved image quality, projection data coverage and beam-on time. Material & Methods: The analysis included i4DCT data for 129 scans of patients with thoracic tumors. Projection data coverage and beam-on time were evaluated. Additionally, image quality was exemplarily discussed and rated by ten clinical experts with a 5-score-scale for 30 patients with large variations in their breathing pattern (‘challenging subgroup’). Rated images were reconstructed amplitude- and phase-based. Results: Expert scoring revealed that 78% (amplitude-based) and 63% (phase-based) of the challenging subgroup were artifact-free (rating ≥4). For the entire cohort, average beam-on time per couch position was 4.9 ± 1.6 s. For the challenging subgroup, time increased slightly but not significantly compared to the remaining patients (5.1 s vs. 4.9 s; p = 0.64). Median projection data coverage was 93% and 94% for inhalation and exhalation, respectively, for the entire cohort. The comparison for the subgroup and the remaining patients revealed a small but significant decrease of the median coverage values for the challenging cases (inhalation: 90% vs. 94%, p = 0.02; exhalation: 93% vs. 94%, p = 0.02). Conclusions: This first clinical evaluation of i4DCT shows very promising results in terms of image quality and projection data coverage. The results agree with and support the results of previous i4DCT phantom studies.
CRIS-Team Scopus Importer:2021-11-12
Keywords: 4DCT; Motion artifacts; Respiratory motion

First clinical experience with a novel, mobile cone-beam CT system for treatment quality assurance in brachytherapy - Karius, Andre; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Bert, Christoph (Strahlentherapie und Onkologie, 2022)
Background and purpose: On-site cone-beam computed tomography (CBCT) has gained in importance in adaptive brachytherapy during recent years. Besides treatment planning, there is increased need particularly for image-guidance during interventional procedures and for image-guided treatment quality assurance (QA). For this purpose, an innovative CBCT device was rolled out at our hospital as the first site worldwide. We present the first clinical images and experiences. Materials and methods: The novel CBCT system is constructed of a 121 cm diameter ring gantry, and features a 43.2 × 43.2 cm2 flat-panel detector, wireless remote-control via tablet-PC, and battery-powered maneuverability. Within the first months of clinical operation, we performed CBCT-based treatment QA for a total of 26 patients (8 with breast, 16 with cervix, and 2 with vaginal cancer). CBCT scans were analyzed regarding potential movements of implanted applicators in-situ during the brachytherapy course. Results: With the presented device, treatment QA was feasible for the majority of patients. The CBCT scans of breast patients showed sufficient contrast between implanted catheters and tissue. For gynecologic patients, a distinct visualization of applicators was achieved in general. However, reasonable differentiations of organic soft tissues were not feasible. Conclusion: The CBCT system allowed basic treatment QA measures for breast and gynecologic patients. For image-guidance during interventional brachytherapy procedures, the current image quality is not adequate. Substantial performance enhancements are required for intraoperative image-guidance.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Adaptive brachytherapy; Gynecologic brachytherapy; Image-guidance; Mobile imaging; On-site computed tomography imaging

First implementation of an innovative infra-red camera system integrated into a mobile CBCT scanner for applicator tracking in brachytherapy—Initial performance characterization - Karius, Andre; Leifeld, Lisa Marie; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2024)
Purpose: To enable a real-time applicator guidance for brachytherapy, we used for the first time infra-red tracking cameras (OptiTrack, USA) integrated into a mobile cone-beam computed tomography (CBCT) scanner (medPhoton, Austria). We provide the first description of this prototype and its performance evaluation. Methods: We performed assessments of camera calibration and camera-CBCT registration using a geometric calibration phantom. For this purpose, we first evaluated the effects of intrinsic parameters such as camera temperature or gantry rotations on the tracked marker positions. Afterward, calibrations with various settings (sample number, field of view coverage, calibration directions, calibration distances, and lighting conditions) were performed to identify the requirements for achieving maximum tracking accuracy based on an in-house phantom. The corresponding effects on camera-CBCT registration were determined as well by comparing tracked marker positions to the positions determined via CBCT. Long-term stability was assessed by comparing tracking and a ground-truth on a weekly basis for 6 weeks. Results: Robust tracking with positional drifts of 0.02 ± 0.01 mm was feasible using the system after a warm-up period of 90 min. However, gantry rotations affected the tracking and led to inaccuracies of up to 0.70 mm. We identified that 4000 samples and full coverage were required to ensure a robust determination of marker positions and camera-CBCT registration with geometric deviations of 0.18 ± 0.03 mm and 0.42 ± 0.07 mm, respectively. Long-term stability showed deviations of more than two standard deviations from the initial calibration after 3 weeks. Conclusion: We implemented for the first time a standalone combined camera-CBCT system for tracking in brachytherapy. The system showed high potential for establishing corresponding workflows.
CRIS-Team Scopus Importer:2024-05-03
Keywords: brachytherapy; combined camera-CT system; infra-red applicator tracking; system characterization

First Steps Toward Ultrasound-Based Motion Compensation for Imaging and Therapy: Calibration with an Optical System and 4D PET Imaging - Schwaab, Julia; Kurz, Christopher; Sarti, Cristina; Bongers, Andre; Schoenahl, Frederic; Bert, Christoph; Debus, Juergen; Parodi, Katia; Jenne, Juergen Walter (Frontiers in Oncology, 2015)
Target motion, particularly in the abdomen, due to respiration or patient movement is still a challenge in many diagnostic and therapeutic processes. Hence, methods to detect and compensate this motion are required. Diagnostic ultrasound (US) represents a non-invasive and dose-free alternative to fluoroscopy, providing more information about internal target motion than respiration belt or optical tracking. The goal of this project is to develop an US-based motion tracking for real-time motion correction in radiation therapy and diagnostic imaging, notably in 4D positron emission tomography (PET). In this work, a workflow is established to enable the transformation of US tracking data to the coordinates of the treatment delivery or imaging system - even if the US probe is moving due to respiration. It is shown that the US tracking signal is equally adequate for 4D PET image reconstruction as the clinically used respiration belt and provides additional opportunities in this concern. Furthermore, it is demonstrated that the US probe being within the PET field of view generally has no relevant influence on the image quality. The accuracy and precision of all the steps in the calibration workflow for US tracking-based 4D PET imaging are found to be in an acceptable range for clinical implementation. Eventually, we show in vitro that an US-based motion tracking in absolute room coordinates with a moving US transducer is feasible.
EVALuna2:18367

Four-dimensional patient dose reconstruction for scanned ion beam therapy of moving liver tumors - Richter, Daniel; Saito, Nami; Chaudhri, Naved; Haertig, Martin; Ellerbrock, Malte; Jaekel, Oliver; Combs, Stephanie E.; Habermehl, Daniel; Herfarth, Klaus; Durante, Marco; Bert, Christoph (International Journal of Radiation Oncology Biology Physics, 2014)
Estimation of the actual delivered 4-dimensional (4D) dose in treatments of patients with mobile hepatocellular cancer with scanned carbon ion beam therapy.Six patients were treated with 4 fractions to a total relative biological effectiveness (RBE)-weighted dose of 40 Gy (RBE) using a single field. Respiratory motion was addressed by dedicated margins and abdominal compression (5 patients) or gating (1 patient). 4D treatment dose reconstructions based on the treatment records and the measured motion monitoring data were performed for the single-fraction dose and a total of 17 fractions. To assess the impact of uncertainties in the temporal correlation between motion trajectory and beam delivery sequence, 3 dose distributions for varying temporal correlation were calculated per fraction. For 3 patients, the total treatment dose was formed from the fractional distributions using all possible combinations. Clinical target volume (CTV) coverage was analyzed using the volumes receiving at least 95% (V95) and 107% (V107) of the planned doses.4D dose reconstruction based on daily measured data is possible in a clinical setting. V95 and V107 values for the single fractions ranged between 72% and 100%, and 0% and 32%, respectively. The estimated total treatment dose to the CTV exhibited improved and more robust dose coverage (mean V95 > 87%, SD < 3%) and overdose (mean V107 < 4%, SD < 3%) with respect to the single-fraction dose for all analyzed patients.A considerable impact of interplay effects on the single-fraction CTV dose was found for most of the analyzed patients. However, due to the fractionated treatment, dose heterogeneities were substantially reduced for the total treatment dose. 4D treatment dose reconstruction for scanned ion beam therapy is technically feasible and may evolve into a valuable tool for dose assessment.
EVALuna2:18188

FSRT vs. SRS in Brain Metastases—Differences in Local Control and Radiation Necrosis—A Volumetric Study - Putz, Florian; Weissmann, Thomas; Oft, Dominik; Schmidt, Manuel; Roesch, Johannes; Siavooshhaghighi, Hadi; Filimonova, Irina; Schmitter, Charlotte; Mengling, Veit; Bert, Christoph; Frey, Benjamin; Lettmaier, Sebastian; et al. (Frontiers in Oncology, 2020)
Background: While the role of stereotactic radiotherapy for brain metastases is increasing, evidence on the comparative efficacy and safety of fractionated stereotactic radiotherapy (FSRT) and single-session radiosurgery (SRS) is scarce. Methods: Longitudinal volumetric analysis was performed in a consecutive cohort of 120 patients and 190 brain metastases (>0.065 cm3 in volume / > 5 mm in diameter) treated exclusively with FSRT (n = 98) and SRS (n = 92), respectively. A total of 972 tumor segmentations was used, averaging 5.1 time points per metastasis. Progression was defined using a volumetric extension of the RANO-BM criteria. Local control and radionecrosis were compared for lesions treated with FSRT and SRS, respectively. Results: Metastases treated with FSRT were significantly larger at baseline (mean, 4.66 vs. 0.40 cm3, p < 0.001). Biologically effective dose (BED) for metastases (α/β = 12, linear-quadratic-cubic model) was significantly associated with local control, whereas BED for normal brain (α/β = 2, linear-quadratic model) was significantly associated with radionecrosis. Median time to local progression was 22.9 months in the FSRT group compared to 14.5 months in the SRS group (p = 0.022). Overall radionecrosis rate at 12 months was 3.4% for FSRT and 14.8% for SRS (p = 0.010). Radionecrosis °IV requiring resection with histologic proof of radiation necrosis also was significantly reduced in the FSRT group (FSRT 0.0% vs. SRS 3.9%, p = 0.041). In multivariate analysis, FSRT was associated with reduced risk of progression (HR 0.47, p = 0.015) and reduced risk of radionecrosis (HR 0.18, p = 0.045). Conclusions: This volumetric study provides initial evidence that the improvements in therapeutic ratio expected for FSRT in larger brain metastases, might equally extend into the domain of smaller metastases, traditionally less considered for fractionated treatment. FSRT might constitute an important tool to further increase local control and reduce radionecrosis risk in stereotactic radiotherapy for brain metastases, that should be assessed in randomized intervention trials.
CRIS-Team Scopus Importer:2020-10-30
Keywords: brain metastases; fractionated stereotactic radiotherapy; radiobiological aspects; segmentation; stereotactic radiosurgery (SRS); stereotactic radiotherapy (SRT); volumetric analysis

Hemicorporal paresthesias in a parvovirusinfection - Baltas, Dimos; Ladd, Mark E.; Fiebich, Martin; Bert, Christoph; Heufelder, Jens (Zeitschrift für Medizinische Physik, 2020)
CRIS-Team WoS Importer:2021-01-29

High Detection Accuracy of an optimized 3D Convolutional Neural Network for Auto Detection and Auto Segmentation of Brain Metastases - Putz, Florian; Weissmann, Thomas; Mansoorian, Sina; Schmitter, Charlotte; Semrau, Sabine; Lettmaier, Sebastian; Masitho, Siti; Grigo, Johanna; Schmidt, Manuel; Heiß, Rafael; Frey, Benjamin; Bert, Christoph; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Hypofractionated Irradiation Has Immune Stimulatory Potential and Induces a Timely Restricted Infiltration of Immune Cells in Colon Cancer Tumors - Frey, Benjamin; Rueckert, Michael; Weber, Julia; Mayr, Xaver; Derer, Anja; Lotter, Michael; Bert, Christoph; Roedel, Franz; Fietkau, Rainer; Gaipl, Udo (Frontiers in Immunology, 2017)
In addition to locally controlling the tumor, hypofractionated radiotherapy (RT) particularly aims to activate immune cells in the RT-modified microenvironment. Therefore, we examined whether hypofractionated RT can activate dendritic cells (DCs), induce immune cell infiltration in tumors, and how the chronology of immune cell migration into tumors occurs to gain knowledge for future definition of radiation breaks and inclusion of immunotherapy. Colorectal cancer treatments offer only limited survival benefit, and immunobiological principles for additional therapies need to be explored with preclinical models. The impact of hypofractionated RT on CT26 colon cancer tumor cell death, migration of DCs toward supernatants (SN) of tumor cells, and activation of DCs by SN were analyzed. The subcutaneous tumor of a BALB/c-CT26 mouse model was locally irradiated with 2 × 5 Gy, the tumor volume was monitored, and the infiltration of immune cells in the tumor was determined by flow cytometry daily. Hypofractionated RT induced a mixture of apoptotic and necrotic CT26 cells, which is known to be in particular immunogenic. DCs that migrated toward SN of CT26 cells particularly upregulated the activation markers CD80 and CD86 when in contact with SN of irradiated tumor cells. After hypofractionated RT, the tumor outgrowth was significantly retarded and in the irradiated tumors an increased infiltration of macrophages (CD11bhigh/F4-80+) and DCs (MHC-II+), but only between day 5 and 10 after the first irradiation, takes place. While CD4+T cells migrated into non-irradiated and irradiated tumors, CD8+T cells were only found in tumors that had been irradiated and they were highly increased at day 8 after the first irradiation. Myeloid-derived suppressor cells and regulatory T cells show regular turnover in irradiated and non-irradiated tumors. Tumor cell-specific anti-IgM antibodies were enhanced in the serum of animals with irradiated tumors. We conclude that hypofractionated RT suffices to activate DCs and to induce infiltration of innate and adaptive immune cells into solid colorectal tumors. However, the presence of immune cells in the tumor which are beneficial for antitumor immune responses is timely restricted. These findings should be considered when innovative multimodal tumor treatment protocols of distinct RT with immune therapies are designed and clinically implemented.
EVALuna2:32906

Identification of High-risk Metastases in MRI Follow-up after Stereotaxic by using Radiomics and Delta Radiomics - Sommer, Phillip; Huang, Yixing; Fischer, Stefan; Srinivasan, Aishwarya Lakshmi; Dörfler, Arnd; Schmidt, M.; Frey, Benjamin; Maier, Andreas; Fietkau, Rainer; Bert, Christoph; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Immobilization for carbon ion beam ablation of cardiac structures in a porcine model - Prall, Matthias; Eichhorn, Anna; Richter, Daniel; Lehmann, H. Immo; Constantinescu, Anna; Kaderka, Robert; Lugenbiel, Patrick; Thomas, Dierk; Bert, Christoph; Packer, Douglas L.; Durante, Marco; Graeff, Christian (Physica Medica, 2017)
INTRODUCTION: Whereas hadron therapy of static targets is clinically established, treatment of moving organs remains a challenge. One strategy is to minimize motion of surrounding tissue mechanically and to mitigate residual motion with an appropriate irradiation technique. In this technical note, we present and characterize such an immobilization technique for a novel noncancerous application: the irradiation of small targets in hearts with scanned carbon ion beams in a porcine model for elimination of arrhythmias. MATERIAL AND METHODS: A device for immobilization was custom-built. Both for the treatment planning 4D-CT scan and for irradiation, breath-hold at end-exhale was enforced using a remotely-controlled respirator. Target motion was thus reduced to heartbeat only. Positioning was verified by orthogonal X-rays followed by couch shift if necessary. Reproducibility of bony anatomy, diaphragm, and heart position after repositioning and between repeated breath-hold maneuvers was evaluated on X-rays and cardiac-gated 4D-CTs. Treatment was post hoc simulated on sequential 4D-CTs for a subset of animals, after immediate repositioning and after a delay of one week, similar to the delay between imaging and irradiation. RESULTS: Breath-hold without repositioning was highly reproducible with an RMS deviation of at most one millimeter. 4D-CTs showed larger deformations in soft tissue, but treatment simulation on sequential images resulted in full target coverage (V95 >95%). CONCLUSION: The method of immobilization permitted reproducible positioning of mobile, thoracic targets for range-sensitive particle therapy. The presented immobilization strategy could be a reasonable approach for future animal investigations with the ultimate goal of translation to therapy in men.
EVALuna2:33031

Impact of fractionation and number of fields on dose homogeneity for intra-fractionally moving lung tumors using scanned carbon ion treatment - Woelfelschneider, Jens; Friedrich, Thomas; Luechtenborg, Robert; Zink, Klemens; Scholz, Michael; Dong, Lei; Durante, Marco; Bert, Christoph (Radiotherapy and Oncology, 2016)
Scanned particle beam therapy may result in over and under dosages within the target volume. This study quantifies how CTV dose coverage improves with number of fractions and fields.Based on 4DCTs of nine lung tumor patients, treatment plans were optimized separately for four different fields using an ITV approach. 4D RBE-weighted dose distributions were calculated for varying motion parameters and fraction numbers. The total RBE-weighted dose was determined for one and four-field application per fraction. DVHs were analyzed for the tumor and interpreted based on statistical modeling.Dose homogeneity within the CTV increased with the fraction number, but depends significantly on the tumor motion amplitude. For single-field schedules and amplitudes >6mm, the dose coverage indices (V95min=90.7% and V107max=0.4%) differed to the stationary case even after 40 fractions. Target coverage for a four-field approach followed a proposed model and homogeneous dose distributions could be achieved 6-times faster than single-field treatments.Fractionated delivery improves dose homogeneity in scanned ion beam therapy of moving targets. The achievable homogeneity depends mainly on tumor volume and motion amplitude. The outcome of multiple-field irradiations can be predicted based on single-field results and accelerates the achievement of homogeneous dose distributions.
EVALuna2:18345

Impact of inter- and intra-observer variabilities of catheter reconstruction on multi-catheter interstitial brachytherapy of breast cancer patients - Kallis, Karoline; Kaltsas, Theodoros; Kreppner, Stephan; Lotter, Michael; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2019)
Purpose: The aim of this study was to evaluate inter- and intra-observer variabilities of catheter reconstruction and its dosimetric impact for multi-catheter interstitial breast cancer patients. Methods and materials: In order to evaluate inter-observer variabilities (IOV) three medical physicists reconstructed the catheter traces of 13 patients. These manual reconstructions were further compared to the automatic reconstruction algorithm integrated into the planning system and one on purpose imprecise manual reconstruction. For intra-observer variabilities (IAV) repeated reconstructions of two physicists were compared for 13 patients. In total 426 catheters were considered. Keeping dwell times, dwell positions, the optimization and the normalization relative points constant the geometrical deviations between the corresponding dwell positions of the reference data set and the investigated reconstructions were evaluated. Also, the effect on the quality indices, such as coverage index (CI), dose non-uniformity ratio (DNR) or conformal index (COIN), and the exposure of the organs at risk were analyzed. Results: Over all patients and all different catheter reconstructions considered for IOV a mean deviation between the corresponding dwell positions of 0.60 ± 0.35 mm was detected. The first observer had a mean deviation of 0.54 ± 0.32 mm, whereas the second observer yielded a mean deviation of 0.58 ± 0.37 mm. The length of the catheter traces varied in the mean by 0.51 ± 0.45 mm. The mean relative deviation of the CI, DNR, COIN, mean heart dose and mean lung dose varied by 0.27 ± 0.31%, 0.0027 ± 0.0025, 0.0036 ± 0.0033, 0.024 ± 0.019%, 0.05 ± 0.11%, respectively. The skin dose (D 0.2ccm ) changed in the maximum 8.52%. On average IAV reached a deviation between the corresponding dwell positions of 0.49 ± 0.30 mm. IOVs and IAVs proved to be significantly different (Wilcoxon's test p < 0.01). Conclusions: The study proved that a repeated reconstruction of the catheter traces does not lead to large geometrical deviations or to a significant change in the dose exposure. But the lack of ground truth makes the estimation of the quality of the reconstruction challenging. A precise reconstruction mapping the reality is a necessity for the planned dose delivery. With all considered reconstruction techniques reliable quality indices for the target and the organs at risk could be obtained.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Breast cancer; Inter-observer variability; Interstitial multi-catheter brachytherapy

Impact of patient positioning on interstitial multicatheter HDR brachytherapy of the breast - Abu-Hossin, N.; Kallis, Karoline; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-18

Implant-based CT estimation towards adaptive breast brachytherapy - Dürrbeck, Christopher; Pflaum, L.; Schulz, M.; Kallis, Karoline; Geimer, Tobias; Abu-Hossin, N.; Strnad, Vratislav; Maier, Andreas; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-18

Implementation and validation of 2-D-array based tests in routine linac quality assurance - Valenta, Jiri; Schmidt, Manfred; Bert, Christoph (Zeitschrift für Medizinische Physik, 2024)
Purpose: In medical linac quality assurance (QA), to replace film dosimetry with low-resolution 2-D ionization chamber array measurements, to validate the procedures, and to perform a comprehensive sensitivity analysis. Methods: A 2-D ionization chamber array with a spatial resolution of 7.62 mm was deployed to perform the following tests: Junction tests, MLC transmission test, beam profile constancy vs. gantry angle test, beam profile constancy vs. low dose delivery test, and beam energy constancy vs. low dose delivery test. Test validation and sensitivity analyses based on short- and long-term statistics of the test results were performed. Results: All selected mechanical and dosimetry tests could be successfully performed with a 2-D array. Considering the tolerance limits recommended by the AAPM Task Group 142 report (2009), sensitivities of 99.0% or better and specificities ranging from 99.5% to 99.9% could be achieved in all tests when the proper metrics were chosen. Conclusions: The results showed that a low-resolution 2-D ionization chamber array could replace film dosimetry without having to sacrifice high test sensitivity. Its implementation in the routine clinical linac QA program may involve considerable QA time savings.
CRIS-Team Scopus Importer:2024-03-22
Keywords: 2-D array; Linear accelerator quality assurance; Test sensitivity; Test specificity

Implementation of a dedicated 1.5 T MR scanner for radiotherapy treatment planning featuring a novel high-channel coil setup for brain imaging in treatment position - Mengling, Veit; Bert, Christoph; Perrin, Rosalind; Masitho, Siti; Weissmann, Thomas; Mansoorian, Sina; Siavooshhaghighi, Hadi; Janka, Rolf Matthias; Doussin, Sylvain; Habatsch, Melanie; Fietkau, Rainer; Putz, Florian (Strahlentherapie und Onkologie, 2020)
Purpose: To share our experiences in implementing a dedicated magnetic resonance (MR) scanner for radiotherapy (RT) treatment planning using a novel coil setup for brain imaging in treatment position as well as to present developed core protocols with sequences specifically tuned for brain and prostate RT treatment planning. Materials and methods: Our novel setup consists of two large 18-channel flexible coils and a specifically designed wooden mask holder mounted on a flat tabletop overlay, which allows patients to be measured in treatment position with mask immobilization. The signal-to-noise ratio (SNR) of this setup was compared to the vendor-provided flexible coil RT setup and the standard setup for diagnostic radiology. The occurrence of motion artifacts was quantified. To develop magnetic resonance imaging (MRI) protocols, we formulated site- and disease-specific clinical objectives. Results: Our novel setup showed mean SNR of 163 ± 28 anteriorly, 104 ± 23 centrally, and 78 ± 14 posteriorly compared to 84 ± 8 and 102 ± 22 anteriorly, 68 ± 6 and 95 ± 20 centrally, and 56 ± 7 and 119 ± 23 posteriorly for the vendor-provided and diagnostic setup, respectively. All differences were significant (p > 0.05). Image quality of our novel setup was judged suitable for contouring by expert-based assessment. Motion artifacts were found in 8/60 patients in the diagnostic setup, whereas none were found for patients in the RT setup. Site-specific core protocols were designed to minimize distortions while optimizing tissue contrast and 3D resolution according to indication-specific objectives. Conclusion: We present a novel setup for high-quality imaging in treatment position that allows use of several immobilization systems enabling MR-only workflows, which could reduce unnecessary dose and registration inaccuracies.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Immobilization; MR-only treatment planning; Prostate; Simulation; Stereotactic radiosurgery

Implementation of an analytical model for leakage neutron equivalent dose in a proton radiotherapy planning system - Eley, John; Newhauser, Wayne; Homann, Kenneth; Howell, Rebecca; Schneider, Christopher; Durante, Marco; Bert, Christoph (Cancers, 2015)
Equivalent dose from neutrons produced during proton radiotherapy increases the predicted risk of radiogenic late effects. However, out-of-field neutron dose is not taken into account by commercial proton radiotherapy treatment planning systems. The purpose of this study was to demonstrate the feasibility of implementing an analytical model to calculate leakage neutron equivalent dose in a treatment planning system. Passive scattering proton treatment plans were created for a water phantom and for a patient. For both the phantom and patient, the neutron equivalent doses were small but non-negligible and extended far beyond the therapeutic field. The time required for neutron equivalent dose calculation was 1.6 times longer than that required for proton dose calculation, with a total calculation time of less than 1 h on one processor for both treatment plans. Our results demonstrate that it is feasible to predict neutron equivalent dose distributions using an analytical dose algorithm for individual patients with irregular surfaces and internal tissue heterogeneities. Eventually, personalized estimates of neutron equivalent dose to organs far from the treatment field may guide clinicians to create treatment plans that reduce the risk of late effects.
EVALuna2:18366

Implementation of registration quality assurance - Anderle, K.; Brandt, Tobias; Wölfelschneider, Jens; Bert, Christoph; Graeff, C. (2018)
EVALuna2:36477

Implementation of Whole Skin Therapy: Dosimetry, Optimization and FMEA Analysis - Shariff, Maya; Lotter, M.; Stillkrieg, W.; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Improvement of Deep Learning-based Auto-detection of Brain Metastases by Integrating previous MRI Images - Dörfler, Arnd; Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Maier, Andreas; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Improving the safety of radiotherapy treatment processes via incident-driven FMEA feedback loops - Kornek, Dominik; Lotter, Michael; Szkitsak, Juliane; Dürrbeck, Christopher; Karius, Andre; Ott, Oliver; Brandl, Carolin; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2024)
Background: Failure mode and effects analysis (FMEA) is a valuable tool for radiotherapy risk assessment, yet its outputs might be unreliable due to failures not being identified or due to a lack of accurate error rates. Purpose: A novel incident reporting system (IRS) linked to an FMEA database was tested and evaluated. The study investigated whether the system was suitable for validating a previously performed analysis and whether it could provide accurate error rates to support the expert occurrence ratings of previously identified failure modes. Methods: Twenty-three pre-identified failure modes of our external beam radiotherapy process, covering the process steps from patient admission to treatment delivery, were proffered on dedicated FMEA feedback and incident reporting terminals generated by the IRS. The clinical setting involved a computed tomography scanner, dosimetry, and five linacs. Incoming reports were used as basis to identify additional failure modes or confirm initial ones. The Kruskal–Wallis H test was applied to compare the risk priorities of the retrospective and prospective failure modes. Wald's sequential probability ratio test was used to investigate the correctness of the experts’ occurrence ratings by means of the number of incoming reports. Results: Over a 15-month period, 304 reports were submitted. There were 0.005 (confidence interval [CI], 0.0014–0.0082) reported incidents per imaging study and 0.0006 (CI, 0.0003–0.0009) reported incidents per treatment fraction. Sixteen additional failure modes could be identified, and their risk priorities did not differ from those of the initial failure modes (p = 0.954). One failure mode occurrence rating could be increased, whereas the other 22 occurrence ratings could not be disproved. Conclusions: Our approach is suitable for validating FMEAs and deducing additional failure modes on a continual basis. Accurate error rates can only be provided if a sufficient number of reports is available.
CRIS-Team Scopus Importer:2024-08-23
Keywords: error rates; failure mode and effects analysis (FMEA); incident reporting system (IRS); radiotherapy; risk assessment

Influence and compensation of patient motion in electromagnetic tracking based quality assurance in interstitial brachytherapy of the breast - Dürrbeck, Christopher; Gulde, Sarah; Abu-Hossin, Nadin; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (Medical Physics, 2022)
Purpose: Electromagnetic tracking (EMT) is a versatile and viable technique for various quality assurance (QA) tasks in interstitial brachytherapy (iBT). As the duration of EMT measurements in iBT is on the order of minutes, they can be strongly affected by patient motion, especially breathing, which gives rise to motion artefacts. Since the centrepiece of EMT-related QA in iBT is to assess the geometry of the iBT implant or applicator, the absence of adequate motion compensation techniques could impede the use of EMT for QA purposes. A common way to compensate for this is to reference the data to either external or internal reference sensors (ERS, IRS) which are fixated on the patient's body or inside the applicator and therefore move with the patient. The purpose of the presented study is to provide a quantitative and in-depth analysis on the use of reference sensors for motion compensation. Methods: First, the need for adequate motion compensation is identified both qualitatively and quantitatively using a phantom subjected to simulated breathing motion. An evaluation routine is developed to assess the influence of motion compensation using reference sensors on the acquired EMT data. The evaluation metric is based on the observed displacement of the EMT sensor from its mean position while dwelling at a dwell position (DP) for a dwell time of 1 s. After that, the routine is applied to a cohort of 54 breast cancer patients treated with iBT, and the quality of an ERS based compensation approach is assessed. In a subgroup of four patients, an IRS is inserted into the iBT implant and IRS-based compensation is compared to the ERS-based approach. Moreover, a correlation analysis of the ERS and IRS approach is performed, also including respiratory signals derived from the trajectories of the different reference sensors. Results: It was found that motion compensation with ERS effectively reduced the mean sensor displacement per DP to median values as low as 0.11 mm in both phantom and patient measurements, which is below the precision of the EMT system (0.48 mm). Compensation using the IRS yielded comparable results and was as good as compensation with ERS. The results obtained from both approaches showed a strong correlation. Also the respiratory signals calculated from the different reference sensors were well correlated in most cases. Conclusion: These results indicate that motion compensation with ERS can effectively remove motion artefacts in EMT data. While compensation with an IRS leads to comparable results, the IRS occupies one catheter whose geometry hence cannot be assessed. The use of ERS has proven to be both effective and practical in clinical routine.
CRIS-Team Scopus Importer:2022-03-04
Keywords: breast cancer; breathing motion; electromagnetic tracking; interstitial brachytherapy; quality assurance

Influence of MRI Distortion Correction on the local Control of stereotactically irradiated Brain Metastases - Putz, Florian; Siavooshhaghighi, Hadi; Grigo, Johanna; Masitho, Siti; Huang, Yixing; Weissmann, Thomas; Mansoorian, Sina; Schmidt, Manfred; Semrau, Sabine; Bert, Christoph; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Influence of patient mispositioning on SAR distribution and simulated temperature in regional deep hyperthermia - Aklan, Bassim; Gierse, Pia; Hartmann, Josefin; Ott, Oliver J.; Fietkau, Rainer; Bert, Christoph (Physics in Medicine and Biology, 2017)
Patient positioning plays an important role in regional deep hyperthermia to obtain a successful hyperthermia treatment. In this study, the influence of possible patient mispositioning was systematically assessed on specific absorption rate (SAR) and temperature distribution. With a finite difference time domain approach, the SAR and temperature distributions were predicted for six patients at 312 positions. Patient displacements and rotations as well as the combination of both were considered inside the Sigma-Eye applicator. Position sensitivity is assessed for hyperthermia treatment planning -guided steering, which relies on model-based optimization of the SAR and temperature distribution. The evaluation of the patient mispositioning was done with and without optimization. The evaluation without optimization was made by creating a treatment plan for the patient reference position in the center of the applicator and applied for all other positions, while the evaluation with optimization was based on creating an individual plan for each position. The parameter T90 was used for the temperature evaluation, which was defined as the temperature that covers 90% of the gross tumor volume (GTV). Furthermore, the hotspot tumor quotient (HTQ) was used as a goal function to assess the quality of the SAR and temperature distribution. The T90 was shown considerably dependent on the position within the applicator. Without optimization, the T90 was clearly decreased below 40 °C by patient shifts and the combination of shifts and rotations. However, the application of optimization for each positon led to an increase of T90 in the GTV. Position inaccuracies of less than 1 cm in the X-and Y-directions and 2 cm in the Z-direction, resulted in an increase of HTQ of less than 5%, which does not significantly affect the SAR and temperature distribution. Current positioning precision is sufficient in the X (right-left)-direction, but position accuracy is required in the Y-and Z-directions.
EVALuna2:32875

Infrared camera based thermometry for quality assurance of superficial hyperthermia applicators - Müller, Johannes; Hartmann, Josefin; Bert, Christoph (Physics in Medicine and Biology, 2016)
The purpose of this work was to provide a feasible and easy to apply phantom-based quality assurance (QA) procedure for superficial hyperthermia (SHT) applicators by means of infrared (IR) thermography. The VarioCAM hr head (InfraTec, Dresden, Germany) was used to investigate the SA-812, the SA-510 and the SA-308 applicators (all: Pyrexar Medical, Salt Lake City, UT, USA). Probe referencing and thermal equilibrium procedures were applied to determine the emissivity of the muscle-equivalent agar phantom. Firstly, the disturbing potential of thermal conduction on the temperature distribution inside the phantom was analyzed through measurements after various heating times (5-50 min). Next, the influence of the temperature of the water bolus between the SA-812 applicator and the phantom's surface was evaluated by varying its temperature. The results are presented in terms of characteristic values (extremal temperatures, percentiles and effective field sizes (EFS)) and temperature-area-histograms (TAH). Lastly, spiral antenna applicators were compared by the introduced characteristics. The emissivity of the used phantom was found to be ? = 0.91 ± 0.03, the results of both methods coincided. The influence of thermal conduction with regard to heating time was smaller than expected; the EFS of the SA-812 applicator had a size of (68.6 ± 6.7) cm(2), averaged group variances were ±3.0 cm(2). The TAHs show that the influence of the water bolus is mostly limited to depths of <3 cm, yet it can greatly enhance or reduce heat generation in this regime: at a depth of 1 cm, measured maximal temperature rises were 14.5 °C for T Bolus = 30 °C and 8.6 °C for T Bolus = 21 °C, respectively. The EFS was increased, too. The three spiral antenna applicators generated similar heat distributions. Generally, the procedure proved to yield informative insights into applicator characteristics, thus making the application of an IR camera a very useful tool in SHT technical QA.
EVALuna2:18343

Initial needle tracking with the first standalone combined infrared camera – CT system for brachytherapy—analysis of tracking accuracy and uncertainties - Karius, Andre; Leifeld, Lisa Marie; Strnad, Vratislav; Schweizer, Claudia; Fietkau, Rainer; Bert, Christoph (Strahlentherapie und Onkologie, 2024)
Purpose: A prototype infrared camera – cone-beam computed tomography (CBCT) system for tracking in brachytherapy has recently been developed. We evaluated for the first time the corresponding tracking accuracy and uncertainties, and implemented a tracking-based prediction of needles on CBCT scans. Methods: A marker tool rigidly attached to needles was 3D printed. The precision and accuracy of tool tracking was then evaluated for both static and dynamic scenarios. Euclidean distances between the tracked and CBCT-derived markers were assessed as well. To implement needle tracking, ground truth models of the tool attached to 200 mm and 160 mm needles were matched to the tracked positions in order to project the needles into CBCT scans. Deviations between projected and actual needle tips were measured. Finally, we put our results into perspective with simulations of the system’s tracking uncertainties. Results: For the stationary scenario and dynamic movements, we achieved tool-tracking precision and accuracy of 0.04 ± 0.06 mm and 0.16 ± 0.18 mm, respectively. The tracked marker positions differed by 0.52 ± 0.18 mm from the positions determined via CBCT. In addition, the predicted needle tips in air deviated from the actual tip positions by only 1.62 ± 0.68 mm (200 mm needle) and 1.49 ± 0.62 mm (160 mm needle). The simulated tracking uncertainties resulted in tip variations of 1.58 ± 0.91 mm and 1.31 ± 0.69 mm for the 200 mm and 160 mm needles, respectively. Conclusion: With the innovative system it was possible to achieve a high tracking and prediction accuracy of marker tool and needles. The system shows high potential for applicator tracking in brachytherapy.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Adaptive treatments; Gynecologic brachytherapy; Needle navigation; Optical tracking; Patient-specific implantations

Integration of a Halcyon Accelerator with ARIA in a Mosaiq - Environment - Risk Analysis Procedure - Shariff, Maya; Lotter, M.; Lambrecht, U.; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Inter-observer effects in needle reconstruction for temporary prostate brachytherapy: Dosimetric implications and adaptive CBCT-TRUS registration solutions - Karius, Andre; Kreppner, Stephan; Strnad, Vratislav; Schweizer, Claudia; Lotter, Michael; Fietkau, Rainer; Bert, Christoph (Brachytherapy, 2024)
PURPOSE: To investigate geometric and dosimetric inter-observer variability in needle reconstruction for temporary prostate brachytherapy. To assess the potential of registrations between transrectal ultrasound (TRUS) and cone-beam computed tomography (CBCT) to support implant reconstructions. METHODS AND MATERIALS: The needles implanted in 28 patients were reconstructed on TRUS by three physicists. Corresponding geometric deviations and associated dosimetric variations to prostate and organs at risk (urethra, bladder, rectum) were analyzed. To account for the found inter-observer variability, various approaches (template-based, probe-based, marker-based) for registrations of CBCT to TRUS were investigated regarding the respective needle transfer accuracy in a phantom study. Three patient cases were examined to assess registration accuracy in-vivo. RESULTS: Geometric inter-observer deviations >1 mm and >3 mm were found for 34.9% and 3.5% of all needles, respectively. Prostate dose coverage (changes up to 7.2%) and urethra dose (partly exceeding given dose constraints) were most affected by associated dosimetric changes. Marker-based and probe-based registrations resulted in the phantom study in high mean needle transfer accuracies of 0.73 mm and 0.12 mm, respectively. In the patient cases, the marker-based approach was the superior technique for CBCT-TRUS fusions. CONCLUSION: Inter-observer variability in needle reconstruction can substantially affect dosimetry for individual patients. Especially marker-based CBCT-TRUS registrations can help to ensure accurate reconstructions for improved treatment planning.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Cone-beam computed tomography; Image registration; Inter-observer variation; Needle reconstruction; Temporary prostate brachytherapy; Transrectal ultrasound

Introduction of a hybrid treatment delivery system used for quality assurance in multi-catheter interstitial brachytherapy - Kallis, Karoline; Kreppner, Stephan; Lotter, Michael; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (Physics in Medicine and Biology, 2018)
Multi-catheter interstitial brachytherapy (iBT) is a treatment option for breast cancer patients after breast conserving surgery. Typically, only a few additional quality interventions after the first irradiation have been introduced to ensure the planned treatment delivery. Therefore, the purpose of this study is to show the possibilities of an electromagnetic tracking (EMT) system integrated into the afterloader for quality assurance (QA) in high-dose rate (HDR) iBT of patients with breast cancer. The hybrid afterloader system equipped with an electromagnetic sensor was used for all phantom and patient measurements. Phantom measurements were conducted to estimate the quality of different evaluation schemes. After a coherent point drift registration of the EMT traces to the reconstructed catheters based on computed tomograms the dwell positions (DP) were defined. Different fitting and interpolation methods were analyzed for the reconstruction of DPs. All estimated DPs were compared to the DPs defined in treatment planning. Until now, the implant geometry of 20 patients treated with HDR brachytherapy was acquired and explored. Regarding the reconstruction techniques, both fitting and interpolation were able to detect manually introduced shifts and swaps. Nonetheless, interpolation showed superior results (RMSE = 1.27 mm), whereas fitting seemed to be more stable to distortion and motion. The EMT system proved to be beneficial for QA in brachytherapy and furthermore, clinical feasibility was proven.
EVALuna2:36464

Investigating the effects of table movement and sag on optical surrogate-driven respiratory-guided computed tomography - Lackner, Niklas; Dietrich, Lou; Karius, Andre; Fietkau, Rainer; Bert, Christoph; Szkitsak, Juliane (Journal of Applied Clinical Medical Physics, 2024)
Purpose: Respiratory-guided computed tomography (CT) typically employs breathing motion surrogates to feed image reconstruction or visual breathing coaching. Our study aimed to assess the impact of table movements and table sag on the breathing curves recorded in four-dimensional (4D) CT and deep-inspiration breath-hold (DIBH) CT. Methods: For breathing curve measurements, static and dynamic phantom scenarios were used. Breathing curves were recorded using three different surrogate systems and the impact of table sag due to weights of up to 130 kg was analyzed and compared to a non-weighted setting, respectively. The calibration procedure of the system used as an input for the visual coaching device used for clinical DIBH CT scans was adapted. We evaluated corresponding breathing curves acquired during DIBH and 4DCT scans of altogether 70 patients using various stability metrics. Results: The various surrogate systems showed consistent table sag measurements below 4 mm, even under loads up to 130 kg, compared to a reference scan conducted without additional weight. Higher weight loads were related to steeper table sag fall-offs towards the deepest table position. For DIBH CT scans, the visual guidance was heavily affected by artifacts. This resulted in breathing threshold limits, which could not be achieved by 48% (n = 21) of the, respectively, examined patients. Using the new calibration workflow, the baseline drift was compensated better and 90% (n = 20) of the addressed patients stayed within the thresholds. The evaluated table sag in clinical 4DCT scans (n = 29) stayed below 3 mm compared to the non-weighted situation. Conclusion: Table movement and sag can impact breathing curves recorded by different surrogate systems. Correcting table movement and sag artifacts is crucial for reliable breathing curve acquisition in respiratory-guided CT.
CRIS-Team Scopus Importer:2024-12-13
Keywords: motion artifacts; respiratory motion; respiratory-guided CT; surrogate system; table sag

Investigating the impact of breast positioning control on physical treatment parameters in multi-catheter breast brachytherapy - Karius, Andre; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer; Bert, Christoph (Strahlentherapie und Onkologie, 2023)
Purpose: To assess the effects of a workflow for reproducible patient and breast positioning on implant stability during high-dose-rate multi-catheter breast brachytherapy. Methods: Thirty patients were treated with our new positioning control workflow. Implant stability was evaluated based on a comparison of planning-CTs to control-CTs acquired halfway through the treatment. To assess geometric stability, button–button distance variations as well as Euclidean dwell position deviations were evaluated. The latter were also quantified within various separated regions within the breast to investigate the location-dependency of implant alterations. Furthermore, dosimetric variations to target volume and organs at risk (ribs, skin) as well as isodose volume changes were analyzed. Results were compared to a previously treated cohort of 100 patients. Results: With the introduced workflow, the patient fraction affected by button–button distance variations > 5 mm and by dwell position deviations > 7 mm were reduced from 37% to 10% and from 30% to 6.6%, respectively. Implant stability improved the most in the lateral to medial breast regions. Only small stability enhancements were observed regarding target volume dosimetry, but the stability of organ at risk exposure became substantially higher. D0.2ccm skin dose variations > 12.4% and D0.1ccm rib dose variations > 6.7% were reduced from 11% to 0% and from 16% to 3.3% of all patients, respectively. Conclusion: Breast positioning control improved geometric and dosimetric implant stability for individual patients, and thus enhanced physical plan validity in these cases.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Adaptive brachytherapy; Computed tomography; Implant stability; Treatment quality; Treatment re-planning

Ion beam tracking using ultrasound motion detection - Prall, M.; Kaderka, R.; Saito, N.; Graeff, Christian; Bert, Christoph; Durante, Marco; Parodi, K.; Schwaab, J.; Sarti, C.; Jenne, J. (Medical Physics, 2014)
The use of motion mitigation techniques such as tracking and gating in particle therapy requires real-time knowledge of tumor position with millimeter precision. The aim of this phantom-based study was to evaluate the option of diagnostic ultrasound (US) imaging (sonography) as real-time motion detection method for scanned heavy ion beam irradiation of moving targets.For this pilot experiment, a tumor surrogate was moved inside a water bath along two-dimensional trajectories. A rubber ball was used for this purpose. This ball was moved by a robotic arm in two dimensions lateral to the heavy ion beam. Trajectories having a period of 3 s and peak to peak amplitude of 20 mm were used. Square radiation fields of[Formula: see text] were irradiated on radiosensitive films with a 200 MeV/u beam of calcium ions having a FWHM of 6 mm. Pencil beam scanning and beam tracking were employed. The films were attached on the robotic arm and thus moved with the rubber ball. The position of the rubber ball was continuously measured by a US tracking system (Mediri GmbH, Heidelberg) and sent to the GSI therapy control system (TCS). This position was used as tracking vector. Position reconstruction from the US tracking system and data communication introduced a delay leading to a position error of several millimeters. An artificial neural network (ANN) was implemented in the TCS to predict motion from US measurements and thus to compensate for the delay.Using ANN delay compensation and large motion amplitudes, the authors could produce irradiation patterns with a few percent inhomogeneity and about 1 mm geometrical conformity.This pilot experiment suggests that diagnostic US should be further investigated as dose-free, high frame-rate, and model-independent motion detection method for scanning heavy ion beam irradiation of moving targets.
EVALuna2:18309

Ion therapy of prostate cancer: daily rectal dose reduction by application of spacer gel - Rucinski, Antoni; Brons, Stephan; Richter, Daniel; Habl, Gregor; Debus, Juergen; Bert, Christoph; Haberer, Thomas; Jaekel, Oliver (Radiation Oncology, 2015)
Ion beam therapy represents a promising approach to treat prostate cancer, mainly due to its high conformity and radiobiological effectiveness. However, the presence of prostate motion, patient positioning and range uncertainties may deteriorate target dose and increase exposure of organs at risk. Spacer gel injected between prostate and rectum may increase the safety of prostate cancer (PC) radiation therapy by separating the rectum from the target dose field. The dosimetric impact of the application of spacer gel for scanned carbon ion therapy of PC has been analyzed at Heidelberg Ion-Beam Therapy Center (HIT).The robustness of ion therapy treatment plans was investigated by comparison of two data sets of patients treated with and without spacer gel. A research treatment planning system for ion therapy was used for treatment plan optimization and calculation of daily dose distributions on 2 to 9 Computed Tomography (CT) studies available for each of the 19 patients. Planning and daily dose distributions were analyzed with respect to target coverage, maximal dose to the rectum (excluding 1 ml of the greatest dose; Dmax-1 ml) and the rectal volume receiving dose greater than 90% of prescribed target dose (V90Rectum), respectively.The application of spacer gel did substantially diminish rectum dose. Dmax-1 ml on the treatment planning CT was on average reduced from 100.0 ± 1.0% to 90.2 ± 4.8%, when spacer gel was applied. The robustness analysis performed with daily CT studies demonstrated for all analyzed patient cases that application of spacer gel results in a decrease of the daily V90Rectum index, which calculated over all patient cases and CT studies was 10.2 ± 10.4 [ml] and 1.1 ± 2.1 [ml] for patients without and with spacer gel, respectively.The dosimetric benefit of increasing the distance between prostate and rectum using spacer gel for PC treatment with carbon ion beams has been quantified. Application of spacer gel substantially reduced rectal exposure to high treatment dose and, therefore, can reduce the hazard of rectal toxicity in ion beam therapy of PC. The results of this study enable modifications of the PC ion therapy protocol such as dose escalation or hypofractionation.
EVALuna2:18312

Is adaptive treatment planning in multi-catheter interstitial breast brachytherapy necessary? - Kallis, Karoline; Ziegler, Marc; Lotter, Michael; Kreppner, Stephan; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2019)
Purpose: For 55 patients treated with interstitial multi-catheter breast brachytherapy the need for adaptive treatment planning was assessed. Methods and materials: For all patients a treatment planning computed tomography (CT) and a follow-up CT were acquired and used for the retrospective evaluation. Keeping dwell time and dwell positions constant, the treatment plan assessed directly after catheter implantation was compared to the situation 48 h after implantation. Both manual catheter reconstructions, based on the planning and follow-up CT, were rigid registered to each other and the resulting deviations analyzed, like the difference between corresponding dwell positions (ΔDP) or the discrete Fréchet distance. Further, the dosimetric changes, e.g., coverage index (ΔCI), conformal index (ΔCOIN) and dose non-uniformity ratio (ΔDNR) were considered for a deformed planning target volume (PTV) and the rigid warped PTV structure. The PTV was deformed according to the vector field estimated between the two acquired CTs. Results: Over all patients with rigid aligned CTs a mean ΔDP, ΔCI, ΔCOIN and ΔDNR were determined to 2.41 ± 1.73 mm, 3.10 ± 3.17%, 0.009 ± 0.007 and 0.036 ± 0.040, respectively. Considering the deformed PTV ΔCI was estimated to 5.05 ± 4.14 %. Conclusion: In conclusion, in 4% of the cases re-planning would have been beneficial to ensure the planned dose delivery. Large PTV changes or large DP deviations were found to be the main reasons for dosimetric variations.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Adaptive treatment planning; Breast cancer; Deformable image registration; Interstitial brachytherapy

Is model-based dose calculation based on cone-beam computed tomography suitable for adaptive treatment planning in brachytherapy? - Karius, Andre; Shariff, Maya; Schaller, Sabrina; Lotter, Michael; Strnad, Vratislav; Lackner, Niklas; Fietkau, Rainer; Bert, Christoph; Merten, Ricarda; Schweizer, Claudia (Strahlentherapie und Onkologie, 2024)
Background and purpose: Model-based dose calculation considering tissue compositions is increasingly being investigated in brachytherapy. The aim of this study was to assess the suitability of modern cone-beam computed tomography (CBCT) imaging compared to conventional computed tomography (CT) scans for this purpose. Materials and methods: By means of a phantom study, we evaluated the CT numbers and electron densities measured using a modern CBCT device as well as a conventional CT scanner for various materials. Based on this, we compared dose calculations (using the TG-43 formalism as well as model-based collapsed cone calculations assuming uniform materials [ACEuniform] and considering CT numbers [ACECT#]) on planning CTs and control CBCTs for patients with cervical and breast cancer as well as phantom-simulated skin cancer cases. Assessing dosimetric deviations between the planning CTs and control CBCTs acquired during the treatment course served to estimate interfractional implant variations. Results: The comparison of ACEuniform–ACECT# deviations between planning CTs and control CBCTs revealed no statistically significant difference for almost all examined dose parameters. Dosimetric deviations between model-based dose calculations and TG-43 were partly significant but of small magnitude (< 10 cGy per fraction). Interfractional dosimetric variations were substantially larger than the dosimetric differences found between the various dose calculation procedures. Conclusion: Model-based dose calculation based on modern CBCT imaging was suitable. However, the found differences between these calculations and the TG-43 formalism should be investigated in dose–outcome analyses. The observed interfractional dosimetric variations revealed the importance of performing treatment quality assurance.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Adaptive radiotherapy; Brachytherapy; Breast cancer; Cervical cancer; Model-based dose calculation

Localization of reference points in electromagnetic tracking data and their application for treatment error detection in interstitial breast brachytherapy - Dürrbeck, Christopher; Schuster, Sabrina; Sauer, Birte; Abu-Hossin, Nadin; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Medical Physics, 2023)
Background: Electromagnetic tracking (EMT) is a promising technology that holds great potential to advance patient-specific pre-treatment verification in interstitial brachytherapy (iBT). It allows easy determination of the implant geometry without line-of-sight restrictions and without dose exposure to the patient. What it cannot provide, however, is a link to anatomical landmarks, such as the exit points of catheters or needles on the skin surface. These landmarks are required for the registration of EMT data with other imaging modalities and for the detection of treatment errors such as incorrect indexer lengths, and catheter or needle shifts. Purpose: To develop an easily applicable method to detect reference points in the positional data of the trajectory of an EMT sensor, specifically the exit points of catheters in breast iBT, and to apply the approach to pre-treatment error detection. Methods: Small metal objects were attached to catheter fixation buttons that rest against the breast surface to intentionally induce a local, spatially limited perturbation of the magnetic field on which the working principle of EMT relies. This perturbation can be sensed by the EMT sensor as it passes by, allowing it to localize the metal object and thus the catheter exit point. For the proof-of-concept, different small metal objects (magnets, washers, and bushes) and EMT sensor drive speeds were used to find the optimal parameters. The approach was then applied to treatment error detection and validated in-vitro on a phantom. Lastly, the in-vivo feasibility of the approach was tested on a patient cohort of four patients to assess the impact on the clinical workflow. Results: All investigated metal objects were able to measurably perturb the magnetic field, which resulted in missing sensor readings, that is two data gaps, one for the sensor moving towards the tip end and one when retracting from there. The size of the resulting data gaps varied depending on the choice of gap points used for calculation of the gap size; it was found that the start points of the gaps in both directions showed the smallest variability. The median size of data gaps was ⩽8 mm for all tested materials and sensor drive speeds. The variability of the determined object position was ⩽0.5 mm at a speed of 1.0 cm/s and ⩽0.7 mm at 2.5 cm/s, with an increase up to 2.3 mm at 5.0 cm/s. The in-vitro validation of the error detection yielded a 100% detection rate for catheter shifts of ≥2.2 mm. All simulated wrong indexer lengths were correctly identified. The in-vivo feasibility assessment showed that the metal objects did not interfere with the routine clinical workflow. Conclusions: The developed approach was able to successfully detect reference points in EMT data, which can be used for registration to other imaging modalities, but also for treatment error detection. It can thus advance the automation of patient-specific, pre-treatment quality assurance in iBT.
CRIS-Team Scopus Importer:2023-07-28
Keywords: brachytherapy; electromagnetic tracking; error detection; quality assurance

Longitudinal Spread Analysis of Patients with Glioblastoma: high Prevalence of discontinuous Tumor Foci with no strong Relation to the Fibrous Tract System - Schmitter, Charlotte; Weissmann, Thomas; Mansoorian, Sina; Lettmaier, Sebastian; Semrau, Sabine; Schmidt, Manfred; Heiß, Rafael; Frey, Benjamin; Bert, Christoph; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Low-dose-rate Prostate Brachytherapy: Characterization of Seeds Dynamics within the Prostate - Karius, Andre; Lotter, M.; Kreppner, Stephan; Lubgan, Dorota; Grigo, Johanna; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Low- vs. high-dose radiotherapy in Graves’ ophthalmopathy: a retrospective comparison of long-term results - Weissmann, Thomas; Lettmaier, Sebastian; Donaubauer, Anna-Jasmina; Bert, Christoph; Schmidt, Manfred; Kruse, Friedrich; Ott, Oliver; Hecht, Markus; Fietkau, Rainer; Frey, Benjamin; Putz, Florian (Strahlentherapie und Onkologie, 2021)
Purpose: Radiotherapy represents an effective treatment option in Graves’ ophthalmopathy (GO), leading to palliation of clinical symptoms. However, there are only a limited number of trials comparing the effectiveness of low- vs. high-dose radiotherapy. Methods: We analyzed 127 patients treated with radiotherapy for stage 3/4 GO (NOSPECS classification). Patients were treated with single doses of 2.0 Gy (cumulative dose 20 Gy) until 2007, afterwards a single dose of 0.8 Gy (cumulative dose 4.8 Gy) was applied. With a median follow-up-time of 9.0 years, the treatment efficacy (overall improvement, sense of eye pressure, lid edema, ocular motility, exophthalmos, subjective vision, and diplopia) and adverse effects were analyzed by a standardized survey. Results: Overall, 63.8% described improvement of symptoms after radiotherapy. No significant differences in overall treatment response and improvement of main outcome measures between low- or high-dose radiotherapy treatments are detectable, while low-dose radiotherapy leads significantly more often to retreatment (13.1% vs. 1.7%, p = 0.016). The main independent predictor of treatment response is the presence of lid edema (odds ratio, OR, 3.53; p = 0.006). Conclusion: At long-term follow-up, the majority of patients reported palliation of symptoms with limited adverse effects, suggesting clinical effectiveness of radiotherapy for amelioration of GO symptoms independent of low- or high-dose radiotherapy.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Exophthalmos; Graves’ ophthalmopathy; Low dose radiation therapy; Radiotherapy; Thyroid eye disease

Magnetic resonance imaging for brain stereotactic radiotherapy - A review of requirements and pitfalls - Putz, Florian; Mengling, Veit; Perrin, Rosalind; Masitho, Siti; Weissmann, Thomas; Roesch, Johannes; Bäuerle, Tobias; Janka, Rolf Matthias; Uder, Michael; Amarteifio, Patrick; Doussin, Sylvain; Schmidt, Manuel; et al. (Strahlentherapie und Onkologie, 2020)
Due to its superior soft tissue contrast, magnetic resonance imaging (MRI) is essential for many radiotherapy treatment indications. This is especially true for treatment planning in intracranial tumors, where MRI has a long-standing history for target delineation in clinical practice. Despite its routine use, care has to be taken when selecting and acquiring MRI studies for the purpose of radiotherapy treatment planning. Requirements on MRI are particularly demanding for intracranial stereotactic radiotherapy, where accurate imaging has a critical role in treatment success. However, MR images acquired for routine radiological assessment are frequently unsuitable for high-precision stereotactic radiotherapy as the requirements for imaging are significantly different for radiotherapy planning and diagnostic radiology. To assure that optimal imaging is used for treatment planning, the radiation oncologist needs proper knowledge of the most important requirements concerning the use of MRI in brain stereotactic radiotherapy. In the present review, we summarize and discuss the most relevant issues when using MR images for target volume delineation in intracranial stereotactic radiotherapy.
CRIS-Team WoS Importer:2020-04-10

Magnetic Resonance thermometry images of hyperthermia treatments of sarcomas for prediction of therapy responses-need of data reprocessing and cleaning - Khatun, Rupali; Hader, Michael; Schmidt, Manfred; Bert, Christoph; Wadepohl, Martin; Fietkau, Rainer; Ott, Jessica; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Management of organ motion in scanned ion beam therapy - Bert, Christoph; Herfarth, Klaus (Radiation Oncology, 2017)
Scanned ion beam therapy has special demands for treatment of intra-fractionally moving tumors such as lesions in lung or liver. Interplay effects between beam and organ motion can in those settings lead to under-dosage of the target volume. Dedicated treatment techniques such as gating or abdominal compression are required. In addition 4D treatment planning should be used to determine strategies for patient specific treatment planning such as an increased beam focus or the use of internal target volumes incorporating range changes.Several work packages of the Clinical Research Units 214 and 214/2 funded by the German Research Council investigated the management of organ motion in scanned ion beam therapy. A focus was laid on 4D treatment planning using TRiP4D and the development of motion mitigation strategies including their quality assurance. This review focuses on the activity in the second funding period covering adaptive treatment planning strategies, 4D treatment plan optimization, and the application of motion management in pre-clinical research on radiation therapy of cardiac arrhythmias.
EVALuna2:33030

Megavoltage intrafraction monitoring and position uncertainty in gimbaled markerless dynamic tumor tracking treatment of lung tumors - Serpa, Marco; Brandt, Tobias; Spohn, Simon K.B.; Rimner, Andreas; Bert, Christoph (Medical Physics, 2025)
Background: The clinical realization of markerless dynamic tumor tracking (MLDTT) has prompted a new paradigm shift to intrafraction imaging-based quality assurance (QA). During MLDTT treatment using a gimbaled accelerator, the megavoltage (MV) imager serves as an independent system to leverage real-time intrafraction monitoring. Soft-tissue feature tracking has shown promise for tumor localization in confined MV projections, but studies demonstrating its application in clinical MLDTT treatments are scarse. Purpose: To validate MV image-based dense soft-tissue feature tracking for intrafraction position monitoring of lung tumors during MLDTT stereotactic body radiotherapy (SBRT), and report on the resolved geometric uncertainty. Methods: Ten non-small cell lung cancer (NSCLC) patients underwent MLDTT-SBRT using a commercial gimbal-based system. During treatment, beam's-eye-view (BEV) projection images were captured at ∼3 frames s−1 (fps) using the electronic portal imaging device (EPID). MV sequences were streamed to a research workstation and processed off-line using a purpose-built algorithm, the soft-tissue feature tracker (SoFT). Both the tumor and dynamic field aperture position were automatically extracted in the pan and tilt directions of the gimbaled x-ray head, corresponding to the in-plane lateral and longitudinal direction of the imager, and compared to ground truth manual tracking. The success, percentage of fields producing an output, and performance of MV tracking under the presence/absence of anatomy-related obstruction and multi-leaf collimator (MLC) occlusion were quantified, including three-dimensional conformal (3DCRT) and step-and-shoot intensity modulated radiotherapy (IMRT) deliveries. In addition, the geometric uncertainty of MLDTT treatment was estimated as the difference between field aperture and target center position in the BEV. The standard deviation of systematic (Σ) and random (σ) errors were determined. Results: MV tracking was successful for 89.7% of (unmodulated) 3DCRT fields, as well as 82.4% of (modulated) control points (CPs) and subfields (SFs) for IMRT and field-in-field 3DCRT deliveries. The MV tracking accuracy was dependent on the traversed anatomy, tumor visibility, and occlusion by the MLC. The mean MV tracking accuracy was 1.2 mm (pan) and 1.4 mm (tilt), and a resultant 2D accuracy of 1.8 mm. The MV tracking performance within 2 mm was observed in 92.1% (pan) and 86.6% (tilt), respectively. The mean aperture-target positional uncertainty smaller than 3 mm/5 mm was observed in 94.4/97.9% (pan) and 89.6/96.7% (tilt) of the time. The group Σ and σ were 0.5 mm/0.8 mm (pan), and 0.7 mm/1.2 mm (tilt), compared to 0.3 mm/0.5 mm (pan), and 0.6 mm/0.9 mm (tilt) based on the manual ground truth. Conclusion: MV imaging coupled with the soft-tissue feature tracker algorithm constitutes a valuable non-invasive method for independent intrafraction surveillance. Tracking multiple features has shown the potential to improve position estimation, notwithstanding obstruction, and occlusion challenges, facilitating the quantification of the geometric uncertainty of MLDTT treatment.
CRIS-Team Scopus Importer:2025-04-18
Keywords: intrafraction monitoring; markerless dynamic tumor tracking; megavoltage tracking

Method for a motion model based automated 4D dose calculation - Ziegler, Marc; Brandt, Tobias; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (Physics in Medicine and Biology, 2019)
The Vero system can treat intra-fractionally moving tumors with gimbaled dynamic tumor tracking (DTT) by rotating the treatment beam so that it follows the motion of the tumor. However, the changes in the beam geometry and the constant breathing motion of the patient influence the dose applied to the patient. This study aims to perform a full 4D dose reconstruction for thirteen patients treated with DTT at the Vero system at the Universitätsklinikum Erlangen and investigates the temporal resolution required to perform an accurate 4D dose reconstruction. For all patients, a 4DCT was used to train a 4D motion model, which is able to calculate pseudo-CT images for arbitrary breathing phases. A new CT image was calculated for every 100 ms of treatment and a dose calculation was performed according to the current beam geometry (i.e. the rotation of the treatment beam at this moment in time) by rotating according to the momentary beam rotation, which is extracted from log-files. The resulting dose distributions were accumulated on the planning CT and characteristic parameters were extracted and compared. [Formula: see text]-evaluations of dose accumulations with different spatial-temporal resolutions were performed to determine the minimal required resolution. In total 173 700 dose calculations were performed. The accumulated 4D dose distributions show a reduced mean GTV dose of 0.77% compared to the static treatment plan. For some patients larger deviations were observed, especially in the presence of a poor 4DCT quality. The [Formula: see text]-evaluation showed that a temporal resolution of 500 ms is sufficient for an accurate dose reconstruction. If the tumor motion is regarded as well, a spatial-temporal sampling of 1400 ms and 2 mm yields accurate results, which reduces the workload by 84%.
CRIS-Team Scopus Importer:2019-11-26

Minutes of the General Meeting of the German Society for Medical Physics e.V. 2019 - Ladd, Mark E.; Bert, Christoph (Zeitschrift für Medizinische Physik, 2019)
EVALuna2:213674

Multicenter privacy-preserving model training for deep learning brain metastases autosegmentation - Huang, Yixing; Khodabakhshi, Zahra; Gomaa, Ahmed; Schmidt, Manuel; Fietkau, Rainer; Guckenberger, Matthias; Andratschke, Nicolaus; Bert, Christoph; Tanadini-Lang, Stephanie; Putz, Florian (Radiotherapy and Oncology, 2024)
OBJECTIVES: This work aims to explore the impact of multicenter data heterogeneity on deep learning brain metastases (BM) autosegmentation performance, and assess the efficacy of an incremental transfer learning technique, namely learning without forgetting (LWF), to improve model generalizability without sharing raw data. MATERIALS AND METHODS: A total of six BM datasets from University Hospital Erlangen (UKER), University Hospital Zurich (USZ), Stanford, UCSF, New York University (NYU), and BraTS Challenge 2023 were used. First, the performance of the DeepMedic network for BM autosegmentation was established for exclusive single-center training and mixed multicenter training, respectively. Subsequently privacy-preserving bilateral collaboration was evaluated, where a pretrained model is shared to another center for further training using transfer learning (TL) either with or without LWF. RESULTS: For single-center training, average F1 scores of BM detection range from 0.625 (NYU) to 0.876 (UKER) on respective single-center test data. Mixed multicenter training notably improves F1 scores at Stanford and NYU, with negligible improvement at other centers. When the UKER pretrained model is applied to USZ, LWF achieves a higher average F1 score (0.839) than naive TL (0.570) and single-center training (0.688) on combined UKER and USZ test data. Naive TL improves sensitivity and contouring accuracy, but compromises precision. Conversely, LWF demonstrates commendable sensitivity, precision and contouring accuracy. When applied to Stanford, similar performance was observed. CONCLUSION: Data heterogeneity (e.g., variations in metastases density, spatial distribution, and image spatial resolution across centers) results in varying performance in BM autosegmentation, posing challenges to model generalizability. LWF is a promising approach to peer-to-peer privacy-preserving model training.
EVALuna2:587588
Keywords: Continual learning; Learning without forgetting; Brain metastasis; Multicenter collaboration; Data privacy; Data heterogeneity

Multigating, a 4D optimized beam tracking in scanned ion beam therapy - Graeff, Christian; Constantinescu, Anna; Luechtenborg, Robert; Durante, Marco; Bert, Christoph (Technology in Cancer Research & Treatment, 2014)
The treatment of moving tumors with a scanned ion beam is challenging due to interplay effects and changing beam range. We propose multigating, as a method for 4D-treatment optimization and delivery. In 3D beam tracking, tracking vectors are added during delivery to beam spot positions based on the detected motion phase. This has the disadvantage of dose errors in case of complex motion patterns and an uncertain out-of-target dose distribution. In multigating, the motion phase for each beam spot is predefined, which allows to add the tracking vector prior to beam weight optimization on all motion phases. The synchronization of delivery and target motion is assured by fast gating. The feasibility of the delivery was shown in a film experiment and required only minor software modification to the treatment planning system. In a treatment planning study in 4 lung cancer patients, target coverage could be restored to the level of a static reference plan by multigating (V95 > 99%) but not by standard beam tracking (V95 < 95%). The conformity of the multigating plans was only slightly lower than those of the static plan, with a conformity number of 72.0% (median, range 64.6-76.6%) compared to 75.8% (70.8-81.5%) in spite of target motion of up to 22 mm. In conclusion, we showed the technical feasibility of multigating, a 4D-optimization and delivery method using scanned beams that allows for conformal and homogeneous dose delivery to moving targets also in case of complex motion.
EVALuna2:18193

New, mobile CBCT-System (ImagingRing m) for image-guided Brachytherapy - Quality Assurance - Karius, Andre; Strnad, Vratislav; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Noninvasive cardiac arrhythmia ablation with particle beams - Graeff, Christian; Bert, Christoph (Medical Physics, 2018)
Cardiac arrhythmias are a major health burden, associated with reduced quality of life and substantial morbidity and mortality. Current therapy includes moderately effective medication and catheter-based ablation of arrhythmogenic substrates in the heart. Catheter interventions frequently have to be repeated due to recurrent arrhythmia, can have rare but severe side-effects and are less suited especially for potentially lethal left ventricular tachycardia. Noninvasive alternatives are therefore warranted. Photon and ion beam radiotherapy has been studied in animal models and first patient cases have been reported using photons. Ion beams might offer the possibility to greatly reduce dose to surrounding healthy tissue, including critical cardiac substructures. Based on a recently conducted animal study, we report advantages and disadvantages of 4D-ion beam therapy, and strategies necessary for a clinical transition. Motion management of both respiration and heartbeat are discussed, as well as range uncertainty resulting from both regular motion and interfractional anatomic changes. Image guidance both in 3D and 4D has to be employed for a safe irradiation, but also population-based data on motion variability and time behavior of interfractional changes are necessary. Range verification could play a crucial role at least during development of clinical protocols. For clinical realization, it appears necessary to suppress or conformally mitigate the large respiratory motion to avoid normal tissue complications. Cardiac motion has to be incorporated into treatment planning, either through adequate range-considering internal margins or through more conformal strategies such as ECG-based gating or even 4D-optimization. The latter strategies would necessitate online 4D image guidance.
EVALuna2:36472

Novel technique for high-precision stereotactic irradiation of mouse brains - Hartmann, Josefin; Wölfelschneider, Jens; Stache, Christina; Buslei, R.; Derer, Anja; Schwarz, Martin; Bäuerle, Tobias; Fietkau, Rainer; Gaipl, Udo; Bert, Christoph; Hoelsken, A.; Frey, Benjamin (Strahlentherapie und Onkologie, 2016)
Small animal irradiation systems were developed for preclinical evaluation of tumor therapy closely resembling the clinical situation. Mostly only clinical LINACs are available, so protocols for small animal partial body irradiation using a conventional clinical system are essential. This study defines a protocol for conformal brain tumor irradiations in mice.CT and MRI images were used to demarcate the target volume and organs at risk. Three 6 MV photon beams were planned for a total dose of 10 fractions of 1.8 Gy. The mouse position in a dedicated applicator was verified by an X-ray patient positioning system before each irradiation. Dosimetric verifications (using ionization chambers and films) were performed. Irradiation-induced DNA damage was analyzed to verify the treatment effects on the cellular level.The defined treatment protocol and the applied fractionation scheme were feasible. The in-house developed applicator was suitable for individual positioning at submillimeter accuracy of anesthetized mice during irradiation, altogether performed in less than 10 min. All mice tolerated the treatment well. Measured dose values perfectly matched the nominal values from treatment planning. Cellular response was restricted to the target volume.Clinical LINAC-based irradiations of mice offer the potential to treat orthotopic tumors conformably. Especially with respect to lateral penumbra, dedicated small animal irradiation systems exceed the clinical LINAC solution.
EVALuna2:7317

Oligometastatic head and neck cancer: Which patients benefit from radical local treatment of all tumour sites? - Weissmann, Thomas; Höfler, Daniel; Hecht, Markus; Semrau, Sabine; Haderlein, Marlen; Filimonova, Irina; Frey, Benjamin; Bert, Christoph; Lettmaier, Sebastian; Mantsopoulos, Konstantinos; Iro, Heinrich; Fietkau, Rainer; et al. (Radiation Oncology, 2021)
Background: There is a large lack of evidence for optimal treatment in oligometastatic head and neck cancer and it is especially unclear which patients benefit from radical local treatment of all tumour sites. Methods: 40 patients with newly diagnosed oligometastatic head and neck cancer received radical local treatment of all tumour sites from 14.02.2008 to 24.08.2018. Primary endpoint was overall survival. Time to occurrence of new distant metastases and local control were evaluated as secondary endpoints as well as prognostic factors in univariate und multivariate Cox’s regression analysis. To investigate the impact of total tumour volume on survival, all tumour sites were segmented on baseline imaging. Results: Radical local treatment included radiotherapy in 90% of patients, surgery in 25% and radiofrequency ablation in 3%. Median overall survival from first diagnosis of oligometastatic disease was 23.0 months, 2-year survival was 48%, 3-year survival was 37%, 4-year survival was 24% and 5-year survival was 16%. Median time to occurrence of new distant metastases was 11.6 months with freedom from new metastases showing a tail pattern after 3 years of follow-up (22% at 3, 4- and 5-years post-treatment). In multivariate analysis, better ECOG status, absence of bone and brain metastases and lower total tumour volume were significantly associated with improved survival, whereas the number of metastases and involved organ sites was not. Conclusions: Radical local treatment in oligometastatic head and neck cancer shows promising outcomes and needs to be further pursued. Patients with good performance status, absence of brain and bone metastases and low total tumour volume were identified as optimal candidates for radical local treatment in oligometastatic head and neck cancer and should be considered for selection in future prospective trials.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Head and neck cancer; Local treatment; Oligometastatic disease; Radiotherapy; SBRT

On PTV definition for glioblastoma based on fiber tracking of diffusion tensor imaging data - Witulla, Barbara; Goerig, Nicole; Putz, Florian; Frey, Benjamin; Engelhorn, Tobias; Dörfler, Arnd; Uder, Michael; Fietkau, Rainer; Bert, Christoph; Laun, Frederik Bernd (PLoS ONE, 2020)
Radiotherapy (RT) is commonly applied for the treatment of glioblastoma multiforme (GBM). Following the planning target volume (PTV) definition procedure standardized in guidelines, a 20% risk of missing non-local recurrences is present. Purpose of this study was to evaluate whether diffusion tensor imaging (DTI)-based fiber tracking may be beneficial for PTV definition taking into account the prediction of distant recurrences. 56 GBM patients were examined with magnetic resonance imaging (MRI) including DTI performed before RT after resection of the primary tumor. Follow-up MRIs were acquired in three month intervals. For the seven patients with a distant recurrence, fiber tracking was performed with three algorithms and it was evaluated whether connections existed from the primary tumor region to the distant recurrence. It depended strongly on the used tracking algorithm and the used tracking parameters whether a connection was observed. Most of the connections were weak and thus not usable for PTV definition. Only in one of the seven patients with a recurring tumor, a clear connection was present. It seems unlikely that DTI-based fiber tracking can be beneficial for predicting distant recurrences in the planning of PTVs for glioblastoma multiforme.
CRIS-Team Scopus Importer:2020-01-21

On the implant stability in adaptive multi-catheter breast brachytherapy: Establishment of a decision-tree for treatment re-planning - Karius, Andre; Szkitsak, Juliane; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Schubert, Philipp; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2023)
Background and purpose: To assess implant stability and identify causes of implant variations during high-dose-rate multi-catheter breast brachytherapy. Materials and methods: Planning-CTs were compared to control-CTs acquired halfway through the treatment for 100 patients. For assessing geometric stability, Fréchet-distance and button-to-button distance changes of all catheters as well as variations of Euclidean distances and convex hulls of all dwell positions were determined. The CTs were inspected to identify the causes of geometric changes. Dosimetric effects were evaluated by target volume transfers and re-contouring of organs at risk. The dose non-uniformity ratio (DNR), 100% and 150% isodose volumes (V100 and V150), coverage index (CI), and organ doses were calculated. Correlations between the examined geometric and dosimetric parameters were assessed. Results: Fréchet-distance and dwell position deviations >2.5 mm as well as button-to-button distance changes >5 mm were detected for 5%, 2%, and 6.3% of catheters, but for 32, 17, and 37 patients, respectively. Variations occurred enhanced in the lateral breast and close to the ribs, e.g. due to different arm positions. Only small dosimetric effects with median DNR, V100, and CI variations of −0.01 ± 0.02, (−0.5 ± 1.3)ccm, and (–1.4 ± 1.8)% were observed in general. Skin dose exceeded recommended levels for 12 of 100 patients. Various correlations between geometric and dosimetric implant stability were found, based on which decision-tree regarding treatment re-planning was established. Conclusion: Multi-catheter breast brachytherapy shows a high implant stability in general, but considering skin dose changes is important. To increase implant stability for individual patients, we plan to investigate patient immobilization aids during treatments.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Adaptive brachytherapy; CT imaging; Imaging-based treatment planning; Implant stability; Multi-catheter breast brachytherapy; Treatment quality assurance

On the use of multi-dimensional scaling and electromagnetic tracking in high dose rate brachytherapy - Goetz, Th I.; Ermer, M.; Salas-Gonzalez, Diego; Kellermeier, Markus; Strnad, Vratislav; Bert, Christoph; Hensel, Bernhard; Tome, A. M.; Lang, E. W. (Physics in Medicine and Biology, 2017)
High dose rate brachytherapy affords a frequent reassurance of the precise dwell positions of the radiation source. The current investigation proposes a multi-dimensional scaling transformation of both data sets to estimate dwell positions without any external reference. Furthermore, the related distributions of dwell positions are characterized by uni-or bi-modal heavy-tailed distributions. The latter are well represented by α-stable distributions. The newly proposed data analysis provides dwell position deviations with high accuracy, and, furthermore, offers a convenient visualization of the actual shapes of the catheters which guide the radiation source during the treatment.
EVALuna2:33032

On the use of particle filters for electromagnetic tracking in high dose rate brachytherapy - Goetz, Th I.; Lahmer, Godehard; Brandt, Tobias; Kallis, Karoline; Strnad, Vratislav; Bert, Christoph; Hensel, Bernhard; Tome, A. M.; Lang, E. W. (Physics in Medicine and Biology, 2017)
Modern radiotherapy of female breast cancers often employs high dose rate brachytherapy, where a radioactive source is moved inside catheters, implanted in the female breast, according to a prescribed treatment plan. Source localization relative to the patient's anatomy is determined with solenoid sensors whose spatial positions are measured with an electromagnetic tracking system. Precise sensor dwell position determination is of utmost importance to assure irradiation of the cancerous tissue according to the treatment plan. We present a hybrid data analysis system which combines multi-dimensional scaling with particle filters to precisely determine sensor dwell positions in the catheters during subsequent radiation treatment sessions. Both techniques are complemented with empirical mode decomposition for the removal of superimposed breathing artifacts. We show that the hybrid model robustly and reliably determines the spatial positions of all catheters used during the treatment and precisely determines any deviations of actual sensor dwell positions from the treatment plan. The hybrid system only relies on sensor positions measured with an EMT system and relates them to the spatial positions of the implanted catheters as initially determined with a computed x-ray tomography.
EVALuna2:33033

Optimization of Single Voxel MR Spectroscopy Sequence Parameters and Data Analysis Methods for Thermometry in Deep Hyperthermia Treatments - Hartmann, Josefin; Gellermann, J.; Brandt, Tobias; Schmidt, M.; Pyatykh, S.; Hesser, J.; Ott, O.; Fietkau, Rainer; Bert, Christoph (Technology in Cancer Research & Treatment, 2016)
The difference in the resonance frequency of water and methylene moieties of lipids quantifies in magnetic resonance spectroscopy the absolute temperature using a predefined calibration curve. The purpose of this study was the investigation of peak evaluation methods and the magnetic resonance spectroscopy sequence (point-resolved spectroscopy) parameter optimization that enables thermometry during deep hyperthermia treatments.Different Lorentz peak-fitting methods and a peak finding method using singular value decomposition of a Hankel matrix were compared. Phantom measurements on organic substances (mayonnaise and pork) were performed inside the hyperthermia 1.5-T magnetic resonance imaging system for the parameter optimization study. Parameter settings such as voxel size, echo time, and flip angle were varied and investigated.Usually all peak analyzing methods were applicable. Lorentz peak-fitting method in MATLAB proved to be the most stable regardless of the number of fitted peaks, yet the slowest method. The examinations yielded an optimal parameter combination of 8 cm(3) voxel volume, 55 millisecond echo time, and a 90° excitation pulse flip angle.The Lorentz peak-fitting method in MATLAB was the most reliable peak analyzing method. Measurements in homogeneous and heterogeneous phantoms resulted in optimized parameters for the magnetic resonance spectroscopy sequence for thermometry.
EVALuna2:18362

Optimized raw data selection for artifact reduction of breathing controlled four-dimensional sequence scanning - Szkitsak, Juliane; Karius, Andre; Fernolendt, Susanne; Schubert, Philipp; Speer, Stefan; Fietkau, Rainer; Bert, Christoph; Hofmann, Christian (Physics and Imaging in Radiation Oncology, 2024)
Background and purpose: Even with most breathing-controlled four-dimensional computed tomography (4DCT) algorithms image artifacts caused by single significant longer breathing still occur, resulting in negative consequences for radiotherapy. Our study presents first phantom examinations of a new optimized raw data selection and binning algorithm, aiming to improve image quality and geometric accuracy without additional dose exposure. Materials and methods: To validate the new approach, phantom measurements were performed to assess geometric accuracy (volume fidelity, root mean square error, Dice coefficient of volume overlap) for one- and three-dimensional tumor motion trajectories with and without considering motion hysteresis effects. Scans without significantly longer breathing cycles served as references. Results: Median volume deviations between optimized approach and reference of at maximum 1% were obtained considering all movements. In comparison, standard reconstruction yielded median deviations of 9%, 21% and 12% for one-dimensional, three-dimensional, and hysteresis motion, respectively. Measurements in one- and three-dimensional directions reached a median Dice coefficient of 0.970 ± 0.013 and 0.975 ± 0.012, respectively, but only 0.918 ± 0.075 for hysteresis motions averaged over all measurements for the optimized selection. However, for the standard reconstruction median Dice coefficients were 0.845 ± 0.200, 0.868 ± 0.205 and 0.915 ± 0.075 for one- and three-dimensional as well as hysteresis motions, respectively. Median root mean square errors for the optimized algorithm were 30 ± 16 HU2 and 120 ± 90 HU2 for three-dimensional and hysteresis motions, compared to 212 ± 145 HU2 and 130 ± 131 HU2 for the standard reconstruction. Conclusions: The algorithm was proven to reduce 4DCT-related artifacts due to missing projection data without further dose exposure. An improvement in radiotherapy treatment planning due to better image quality can be expected.
CRIS-Team Scopus Importer:2024-07-26
Keywords: 4DCT; Artifacts; Hysteresis; Irregular breathing; Optimized raw data selection; Reconstruction

Paragangliomas of the Head and Neck: Local Control and Functional Outcome Following Fractionated Stereotactic Radiotherapy - Weissmann, Thomas; Lettmaier, Sebastian; Roesch, Johannes; Mengling, Veit; Bert, Christoph; Iro, Heinrich; Hornung, Joachim; Janka, Rolf Matthias; Semrau, Sabine; Fietkau, Rainer; Putz, Florian (American Journal of Clinical Oncology-Cancer Clinical Trials, 2019)
Objectives: To investigate local control and functional outcome following state-of-the-art fractionated stereotactic radiotherapy (FSRT) for paragangliomas of the head and neck. Methods: In total, 40 consecutive patients with paragangliomas of the head and neck received conventionally FSRT from 2003 to 2016 at the Department of Radiation Oncology of the University Hospital Erlangen. Local control, toxicities, and functional outcome were examined during follow-up. In total, 148 magnetic resonance imaging studies were subjected to longitudinal volumetric analysis using whole tumor segmentation in a subset of 22 patients. Results: A total of 80.0% (32/40) of patients received radiotherapy as part of their primary treatment. In 20.0% (8/40) of patients, radiation was used as salvage treatment after tumor recurrence in patients initially treated with surgery alone. The median dose applied was 54.0 Gy (interdecile range, 50.4 to 56.0 Gy) in single doses of 1.8 or 2 Gy. Local control was 100% after a median imaging follow-up of 52.2 months (range, 0.8 to 152.9 mo). The volumetric analysis confirmed sustained tumor control in a subset of 22 patients and showed transient enlargement (range, 129.6% to 151.2%) in 13.6% of cases (3/22). After a median volumetric follow-up of 24.6 months mean tumor volume had diminished to 86.1% compared with initial volume. In total, 52.5% (21/40) of patients reported improved symptoms after radiotherapy, 40% (16/40) observed no subjective change with only 7.5% (3/40) reporting significant worsening. Conclusions: State-of-the-art FSRT provides excellent control and favorable functional outcome in patients with paragangliomas of the head and neck. The volumetric analysis provides improved evidence for sustained tumor control.
CRIS-Team Scopus Importer:2019-10-22
Keywords: fractionated stereotactic radiotherapy; functional outcomes; paraganglioma; tumor control; volumetric analysis

Particle radiosurgery: a new frontier of physics in medicine - Bert, Christoph; Durante, Marco (Physica Medica, 2014)
Radiosurgery was introduced over half a century ago for treatment of intracranial lesions. In more recent years, stereotactic radiotherapy has rapidly advanced and is now commonly used for treatments of both cranial and extracranial lesions with high doses delivered in a few, down to a single fraction. The results of a workshop on Particle radiosurgery: A new frontier of physics in medicine held at Obergurgl, Austria during August 25-29 2013 are summarized in this issue with an overview presented in this paper. The focus was laid on particle radiosurgery but the content also includes current practice in x-ray radiosurgery and the overarching research in radiobiology and motion management for extracranial lesions. The results and discussions showed that especially research in radiobiology of high-dose charged-particles and motion management are necessary for the success of particle radiosurgery.
EVALuna2:18241

Patterns of lymph node involvement in prostate cancer patients presenting for pelvic and paraaortic stereotactic radiotherapy of nodal metastases - Filimonova, Irina; Weissmann, T.; Mansoorian, S.; Bert, Christoph; Frey, Benjamin; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Penile bulb sparing in prostate cancer radiotherapy: Dose analysis of an in-house MRI system to improve contouring - Boeckelmann, F.; Hammon, Matthias; Lettmaier, S.; Fietkau, Rainer; Bert, Christoph; Putz, Florian (Strahlentherapie und Onkologie, 2019)
ObjectiveThis study aimed to assess the reduction in dose to the penile bulb (PB) achieved by MRI-based contouring following drinking and endorectal balloon (ERB) instructions.Patients and methodsA total of 17prostate cancer patients were treated with intensity-modulated radiation therapy (IMRT) and interstitial brachytherapy (IBT). CT and MRI datasets were acquired back-to-back based on a65cm(3) air-filled ERB and drinking instructions. After rigid co-registration of the imaging data, the CT-based planning target volume (PTV) used for treatment planning was retrospectively compared to an MRI-based adaptive PTV and the dose to the PB was determined in each case. The adapted PTV encompassed acaudally cropped CT-based PTV which was defined on the basis of the MRI-based prostate contour plus an additional 5mm safety margin.ResultsIn the seven-field IMRT treatment plans, the MRI-based adapted PTV achieved mean (D-mean) and maximum (D-max) doses to the PB which were significantly lower (by 7.6Gy and 10.9Gy, respectively; p<0.05) than those of the CT-contoured PTV. For 6patients, the estimated PB D-max (seven-field IMRT and IBT) for the adapted PTV was <70Gy, whereas only 1patient fulfilled this criterium with the CT-based PTV.ConclusionMRI-based contouring and seven-field IMRT-based treatment planning achieved dose sparing to the PB. Whereas the comparison of MRI and CT contouring only relates to external beam radiotherapy (EBRT) sparing, considering EBRT and IBT shows the improvement in PB sparing for the total treatment. ZusammenfassungZielZiel war es, eine Dosisreduktion an der Peniswurzel auf Grundlage einer Magnetresonanztomographie-(MRT-)unterstutzten Konturierung unter Einhaltung eines Trink- und Rektalballonprotokolls (ERB) zu erreichen.Patienten und MethodenInsgesamt wurden 17Patienten mit Prostatakrebs intensitatsmoduliert bestrahlt (IMRT) und erhielten anschlie ss end eine interstitielle Brachytherapie (IBT). Computertomographie- (CT) und MRT-Datensatze wurden kurz nacheinander auf Basis eines 65-cm(3)-ERB- und Trinkprotokolls akquiriert und danach rigide registriert. In beiden Datensatzen wurde jeweils die Peniswurzeldosis bestimmt. Ein CT-basiertes Planungszielvolumen (PTV) wurde fur die Bestrahlungsplanung verwendet und retrospektiv mit einem MRT-basierten adaptiven PTV verglichen. Das adaptive PTV umfasst ein kaudal gekurztes CT-basiertes PTV, welches auf Grundlage einer MRT-basierten Prostatakontur und einem zusatzlichen 5-mm-Sicherheitsraum definiert wurde.ErgebnisseDas MRT-basierte adaptive PTV erzielte bei der 7-Felder-IMRT-Planung 7,6Gy (D-mean) und 10,9Gy (D-max) weniger Dosis an der Peniswurzel als das CT-konturierte PTV. Fur 6Patienten, geplant mit dem adaptiven PTV, war die abgeschatzte Maximaldosis D-max (7-Felder-IMRT+IBT) an der Peniswurzel <70Gy, wohingegen beim CT-basierten PTV nur 1Patient das Kriterium erfullte.SchlussfolgerungDie MRT-basierte Konturierung und die 7-Felder-IMRT-Planung reduzierte die Peniswurzeldosis. Die Gesamtdosis der Peniswurzel bestehend aus der 7-Felder-IMRT- und IBT-Planung zeigte sich reduziert, wobei die MRT- und CT- Konturierungsanalyse nur auf die externe 7-Felder-Bestrahlungsplanung basiert.
CRIS-Team WoS Importer:2019-02-21

Performance of gimbal-based dynamic tumor tracking for treating liver carcinoma - Ziegler, Marc; Brandt, Tobias; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (Radiation Oncology, 2018)
BACKGROUND: Since the introduction of tumor tracking in radiotherapy, it is possible to ensure a precise irradiation of moving targets. To follow the tumor movement, most systems rely on the detection of implanted markers and correlation models between the internal and external patient movement. This study reports the clinical workflow and first results of the dynamic tumor tracking (DTT) performance for patients with liver carcinoma at the Vero SBRT system of the University Hospital Erlangen regarding the detection of the internal marker and the changes of the determined correlation models. METHODS: So far 13 liver patients were treated with DTT. For each patient, two fiducial markers (FM), which are monitored with X-rays during treatment, were implanted in the vicinity of the tumor. All patients received a fraction dose of 4-6 Gy with 8 to 12 fractions. Treatment and patient data is evaluated by processing the acquired log-files of the DTT treatment. Based on this, the marker detection and the changes of the correlation model between the internal and external movement is investigated. RESULTS: The median treatment time was 19:42 min. During treatment a median of 173 X-ray stereoscopic images were acquired. The marker detection was successful in 64.6% of the images. The FM detection is independent of the relative angle between the marker and the imager, but shows a dependency on the average intensity surrounding the FM position within the kV images. The number of correlation models needed during treatment increases in the presence of baseline shifts. The comparison of the correlation models shows large differences in the internal-external correlation between the different models acquired for one patient. CONCLUSION: Thirteen liver patients were treated with DTT at the Vero SBRT system and the marker detection was analyzed. Furthermore, the importance of regularly monitoring the internal target motion could be shown, since the correlation between the internal and external motion changes considerably over the course of the treatment.
EVALuna2:36448

Performance of Makerless Tracking for Gimbaled Dynamic Tumor Tracking - Ziegler, Marc; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2019)
Background and Purpose: The purpose of this work is to report the workflow and the accuracy of the new markerless dynamic tumor tracking (MLDTT) method of the Vero 4DRT system introduced with ExacTrac 3.6.1. Material and Methods: Phantom measurements were performed to assess the accuracy of the MLDTT algorithm by using the QA-tool which is provided by the vendor. A patient breathing curve was used as the motion trajectory of the phantom and the target positions detected by the MLDTT algorithm were compared to the defined positions. Furthermore, eight patients have been treated with MLDTT between May 2018 and July 2019. A log-file analysis is used to evaluate MLDTT treatment data. Results: The accuracy of the MLDTT detection is 0.12 mm ± 0.12 mm, 0.12 mm ± 0.11 mm, 0.20 mm ± 0.21 mm for the x-, y-, z-direction, respectively. These values are comparable to the accuracy of marker based DTT at the Vero system. The median treatment time was 21 min 34 seconds and 175 kV images were acquired during treatment for monitoring the target motion. Conclusion: The accuracy of the MLDTT algorithm is comparable to the marker based approach and the accuracy reported for the XSight Lung of the CyberKnife. Eight patients were treated successfully using MLDTT and the treatment times are comparable to a standard DTT treatment.
CRIS-Team Scopus Importer:2019-12-27
Keywords: NSCLC; Real-time monitoring; Stereotactic body radiation therapy; Tumor Tracking

Performance of Marker-less Tracking for Gimbaled Dynamic Tumor Tracking - Ziegler, Marc; Lettmaier, S.; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Permanent LDR prostate brachytherapy: Comprehensive characterization of seed-dynamics within the prostate on a seed-only level - Karius, Andre; Lotter, Michael; Kreppner, Stephan; Schaller, Verena; Lubgan, Dorota; Grigo, Johanna; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (Brachytherapy, 2022)
PURPOSE: Seed brachytherapy is a well-established treatment modality for prostate cancer. However, there is still a lack of profound characterizations of seed motions within the prostate. We assessed these dynamics between day 0 and day 30 of brachytherapy. METHODS: We considered 45 patients with 2408 implanted seeds, and performed a 1:1 assignment between their positions on post-plan CT (nominal day 30) and intraoperative ultrasound (day 0). Geometric seed arrangement changes were measured for each patient and the entire collective. The impact of seed strand-lengths and implant regions was investigated. Correlations with patient characteristics were evaluated. We determined corresponding dosimetric effects by calculating common dose metrics. RESULTS: We found a median seed displacement of 4.3 mm [interquartile range: 3.1–6.9 mm], occurring preferentially in superior-inferior direction. Single and double strands moved significantly stronger than strands of higher lengths. Seed dynamics was more pronounced in base (5.6 mm [3.7–10.7 mm]) and apex (6.5 mm [4.1–15.0 mm]) than in the mid-gland (3.8 mm [2.7–5.0 mm]), and less pronounced in peripheral (4.3 mm [3.0–6.7 mm]) than in urethra-near (5.5 mm [3.5–10.7 mm]) regions. Correlations of seed dynamics with prostate volume changes and the number of implanted seeds and needles were found. D90 (dose that 90% of the prostate receives) varied by a median of 3 Gy [-6 to 15 Gy] between treatment plan and post-plan, but >40 Gy for individual patients. CONCLUSIONS: Reducing seed dynamics is important to ensure a high treatment quality. For this, strands containing ≥3 seeds may be useful, implantations in base-, apex-, and urethra-near zone should be avoided, and the number of needles and seeds may be minimized where possible.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Adaptive Brachytherapy; Low-dose-rate prostate brachytherapy; Prostate Cancer; Seed brachytherapy; Seed displacements

Plan robustness analysis for threshold determination of SGRT-based intrafraction motion control in 3DCRT breast cancer radiation therapy - Sauer, Tim-Oliver; Stillkrieg, Willy; Ott, Oliver; Fietkau, Rainer; Bert, Christoph (Radiation Oncology, 2023)
Purpose: The goal of this study was to obtain maximum allowed shift deviations from planning position in six degrees of freedom (DOF), that can serve as threshold values in surface guided radiation therapy (SGRT) of breast cancer patients. Methods: The robustness of conformal treatment plans of 50 breast cancer patients against 6DOF shifts was investigated. For that, new dose distributions were calculated on shifted computed tomography scans and evaluated with respect to target volume and spinal cord dose. Maximum allowed shift values were identified by imposing dose constraints on the target volume dose coverage for 1DOF, and consecutively, for 6DOF shifts using an iterative approach and random sampling. Results: Substantial decreases in target dose coverage and increases of spinal cord dose were observed. Treatment plans showed highly differing robustness for different DOFs or treated area. The sensitivity was particularly high if clavicular lymph nodes were irradiated, for shifts in lateral, vertical, roll or yaw direction, and showed partly pronounced asymmetries. Threshold values showed similar properties with an absolute value range of 0.8 mm to 5 mm and 1.4° to 5°. Conclusion: The robustness analysis emphasized the necessity of taking differences between DOFs and asymmetrical sensitivities into account when evaluating the dosimetric impact of position deviations. It also highlighted the importance of rotational shifts, especially if clavicular lymph nodes were irradiated. A practical approach of determining 6DOF shift limits was introduced and a set of threshold values applicable for SGRT based patient motion control was identified.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Intrafraction motion; Probabilistic dose evaluation; Surface guided radiation therapy; Treatment plan robustness

Possibilities of a Seed Control after the Implantation by using MRI and Deep Learning-based QSM Reconstruction - Grigo, Johanna; Karius, Andre; Hanspach, Jannis; Weissmann, Thomas; Laun, Frederik Bernd; Strnad, Vratislav; Putz, Florian; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Prerequisites for the clinical implementation of a markerless SGRT-only workflow for the treatment of breast cancer patients - Sauer, Tim-Oliver; Ott, Oliver; Lahmer, Godehard; Fietkau, Rainer; Bert, Christoph (Strahlentherapie und Onkologie, 2022)
Purpose: A markerless workflow for the treatment of breast cancer patients has been introduced and evaluated retrospectively. It includes surface-guided radiation therapy (SGRT)-only positioning for patients with small cone beam CT (CBCT) position corrections during the first five fractions. Prerequisites and the frequency of its clinical application were evaluated, as well as potential benefits in terms of treatment time and dose savings, the frequency of CBCT scans, and the accuracy of the positioning. Methods: A group of 100 patients treated with the new workflow on two Versa HD linacs has been compared to a matched control group of patients treated with the former workflow, which included prepositioning with skin markings and lasers, SGRT and daily CBCT. The comparison was based on the evaluation of logfiles. Results: Of the patients treated with the new workflow, 40% did not receive daily CBCT scans. This resulted in mean time savings of 97 s, 166 s and 239 s per fraction for the new workflow, for patients treated without daily CBCT and for SGRT-only fractions, respectively, when compared to the old workflow. Dose savings amounted to a weighted computed tomography dose index reduction of CTDIW = 2.56 cGy on average for normofractionated treatment and weekly CBCTs, while for patients not treated with daily CBCT, SGRT-based positioning accuracy was 5.2 mm for the mean translational magnitude, as evaluated by CBCT. Conclusion: For 40% of the patients, after five fractions with small CBCT corrections, the workflow could be changed to SGRT-only positioning with weekly CBCT. This leads to imaging dose and time savings and thus also reduced intrafraction motion, potentially increased patient throughput and patient comfort, while assuring appropriate positioning accuracy.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Breast neoplasms; Interfraction motion management; Intrafraction motion management; Markerless radiation therapy; Surface-guided radiation therapy

Principles of artificial intelligence in radiooncology - Huang, Yixing; Gomaa, Ahmed; Höfler, Daniel; Schubert, Philipp; Gaipl, Udo; Frey, Benjamin; Fietkau, Rainer; Bert, Christoph; Putz, Florian (Strahlentherapie und Onkologie, 2024)
Keywords: Artificial intelligence; Radiation Oncology; Deep learning

Process failure mode and effects analysis for external beam radiotherapy: Introducing a literature-based template and a novel action priority - Kornek, Dominik; Bert, Christoph (Zeitschrift für Medizinische Physik, 2024)
Purpose: The first aim of the study was to create a general template for analyzing potential failures in external beam radiotherapy, EBRT, using the process failure mode and effects analysis (PFMEA). The second aim was to modify the action priority (AP), a novel prioritization method originally introduced by the Automotive Industry Action Group (AIAG), to work with different severity, occurrence, and detection rating systems used in radiation oncology. Methods and materials: The AIAG PFMEA approach was employed in combination with an extensive literature survey to develop the EBRT-PFMEA template. Subsets of high-risk failure modes found through the literature survey were added to the template where applicable. Our modified AP for radiation oncology (RO AP) was defined using a weighted sum of severity, occurrence, and detectability. Then, Monte Carlo simulations were conducted to compare the original AIAG AP, the RO AP, and the risk priority number (RPN). The results of the simulations were used to determine the number of additional corrective actions per failure mode and to parametrize the RO AP to our department's rating system. Results: An EBRT-PFMEA template comprising 75 high-risk failure modes could be compiled. The AIAG AP required 1.7 additional corrective actions per failure mode, while the RO AP ranged from 1.3 to 3.5, and the RPN required 3.6. The RO AP could be parametrized so that it suited our rating system and evaluated severity, occurrence, and detection ratings equally to the AIAG AP. Conclusions: An adjustable EBRT-PFMEA template is provided which can be used as a practical starting point for creating institution-specific templates. Moreover, the RO AP introduces transparent action levels that can be adapted to any rating system.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Action priority (AP); External beam radiation therapy (EBRT); Process failure mode and effects analysis (PFMEA); Prospective risk assessment; Template

QAMaster: A new software framework for phantom-based computed tomography quality assurance - Karius, Andre; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2022)
The regular evaluation of imaging performance of computed tomography (CT) scanners is essential for CT quality assurance. For automation of this process, the software QAMaster was developed at the Universitätsklinikum Erlangen, which provides based on CT scans of the CatPhan® 504 (The Phantom Laboratory, Salem, USA) automated image quality analysis and documentation by evaluating CT number accuracy, spatial linearity, uniformity, contrast-noise-ratio, spatial resolution, noise, and slice thickness. Dose assessment is supported by calculations of the weighted computed tomography dose index (CTDIw) and weighted cone beam dose index (CBDIw). QAMaster was tested with CatPhan® 504 scans and compared to manual evaluations of these scans, whereby high consistency of the respective results was observed. The CT numbers, spatial linearity, uniformity, contrast-noise-ratio, noise, and slice thickness deviated by only (0.13 ± 0.25) HU, (0.02 ± 0.05) mm, (−0.01 ± 0.03)%, 0.8 ± 1.8, (0.131 ± 0.05) HU, and (0.004 ± 0.005) mm between both evaluations, respectively. The QAMaster results for spatial resolution did not differ significantly (p = 0.34) from the CatPhan® 504 based manual resolution assessment. Dose computations were fully consistent between QAMaster and manual calculations. Thus, QAMaster proved to be a comprehensive and functional software for performing an automated CT quality assurance routine. QAMaster will be open-source after its release.
CRIS-Team Scopus Importer:2022-03-25
Keywords: computed tomography; cone beam computed tomography; image quality assurance; phantom-based software framework

Quality assurance and long-term stability of a novel 3-in-1 X-ray system for brachytherapy - Karius, Andre; Szkitsak, Juliane; Boronikolas, Vasilios; Fietkau, Rainer; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2022)
Purpose A novel, mobile 3-in-1 X-ray system featuring radiography, fluoroscopy, and cone-beam computed tomography (CBCT) has been launched for brachytherapy recently. Currently, there is no quality assurance (QA) procedure explicitly applicable to this system equipped with innovative technologies such as dynamic jaws and motorized lasers. We developed a dedicated QA procedure and, based on its performance for a duration of 6 months, provide an assessment of the device's stability over time. Methods With the developed QA procedure, we assessed the system's planar and CBCT-imaging performance by investigating geometric accuracy, CT-number stability, contrast-noise-ratio, uniformity, spatial resolution, low-contrast detectability, dynamic range, and X-ray exposure using dedicated phantoms. Furthermore, we evaluated geometric stability by using the flexmap-approach and investigated the device's laser- and jaw-positioning accuracy with an in-house test phantom. CBCT- and planar-imaging protocols for pelvis, breast, and abdomen imaging were examined. Results Planar- and CBCT-imaging performances were widely stable with a geometric accuracy <= 1 mm, CT-number stability of up to 46 HU, and uniformity variations of up to 48 HU over time. For planar imaging, low-contrast detectability and dynamic range exceeded current recommendations. Although geometric stability was considered tolerable, partly substantial positioning inaccuracies of up to more than 120 mm and -13 mm were obtained for lasers and jaws, respectively. X-ray exposure showed small variations of <= 0.56 mu Gy and <= 0.76 mGy for planar- and CBCT-imaging, respectively. The conductance of the QA procedure allowed a smooth evaluation of the system's overall performance. Conclusion We developed a QA workflow for a novel 3-in-1 X-ray system allowing to assess the device's imaging and hardware performance. The system showed in general a reasonable imaging performance and stability over time, whereas improvements regarding laser and jaw accuracy are strictly required.
CRIS-Team WoS Importer:2022-07-29

Quality Assurance by electromagnetic Tracking in Interstitial multi-catheter HDR Brachytherapy Using a hybrid Afterloading System - Kallis, Karoline; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (2018)
EVALuna2:36475

Quality assurance for dynamic tumor tracking - Witulla, Barbara; Ziegler, Marc; Brandt, Tobias; Prasetio, Heru; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2021)
The purpose of this work was to develop a treatment plan verification routine for a linear accelerator dedicated to SBRT treatments with gimbal based dynamic tumor tracking using three commercially available phantoms. The accelerator system has two special features: It operates with a rotation of the ring shaped gantry instead of a couch rotation and target motion can be compensated for via a gimbal system (dynamic tumor tracking, DTT). DTT plans were each measured with the three different phantoms. Afterwards the measured dose distribution was compared with the calculated dose distribution via global Gamma Index analysis (3 mm / 3%, threshold: 10%). The global gamma pass rates were on average (93.5 ± 7.2) % for ArcCHECK, (98.0 ± 2.6) % for OCTAVIUS® 4D and (98.4 ± 4.2) % for MatriXX Evolution. All three systems could be used for quality assurance with ring rotations and DTT, however, each with limitations.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Intensity modulated radiation therapy; quality assurance; Stereotactic body radiation therapy; Tumor Tracking

Quality assurance for interstitial brachytherapy using an EMT system integrated into an afterloader - Kallis, Karoline; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (2018)
EVALuna2:36479

Quality assurance guidelines for superficial hyperthermia clinical trials: I. Clinical requirements - Trefna, Hana Dobsicek; Crezee, Hans; Schmidt, Manfred; Marder, Dietmar; Lamprecht, Ulf; Ehmann, Michael; Hartmann, Josefin; Nadobny, Jacek; Gellermann, Johanna; Van Holthe, Netteke; Ghadjar, Pirus; Lomax, Nicoletta; et al. (International Journal of Hyperthermia, 2017)
Quality assurance guidelines are essential to provide uniform execution of clinical trials and treatment in the application of hyperthermia. This document provides definitions for a good hyperthermia treatment and identifies the clinical conditions where a certain hyperthermia system can or cannot adequately heat the tumour volume. It also provides brief description of the characteristics and performance of the current electromagnetic (radiative and capacitive), ultrasound and infra-red heating techniques. This information helps to select the appropriate heating technique for the specific tumour location and size, and appropriate settings of the water bolus and thermometry. Finally, requirements of staff training and documentation are provided. The guidelines in this document focus on the clinical application and are complemented with a second, more technical quality assurance document providing instructions and procedure to determine essential parameters that describe heating properties of the applicator for superficial hyperthermia. Both sets of guidelines were developed by the ESHO Technical Committee with participation of senior STM members and members of the Atzelsberg Circle.
EVALuna2:33043

Quality Assurance in interstitial multi-catheter Brachytherapy using an electromagnetic Tracking System - Abu-Hossin, Nadin; Kallis, Karoline; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Quality assurance of a breathing controlled four-dimensional computed tomography algorithm - Szkitsak, Juliane; Karius, Andre; Hofmann, Christian; Fietkau, Rainer; Bert, Christoph; Speer, Stefan (Physics and Imaging in Radiation Oncology, 2022)
Background & purpose: Four-dimensional computed tomography (4DCT) scans are standardly used for radiotherapy planning of tumors subject to respiratory motion. Based on online analysis and automatic adaption of scan parameters to the patient's individual breathing pattern, a new breathing-controlled 4DCT (i4DCT) algorithm attempts to counteract irregular breathing and thus prevent artifacts. The aim of this study was to perform an initial quality assurance for i4DCT. Material & methods: To validate the i4DCT algorithm, phantom measurements were performed to evaluate geometric accuracy (diameter, volume, eccentricity), image quality (dose-normalized contrast-noise-ratio, CT number accuracy), and correct representation of motion amplitude of simulated tumor lesions. Furthermore, the impact of patient weight and resulting table flexion on the measurements was investigated. Static three-dimensional CT (3DCT) scans were used as ground truth. Results: The median volume deviation magnitude between 4DCT and 3DCT was < 2% (<0.2 cm3). The volume differences ranged from –8% (–1.0 cm3) to 3% (0.4 cm3). Median tumor diameter deviation magnitudes were < 2% (<0.7 mm) for regular and < 3.5% (<1.0 mm) for irregular breathing. For eccentricity, a median deviation magnitude of < 0.05 for regular and < 0.08 for irregular breathing curves was found. The respiratory amplitude was represented with a median accuracy of < 0.5 mm. CT numbers and dose-normalized contrast-noise-ratio showed no clinically relevant difference between 4DCT and 3DCT. Table flexion proved to have no clinically relevant impact on geometric accuracy. Conclusions: The breathing-controlled algorithm provides in general good results regarding image quality, geometric accuracy, and correct depiction of motion amplitude for regular and irregular breathing.
CRIS-Team Scopus Importer:2022-07-22
Keywords: 4DCT; Quality assurance; Respiratory motion

Quality assurance of curved catheter paths in interstitial brachytherapy using a constructed phantom - Abu-Hossin, N.; Gulde, S.; Dürrbeck, Christopher; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-18

Quality requirements for MRI simulation in cranial stereotactic radiotherapy: a guideline from the German Taskforce “Imaging in Stereotactic Radiotherapy” - Putz, Florian; Bock, Michael; Schmitt, Daniela; Bert, Christoph; Blanck, Oliver; Ruge, Maximilian I.; Hattingen, Elke; Karger, Christian P.; Fietkau, Rainer; Grigo, Johanna; Schmidt, Manuel; Bäuerle, Tobias; et al. (Strahlentherapie und Onkologie, 2024)
Accurate Magnetic Resonance Imaging (MRI) simulation is fundamental for high-precision stereotactic radiosurgery and fractionated stereotactic radiotherapy, collectively referred to as stereotactic radiotherapy (SRT), to deliver doses of high biological effectiveness to well-defined cranial targets. Multiple MRI hardware related factors as well as scanner configuration and sequence protocol parameters can affect the imaging accuracy and need to be optimized for the special purpose of radiotherapy treatment planning. MRI simulation for SRT is possible for different organizational environments including patient referral for imaging as well as dedicated MRI simulation in the radiotherapy department but require radiotherapy-optimized MRI protocols and defined quality standards to ensure geometrically accurate images that form an impeccable foundation for treatment planning. For this guideline, an interdisciplinary panel including experts from the working group for radiosurgery and stereotactic radiotherapy of the German Society for Radiation Oncology (DEGRO), the working group for physics and technology in stereotactic radiotherapy of the German Society for Medical Physics (DGMP), the German Society of Neurosurgery (DGNC), the German Society of Neuroradiology (DGNR) and the German Chapter of the International Society for Magnetic Resonance in Medicine (DS-ISMRM) have defined minimum MRI quality requirements as well as advanced MRI simulation options for cranial SRT.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Brain metastases; DEGRO; DGMP; DGNC; DGNR; DS-ISMRM; Guideline; Meningioma; MRI simulation; Pituitary adenoma; Stereotactic radiosurgery; Stereotactic radiotherapy; Trigeminal neuralgia; Vestibular schwannoma

Quantification of an external motion surrogate for quality assurance in lung cancer radiation therapy - Wölfelschneider, Jens; Brandt, Tobias; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (BioMed Research International, 2014)
The purpose of this work was to validate the stability of the end exhale position in deep expiration breath hold (DEBH) technique for quality assurance in stereotactic lung tumor radiation therapy. Furthermore, a motion analysis was performed for 20 patients to evaluate breathing periods and baseline drifts based on an external surrogate. This trajectory was detected using stereo infrared (IR) cameras and reflective body markers. The respiratory waveform showed large interpatient differences in the end exhale position during irradiation up to 18.8 mm compared to the global minimum. This position depends significantly on the tumor volume. Also the baseline drifts, which occur mostly in posterior direction, are affected by the tumor size. Breathing periods, which depend mostly on the patient age, were in a range between 2.4 s and 7.0 s. Fifteen out of 20 patients, who showed a reproducible end exhale position with a deviation of less than 5 mm, might benefit from DEBH due to smaller planning target volumes (PTV) compared to free breathing irradiation and hence sparing of healthy tissue. Patients with larger uncertainties should be treated with more complex motion compensation techniques.
EVALuna2:18182

Quantification of pretherapeutic Changes in Brain Metastases before stereotactic Radiotherapy - Putz, Florian; Görnert, Caroline; Voigt, R.; Grigo, Johanna; Masitho, Siti; Reissig, L.; Huang, Yixing; Weissmann, Thomas; Mansoorian, Sina; Schmidt, M.; Semrau, Sabine; Bert, Christoph; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Real-Time Respiratory Motion Analysis Using 4-D Shape Priors - Wasza, Jakob; Fischer, Peter; Leutheuser, Heike; Oefner, Tobias; Bert, Christoph; Maier, Andreas; Hornegger, Joachim (IEEE Transactions on Biomedical Engineering, 2016)
Respiratory motion analysis based on range imaging (RI) has emerged as a popular means of generating respiration surrogates to guide motion management strategies in computer-assisted interventions. However, existing approaches employ heuristics, require substantial manual interaction, or yield highly redundant information. In this paper, we propose a framework that uses preprocedurally obtained 4-D shape priors from patient-specific breathing patterns to drive intraprocedural RI-based real-time respiratory motion analysis. As the first contribution, we present a shape motion model enabling an unsupervised decomposition of respiration induced high-dimensional body surface displacement fields into a low-dimensional representation encoding thoracic and abdominal breathing. Second, we propose a method designed for GPU architectures to quickly and robustly align our models to high-coverage multiview RI body surface data. With our fully automatic method, we obtain respiration surrogates yielding a Pearson correlation coefficient (PCC) of 0.98 with conventional surrogates based on manually selected regions on RI body surface data. Compared to impedance pneumography as a respiration signal that measures the change of lung volume, we obtain a PCC of 0.96. Using off-the-shelf hardware, our framework enables high temporal resolution respiration analysis at 50 Hz.
Keywords: Graphics processing unit (GPU); radiation therapy; range imaging (RI); respiratory motion

Recent advanced in Surface Guided Radiation Therapy - Freislederer, P.; Kügele, M.; Öllers, M.; Swinnen, A.; Sauer, Tim-Oliver; Bert, Christoph; Giantsoudi, D.; Corradini, S.; Batista, V. (Radiation Oncology, 2020)
The growing acceptance and recognition of Surface Guided Radiation Therapy (SGRT) as a promising imaging technique has supported its recent spread in a large number of radiation oncology facilities. Although this technology is not new, many aspects of it have only recently been exploited. This review focuses on the latest SGRT developments, both in the field of general clinical applications and special techniques.SGRT has a wide range of applications, including patient positioning with real-time feedback, patient monitoring throughout the treatment fraction, and motion management (as beam-gating in free-breathing or deep-inspiration breath-hold). Special radiotherapy modalities such as accelerated partial breast irradiation, particle radiotherapy, and pediatrics are the most recent SGRT developments.The fact that SGRT is nowadays used at various body sites has resulted in the need to adapt SGRT workflows to each body site. Current SGRT applications range from traditional breast irradiation, to thoracic, abdominal, or pelvic tumor sites, and include intracranial localizations.Following the latest SGRT applications and their specifications/requirements, a stricter quality assurance program needs to be ensured. Recent publications highlight the need to adapt quality assurance to the radiotherapy equipment type, SGRT technology, anatomic treatment sites, and clinical workflows, which results in a complex and extensive set of tests.Moreover, this review gives an outlook on the leading research trends. In particular, the potential to use deformable surfaces as motion surrogates, to use SGRT to detect anatomical variations along the treatment course, and to help in the establishment of personalized patient treatment (optimized margins and motion management strategies) are increasingly important research topics. SGRT is also emerging in the field of patient safety and integrates measures to reduce common radiotherapeutic risk events (e.g. facial and treatment accessories recognition).This review covers the latest clinical practices of SGRT and provides an outlook on potential applications of this imaging technique. It is intended to provide guidance for new users during the implementation, while triggering experienced users to further explore SGRT applications.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Deep-inspiration breath-hold; Intra-fractional motion mitigation; Motion management; Patient positioning; Patient safety; SGRT; Surface guided radiation therapy

Reduction of elective radiotherapy treatment volume in definitive treatment of locally advanced head and neck cancer—comparison of a prospective trial with a revised simulated contouring approach - Weissmann, Thomas; Speer, Stefan; Putz, Florian; Lettmaier, Sebastian; Schubert, Philipp; Shariff, Maya; Semrau, Sabine; Gostian, Antoniu-Oreste; Traxdorf, Maximilian; Müller, Sarina Katrin; Eckstein, Markus; Hautmann, Matthias; et al. (Journal of Clinical Medicine, 2021)
Definitive radiochemotherapy of locally advanced head and neck squamous cell cancer (HNSCC) achieves high locoregional tumor control rates; but is frequently associated with long-term toxicity. A future direction could be a de-escalation strategy focusing on treated volume rather than radiotherapy dose. This analysis evaluates radiotherapy dose and volume parameters of patients treated with a standard contouring approach in a clinical trial context compared with a revised volume-reduced contouring approach. In this case, 30 consecutive patients from the CheckRad-CD8 trial treated at a single study center were included in this analysis. Treatment toxicity and quality of life were assessed at the end of radiotherapy. Standard treatment plans (ST) following state of the art contouring guidelines that were used for patient treatment and volume reduced treatment plans (VRT) according to a revised simulated approach were calculated for each patient. Planning target volumes (PTV) and mean doses to 38 organs-at-risk structures were compared. At the end of radiotherapy patients reported high rates of mucositis; dysphagia and xerostomia. In addition; patient reported quality of life as assessed by the EORTC QLQ-HN35 questionnaire deteriorated. Comparing the two contouring approaches; the elective PTV_56 Gy and the high risk PTV_63 Gy (shrinking field) were significantly smaller in the VRT group. Significant reduction of mean dose to structures of the oral cavity; the larynx as well as part of the swallowing muscles and the submandibular glands was achieved in the simulated VRT-plan. Treatment de-intensification by reduction of the irradiated volume could potentially reduce treatment volume and mean doses to organs at risk. The proposed contouring approach should be studied further in the context of a clinical trial.
CRIS-Team Scopus Importer:2021-10-22
Keywords: De-intensification; Definitive treatment; Head neck cancer; Radiotherapy; Salivary glands; Swallowing function; Volume reduc-tion

Regional deep hyperthermia: impact of observer variability in CT-based manual tissue segmentation on simulated temperature distribution - Aklan, Bassim; Hartmann, Josefin; Zink, Diana; Siavooshhaghighi, Hadi; Merten, Ricarda; Putz, Florian; Ott, Oliver; Fietkau, Rainer; Bert, Christoph (Physics in Medicine and Biology, 2017)
The aim of this study was to systematically investigate the influence of the inter- and intra-observer segmentation variation of tumors and organs at risk on the simulated temperature coverage of the target. CT scans of six patients with tumors in the pelvic region acquired for radiotherapy treatment planning were used for hyperthermia treatment planning. To study the effect of inter-observer variation, three observers manually segmented in the CT images of each patient the following structures: fat, muscle, bone and the bladder. The gross tumor volumes (GTV) were contoured by three radiation oncology residents and used as the hyperthermia target volumes. For intra-observer variation, one of the observers of each group contoured the structures of each patient three times with a time span of one week between the segmentations. Moreover, the impact of segmentation variations in organs at risk (OARs) between the three inter-observers was investigated on simulated temperature distributions using only one GTV. The spatial overlap between individual segmentations was assessed by the Dice similarity coefficient (DSC) and the mean surface distance (MSD). Additionally, the temperatures T90/T10 delivered to 90%/10% of the GTV, respectively, were assessed for each observer combination. The results of the segmentation similarity evaluation showed that the DSC of the inter-observer variation of fat, muscle, the bladder, bone and the target was 0.68 ± 0.12, 0.88 ± 0.05, 0.73 ± 0.14, 0.91 ± 0.04 and 0.64 ± 0.11, respectively. Similar results were found for the intra-observer variation. The MSD results were similar to the DSCs for both observer variations. A statistically significant difference (p < 0.05) was found for T90 and T10 in the predicted target temperature due to the observer variability. The conclusion is that intra- and inter-observer variations have a significant impact on the temperature coverage of the target. Furthermore, OARs, such as bone and the bladder, may essentially influence the homogeneity of the simulated target temperature distribution.
EVALuna2:32876

Region of interest optimization for radiation therapy of breast cancer - Sauer, Tim-Oliver; Ott, Oliver; Lahmer, Godehard; Fietkau, Rainer; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2021)
Purpose: The goal of this study was to investigate how the choice of the region of interest (ROI) affects the registration results of surface imaging for daily positioning of breast cancer patients. Methods: The AlignRT system (VisionRT, London) and the XVI Cone beam CT (CBCT; Elekta, Stockholm) installed on two Versa HD linacs (Elekta) were used in this study, which included 28 patients (160 fractions). In the clinical workflow, patients were prepositioned with AlignRT and then shifted in 6 degrees of freedom (DOF) according to the CBCT. A new reference capture was taken immediately afterward. Retrospectively, the surface capture resulting from prepositioning was registered to the latest reference capture. By varying the ROI used for registration, the surface-based results were optimized in terms of minimizing the deviation to the clinically applied CBCT shifts. Two sets of ROIs were used: one obtained by applying a variable margin to the breast surface, another by combining ROIs of anatomical structures, including the sternum and contralateral breast. Results: Registration results showed significant differences from one ROI to another. Generally, the results improved with increasing ROI size, especially for rotational DOFs. ROIs, including the axilla or supraclavicular lymph drainage region, did not yield an improved registration result. On the other hand, an ROI comprising the breast surface, sternum, and a belt caudal to the breasts decreased the average magnitude of the translational and rotational deviations by 6.6% and 30.8% (p < 0.01), respectively, compared to the breast surface only results. Conclusion: The influence of the ROI choice on surface imaging registration results was analyzed and the surface-based shifts were compared to clinically applied CBCT shifts. An optimal ROI for the treatment of breast cancer patients, consisting of the breast surface, sternum, and a belt, was identified.
CRIS-Team Scopus Importer:2021-10-01
Keywords: breast cancer; radiation therapy; surface guided radiation therapy

Reirradiation for recurrent glioblastoma: the significance of the residual tumor volume - Mansoorian, Sina; Schmidt, Manuel; Weissmann, Thomas; Delev, Daniel; Heiland, Dieter Henrik; Coras, Roland; Stritzelberger, Jenny; Saake, Marc; Höfler, Daniel; Schubert, Philipp; Schmitter, Charlotte; Lettmaier, Sebastian; et al. (Journal of Neuro-Oncology, 2025)
Purpose: Recurrent glioblastoma has a poor prognosis, and its optimal management remains unclear. Reirradiation (re-RT) is a promising treatment option, but long-term outcomes and optimal patient selection criteria are not well established. Methods: This study analyzed 71 patients with recurrent CNS WHO grade 4, IDHwt glioblastoma (GBM) who underwent re-RT at the University of Erlangen-Nuremberg between January 2009 and June 2019. Imaging follow-ups were conducted every 3 months. Progression-free survival (PFS) was defined using RANO criteria. Outcomes, feasibility, and toxicity of re-RT were evaluated. Contrast-enhancing tumor volume was measured using a deep learning auto-segmentation pipeline with expert validation and jointly evaluated with clinical and molecular-pathologic factors. Results: Most patients were prescribed conventionally fractionated re-RT (84.5%) with 45 Gy in 1.8 Gy fractions, combined with temozolomide (TMZ, 49.3%) or lomustine (CCNU, 12.7%). Re-RT was completed as planned in 94.4% of patients. After a median follow-up of 73.8 months, 88.7% of patients had died. The median overall survival was 9.6 months, and the median progression-free survival was 5.3 months. Multivariate analysis identified residual contrast-enhancing tumor volume at re-RT (HR 1.040 per cm3, p < 0.001) as the single dominant predictor of overall survival. Conclusion: Conventional fractionated re-RT is a feasible and effective treatment for recurrent high-grade glioma. The significant prognostic impact of residual tumor volume highlights the importance of combining maximum-safe resection with re-RT for improved outcomes.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Chemoradiation; Glioblastoma; Prognostic factors; Radiotherapy; Recurrence; Reirradiation; Tumor volume

Reirradiation of recurent glioblastomas: High prognostic significance of contrast-enhancing tumor volume - Mansoorian, Sina; Coras, Roland; Weissmann, Thomas; Lettmaier, Sebastian; Semrau, Sabine; Frey, Benjamin; Bert, Christoph; Schmidt, M.; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Reporting and Evaluation System for Incidents in the Radiation Therapy to increase Patient Safety, Treatment Quality and the Efficiency of Process Flows - Kornek, Dominik; Lang-Welzenbach, Marga; Beck, A.; Reinhardt, A.; Brandt, Tobias; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Required transition from research to clinical application: Report on the 4D treatment planning workshops 2014 and 2015 - Knopf, Antje-Christin; Stuetzer, Kristin; Richter, Christian; Rucinski, Antoni; Da Silva, Joakim; Phillips, Justin; Engelsman, Martijn; Shimizu, Shinichi; Werner, Rene; Jakobi, Annika; Goksel, Orcun; Zhang, Ye; et al. (Physica Medica, 2016)
Since 2009, a 4D treatment planning workshop has taken place annually, gathering researchers working on the treatment of moving targets, mainly with scanned ion beams. Topics discussed during the workshops range from problems of time resolved imaging, the challenges of motion modelling, the implementation of 4D capabilities for treatment planning, up to different aspects related to 4D dosimetry and treatment verification. This report gives an overview on topics discussed at the 4D workshops in 2014 and 2015. It summarizes recent findings, developments and challenges in the field and discusses the relevant literature of the recent years. The report is structured in three parts pointing out developments in the context of understanding moving geometries, of treating moving targets and of 4D quality assurance (QA) and 4D dosimetry. The community represented at the 4D workshops agrees that research in the context of treating moving targets with scanned ion beams faces a crucial phase of clinical translation. In the coming years it will be important to define standards for motion monitoring, to establish 4D treatment planning guidelines and to develop 4D QA tools. These basic requirements for the clinical application of scanned ion beams to moving targets could e.g. be determined by a dedicated ESTRO task group. Besides reviewing recent research results and pointing out urgent needs when treating moving targets with scanned ion beams, the report also gives an outlook on the upcoming 4D workshop organized at the University Medical Center Groningen (UMCG) in the Netherlands at the end of 2016.
EVALuna2:33049

Residual motion mitigation in scanned carbon ion beam therapy of liver tumors using enlarged pencil beam overlap - Richter, Daniel; Graeff, Christian; Jaekel, Oliver; Combs, Stephanie E.; Durante, Marco; Bert, Christoph (Radiotherapy and Oncology, 2014)
Interplay effects may limit the applicability of scanned ion beam therapy for moving tumors even if the motion amplitude is reduced by techniques such as gating or abdominal compression (AC). We investigate the potential of enhanced pencil beam overlap to mitigate residual motion interplay effects in scanned ion beam therapy.Eight patients with hepato cellular carcinoma were selected who were either treated under AC (5 clinical target volumes (CTVs)) or with gating (6 CTVs). We performed 4D dose calculations for treatment plans with variable beam parameters (lateral raster spacing, beam full-width-at-half-maximum (FWHM), iso-energy slice spacing, gating window (GW)) and assessed under- and overdose (V95 and V107), dose homogeneity (HI=D5-D95), and dose volume histograms. The influence of the beam parameters on HI was studied by multivariate regression models.Motion amplitude and FWHM had the largest impact on dose homogeneity, while decreased iso-energy slice spacing and lateral raster spacing had a much smaller or no significant effect, respectively. The multivariate regression models including FWHM, motion amplitude, and IES-spacing explained 86%, 42%, and 71% of the observed variance for AC, 30% and 50% GW, respectively.Residual motion in scanned carbon ion therapy of liver tumors can lead to considerable dose heterogeneities. Using an increased beam spot size dose degradation can be significantly mitigated. Especially for large tumors, increasing the beam spot size is an efficient motion mitigation option readily available at most scanning facilities.
EVALuna2:18311

Respiratory Deformation Estimation in X-Ray-Guided IMRT Using a Bilinear Model - Geimer, Tobias; Ploner, Stefan; Keall, Paul; Bert, Christoph; Maier, Andreas (Informatik aktuell, 2019)
Driving a respiratory motion model in X-ray guided radiotherapy can be challenging in treatments with continuous rotation such as VMAT, as data-driven respiratory signal extraction suffers from angular effects overlapping with respiratory changes in the projection images. Compared to a linear model trained on static acquisition angles, the bilinear model gains flexibility in terms of handling multiple viewpoints at the cost of accuracy. In this paper, we evaluate both models in the context of serving as the surrogate input to a motion model. Evaluation is performed on the 20 patient 4D CTs in a leave-one-phase-out approach yielding a median accuracy drop of only 0.14mm in the 3D error of estimated vector fields of the bilinear model compared to the linear one.
CRIS-Team Scopus Importer:2019-05-14

Risk analysis for radiotherapy at the Universitätsklinikum Erlangen - Lohmann, Daniel; Lang-Welzenbach, Marga; Feldberger, Lorenz; Sommer, Ellen; Bücken, Stefan; Lotter, Michael; Ott, Oliver; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2022)
Purpose: Risk analysis is required by various laws and regulations in Germany and has an impact on each department of a large clinic. We provide an overview of the relevant laws and regulations in Germany and present the technical and organizational experience of introducing risk analysis in the Department of Radiation Oncology at the Universitätsklinikum Erlangen. Methods: Risk analysis was performed with an in-house developed extension of our intranet platform and ticketing system. Risks were classified according to occurrence and severity, each on a 5-level scale resulting into a risk matrix. An interdisciplinary team of six experienced members formed the core meeting weekly. Results: A total of 38 risks and 50 measures have been identified in 41 1 h-meetings corresponding to approx. 260 working hours. Risk was distributed 8/20/13 to the categories critical (n = 8), monitoring (n = 20), and conditionally acceptable (n = 13). Risk analysis has been evaluated before and after introducing measures. Conclusion: The risk analysis method introduced has been successfully used in routine operations for over a year. Risk analysis takes time and effort. However, because experts from different disciplines meet each other every week, the overall workflow of the radiation oncology department can be improved efficiently and continuously.
CRIS-Team Scopus Importer:2022-04-01
Keywords: GBA; Radiation therapy; Risk analysis; Strahlenschutzverordnung

Risk management in radiation-based therapies - Bert, Christoph (Zeitschrift für Medizinische Physik, 2024)
CRIS-Team Scopus Importer:2024-06-21

ROI optimisation for surface guided radiation therapy - Sauer, Tim-Oliver; Popp, D.; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Scanned ion beam therapy for prostate carcinoma: Comparison of single plan treatment and daily plan-adapted treatment - Hild, Sebastian; Graeff, Christian; Rucinski, Antoni; Zink, Klemens; Habl, Gregor; Durante, Marco; Herfarth, Klaus; Bert, Christoph (Strahlentherapie und Onkologie, 2016)
Intensity-modulated particle therapy (IMPT) for tumors showing interfraction motion is a topic of current research. The purpose of this work is to compare three treatment strategies for IMPT to determine potential advantages and disadvantages of ion prostate cancer therapy.Simulations for three treatment strategies, conventional one-plan radiotherapy (ConvRT), image-guided radiotherapy (IGRT), and online adaptive radiotherapy (ART) were performed employing a dataset of 10 prostate cancer patients with six CT scans taken at one week intervals. The simulation results, using a geometric margin concept (7-2 mm) as well as patient-specific internal target volume definitions for IMPT were analyzed by target coverage and exposure of critical structures on single fraction dose distributions.All strategies led to clinically acceptable target coverage in patients exhibiting small prostate motion (mean displacement <4 mm), but IGRT and especially ART led to significant sparing of the rectum. In 20% of the patients, prostate motion exceeded 4 mm causing insufficient target coverage for ConvRT (V95mean = 0.86, range 0.63-0.99) and IGRT (V95mean = 0.91, range 0.68-1.00), while ART maintained acceptable target coverage.IMPT of prostate cancer demands consideration of rectal sparing and adaptive treatment replanning for patients exhibiting large prostate motion.
EVALuna2:18350

“sCT-Feasibility” - a feasibility study for deep learning-based MRI-only brain radiotherapy - Grigo, Johanna; Szkitsak, Juliane; Höfler, Daniel; Fietkau, Rainer; Putz, Florian; Bert, Christoph (Radiation Oncology, 2024)
Background: Radiotherapy (RT) is an important treatment modality for patients with brain malignancies. Traditionally, computed tomography (CT) images are used for RT treatment planning whereas magnetic resonance imaging (MRI) images are used for tumor delineation. Therefore, MRI and CT need to be registered, which is an error prone process. The purpose of this clinical study is to investigate the clinical feasibility of a deep learning-based MRI-only workflow for brain radiotherapy, that eliminates the registration uncertainty through calculation of a synthetic CT (sCT) from MRI data. Methods: A total of 54 patients with an indication for radiation treatment of the brain and stereotactic mask immobilization will be recruited. All study patients will receive standard therapy and imaging including both CT and MRI. All patients will receive dedicated RT-MRI scans in treatment position. An sCT will be reconstructed from an acquired MRI DIXON-sequence using a commercially available deep learning solution on which subsequent radiotherapy planning will be performed. Through multiple quality assurance (QA) measures and reviews during the course of the study, the feasibility of an MRI-only workflow and comparative parameters between sCT and standard CT workflow will be investigated holistically. These QA measures include feasibility and quality of image guidance (IGRT) at the linear accelerator using sCT derived digitally reconstructed radiographs in addition to potential dosimetric deviations between the CT and sCT plan. The aim of this clinical study is to establish a brain MRI-only workflow as well as to identify risks and QA mechanisms to ensure a safe integration of deep learning-based sCT into radiotherapy planning and delivery. Discussion: Compared to CT, MRI offers a superior soft tissue contrast without additional radiation dose to the patients. However, up to now, even though the dosimetrical equivalence of CT and sCT has been shown in several retrospective studies, MRI-only workflows have still not been widely adopted. The present study aims to determine feasibility and safety of deep learning-based MRI-only radiotherapy in a holistic manner incorporating the whole radiotherapy workflow. Trial registration: NCT06106997.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Artificial intelligence; Deep learning; MRI; MRI-only workflow; MRonly; Radiotherapy; sCT; Stereotactic radiotherapy; Synthetic CT

Seed-displacements in the immediate post-implant phase in permanent prostate brachytherapy - Karius, Andre; Schweizer, Claudia; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Lamrani, Allison; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2023)
Purpose: To investigate differences in seed-displacements between the immediate post-implant phase (day 0–1) and the time to post-plan computed tomography (CT) (day 1–30) in seed prostate brachytherapy. Materials and methods: Seed positions were identified on the intra-operatively created ultrasound-based treatment plan (day 0) and CT scans of day 1 and 30 for 33 patients. The day 1 (30) seed arrangement was registered onto the day 0 (1) arrangement using a seed-only approach. Based on a 1:1 assignment of seeds via the Kuhn-Munkres algorithm, seed-displacements were analyzed. Displacements were evaluated depending on strand-length and anatomical implant location. Resulting dosimetric effects were calculated. Results: Seed-displacements in the immediate post-implant phase (median displacements: 3.8 ± 3.6 mm) were stronger than in the time to post-plan CT (2.1 ± 2.6 mm) and enhanced along the superior-inferior direction. From day 0 to 1, strands containing one (7.3 ± 5.4 mm) or two (8.1 ± 5.8 mm) seeds showed larger displacements than strands of higher lengths (up to 4.2 ± 7.0 mm), whereas no length-dependency was found to day 30. Seeds implanted in base and apex tended to move towards the prostate midzone during both time periods. D90 (dose that 90% of prostate receives) was with variations of 2 ± 15 Gy more stable from day 1 to 30 than in the immediate post-implant phase (−18 ± 11 Gy). Conclusion: Seed-displacements in the immediate post-implant phase was enhanced compared to day 1–30. This may result from uncertainties in the gold-standard ultrasound-based treatment planning and implantation. Adaptive implantation workflows appear useful for ensuring high implant stability from the beginning.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Adaptive implantation; Permanent implant; Prostate brachytherapy; Prostate cancer; Seed brachytherapy; Seed displacements

Synthetic CTs for MRI-only brain RT treatment: integration of immobilization systems - Masitho, Siti; Grigo, Johanna; Brandt, Tobias; Lambrecht, Ulrike; Szkitsak, Juliane; Weiß, Alexander; Fietkau, Rainer; Putz, Florian; Bert, Christoph (Strahlentherapie und Onkologie, 2023)
Purpose: Auxiliary devices such as immobilization systems should be considered in synthetic CT (sCT)-based treatment planning (TP) for MRI-only brain radiotherapy (RT). A method for auxiliary device definition in the sCT is introduced, and its dosimetric impact on the sCT-based TP is addressed. Methods: T1-VIBE DIXON was acquired in an RT setup. Ten datasets were retrospectively used for sCT generation. Silicone markers were used to determine the auxiliary devices’ relative position. An auxiliary structure template (AST) was created in the TP system and placed manually on the MRI. Various RT mask characteristics were simulated in the sCT and investigated by recalculating the CT-based clinical plan on the sCT. The influence of auxiliary devices was investigated by creating static fields aimed at artificial planning target volumes (PTVs) in the CT and recalculated in the sCT. The dose covering 50% of the PTV (D50) deviation percentage between CT-based/recalculated plan (∆D50[%]) was evaluated. Results: Defining an optimal RT mask yielded a ∆D50[%] of 0.2 ± 1.03% for the PTV and between −1.6 ± 3.4% and 1.1 ± 2.0% for OARs. Evaluating each static field, the largest ∆D50[%] was delivered by AST positioning inaccuracy (max: 3.5 ± 2.4%), followed by the RT table (max: 3.6 ± 1.2%) and the RT mask (max: 3.0 ± 0.8% [anterior], 1.6 ± 0.4% [rest]). No correlation between ∆D50[%] and beam depth was found for the sum of opposing beams, except for (45° + 315°). Conclusion: This study evaluated the integration of auxiliary devices and their dosimetric influence on sCT-based TP. The AST can be easily integrated into the sCT-based TP. Further, we found that the dosimetric impact was within an acceptable range for an MRI-only workflow.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Artificial intelligence; Image-guided radiotherapy; Radiotherapy setup; Stereotactic radiosurgery; Treatment planning

T1-SPACE vs. T1-MPRAGE for Target Volume Definition in Brain Metastases - a radiotherapy-oriented Comparison - Mansoorian, S.; Mengling, Veit; Masitho, Siti; Perrin, R.; Siavooshaghighi, H.; Weissmann, T.; Filimonova, Irina; Bert, Christoph; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Task-Specific Data Preparation for Deep Learning to Reconstruct Structures of Interest from Severely Truncated CBCT Data - Huang, Yixing; Fan, Fuxin; Gomaa, Ahmed; Maier, Andreas; Fietkau, Rainer; Bert, Christoph; Putz, Florian (The 8th International Conference on Image Formation in X-Ray Computed Tomography, 2024)
Cone-beam computed tomography (CBCT) is widely used in interventional surgeries and radiation oncology. Due to the limited size of flat-panel detectors, anatomical structures might be missing outside the limited field-of-view (FOV), which restricts the clinical applications of CBCT systems. Recently, deep learning methods have been proposed to extend the FOV for multi-slice CT systems. However, in mobile CBCT system with a smaller FOV size, projection data is severely truncated and it is challenging for a network to restore all missing structures outside the FOV. In some applications, only certain structures outside the FOV are of interest, e.g., ribs in needle path planning for liver/lung cancer diagnosis. Therefore, a task-specific data preparation method is proposed in this work, which automatically let the network focus on structures of interest instead of all the structures. Our preliminary experiment shows that Pix2pixGAN with a conventional training has the risk to reconstruct false positive and false negative rib structures from severely truncated CBCT data, whereas Pix2pixGAN with the proposed task-specific training can reconstruct all the ribs reliably. The proposed method is promising to empower CBCT with more clinical applications.<br
Keywords: Field-of-view extension; computed tomography; deep learning; data truncation; task-specific learning.

Technical evaluation of the cone-beam computed tomography imaging performance of a novel, mobile, gantry-based X-ray system for brachytherapy - Karius, Andre; Karolczak, Marek; Strnad, Vratislav; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2021)
Purpose A novel, mobile cone-beam computed tomography (CBCT) system for image-guided adaptive brachytherapy was recently deployed at our hospital as worldwide first site. Prior to the device's clinical operation, a profound characterization of its imaging performance was conducted. This was essential to optimize both the imaging workflow and image quality for achieving the best possible clinical outcomes. We present the results of our investigations. Methods The novel CBCT-system features a ring gantry with 121 cm clearance as well as a 43.2 x 43.2 cm(2) flat-panel detector, and is controlled via a tablet-personal computer (PC). For evaluating its imaging performance, the geometric reproducibility as well as imaging fidelity, computed tomography (CT)-number accuracy, uniformity, contrast-noise-ratio (CNR), noise characteristics, and spatial resolution as fundamental image quality parameters were assessed. As dose metric the weighted cone-beam dose index (CBDIw) was measured. Image quality was evaluated using standard quality assurance (QA) as well as anthropomorphic upper torso and breast phantoms. Both in-house and manufacturer protocols for abdomen, pelvis, and breast imaging were examined. Results Using the in-house protocols, the QA phantom scans showed altogether a high image quality, with high CT-number accuracy (R-2 > 0.97) and uniformity (<12 Hounsfield Unit (HU) cupping), reasonable noise and imaging fidelity, and good CNR at bone-tissue transitions of up to 28:1. Spatial resolution was strongly limited by geometric instabilities of the device. The breast phantom scans fulfilled clinical requirements, whereas the abdomen and pelvis scans showed severe artifacts, particularly at air/bone-tissue transitions. Conclusion With the novel CBCT-system, achieving a high image quality appears possible in principle. However, adaptations of the standard protocols, performance enhancements in image reconstruction referring to artifact reductions, as well as the extinction of geometric instabilities are imperative.
CRIS-Team WoS Importer:2021-12-24

Technical Note: A comparison of point set registration methods for electromagnetic tracking - Götz, T. I.; Wankerl, H.; Tomé, A. M.; Meyer-Baese, A.; Bert, Christoph; Hensel, Bernhard; Lang, E. W. (Medical Physics, 2019)
Purpose: High dose rate brachytherapy applies intense and destructive radiation. A treatment plan defines radiation source dwell positions to avoid irradiating healthy tissue. The study discusses methods to quantify any positional changes of source locations along the various treatment sessions. Methods: Electromagnetic tracking (EMT) localizes the radiation source during the treatment sessions. But in each session the relative position of the patient relative to the filed generator is changed. Hence, the measured dwell point sets need to be registered onto each other to render them comparable. Two point set registration techniques are compared: a probabilistic method called coherent point drift (CPD) and a multidimensional scaling (MDS) technique. Results: Both enable using EMT without external registration and achieve very similar results with respect to dwell position determination of the radiation source. Still MDS achieves smaller grand average deviations (CPD-rPSR: MD = 2.55 mm, MDS-PSR: MD = 2.15 mm) between subsequent dwell position determinations, which also show less variance (CPD-rPSR: IQR = 4 mm, MDS-PSR: IQR = 3 mm). Furthermore, MDS is not based on approximations and does not need an iterative procedure to track sensor positions inside the implanted catheters. Conclusion: Although both methods achieve similar results, MDS is to be preferred over rigid CPD while nonrigid CPD is unsuitable as it does not preserve topology.
CRIS-Team Scopus Importer:2019-05-17
Keywords: brachytherapy; electromagnetic tracking; multi-dimensional scaling; point set registration

Technical Note: Radiation properties of tissue- and water-equivalent materials formulated using the stoichiometric analysis method in charged particle therapy - Yohannes, Indra; Hild, Sebastian; Vasiliniuc, Stefan; Langner, Oliver; Graeff, Christian; Bert, Christoph (Medical Physics, 2016)
Five tissue- and water-equivalent materials (TEMs) mimicking ICRU real tissues have been formulated using a previously established stoichiometric analysis method (SAM) to be applied in charged particle therapy. The purpose of this study was an experimental verification of the TEMs-SAM against charged particle beam measurements and for different computed tomography (CT) scanners. The potential of the TEMs-SAM to be employed in the dosimetry was also investigated.Experimental verification with three CT scanners was carried out to validate the calculated Hounsfield units (HUs) of the TEMs. Water-equivalent path lengths (WEPLs) of the TEMs for proton (106.8 MeV/u), helium (107.93 MeV/u), and carbon (200.3 MeV/u) ions were measured to be compared with the computed relative stopping powers. HU calibration curves were also generated.Differences between the measured HUs of the TEMs and the calculated HUs of the ICRU real tissues for all CT scanners were smaller than 4 HU except for the skeletal tissues which deviated up to 21 HU. The measured WEPLs verified the calculated WEPLs of the TEMs (maximum deviation was 0.17 mm) and were in good agreement with the calculated WEPLs of the ICRU real tissues (maximum deviation was 0.23 mm). Moreover, the relative stopping powers converted from the measured WEPLs differed less than 0.8% and 1.3% from the calculated values of the SAM and the ICRU, respectively. Regarding the relative nonelastic cross section per unit of volume for 200 MeV protons, the ICRU real tissues were generally well represented by the TEMs except for adipose which differed 3.8%. Further, the HU calibration curves yielded the mean and the standard deviation of the errors not larger than 0.5% and 1.9%, respectively.The results of this investigation implied the potential of the TEMs formulated using the SAM to be employed for both, beam dosimetry and HU calibration in charged particle therapy.
EVALuna2:18348

The 3rd ESTRO-EFOMP core curriculum for medical physics experts in radiotherapy - Garibaldi, Cristina; Essers, Marion; Heijmen, Ben; Bertholet, Jenny; Koutsouveli, Efi; Schwarz, Marco; Bert, Christoph; Bodale, Marin; Casares-Magaz, Oscar; Gerskevitch, Eduard; Koniarova, Irena; Korreman, Stine; et al. (Radiotherapy and Oncology, 2022)
Purpose: To update the 2011 ESTRO-EFOMP core curriculum (CC) for education and training of medical physics experts (MPE)s working in radiotherapy (RT), in line with recent EU guidelines, and to provide a framework for European countries to develop their own curriculum. Material and methods: Since September 2019, 27 European MPEs representing ESTRO, EFOMP and National Societies, with expertise covering all subfields of RT physics, have revised the CC for recent advances in RT. The ESTRO and EFOMP Education Councils, all European National Societies and international stakeholders have been involved in the revision process. Results: A 4-year training period has been proposed, with a total of 240 ECTS (European Credit Transfer and Accumulation System). Training entrance levels have been defined ensuring the necessary physics and mathematics background. The concept of competency-based education has been reinforced by introducing the CanMEDS role framework. The updated CC includes (ablative) stereotactic-, MR-guided- and adaptive RT, particle therapy, advanced automation, complex quantitative data analysis (big data/artificial intelligence), use of biological images, and personalized treatments. Due to the continuously increasing RT complexity, more emphasis has been given to quality management. Clear requirements for a research project ensure a proper preparation of MPE residents for their central role in science and innovation in RT. Conclusion: This updated, 3rd edition of the CC provides an MPE training framework for safe and effective practice of modern RT, while acknowledging the significant efforts needed in some countries to reach this level. The CC can contribute to further harmonization of MPE training in Europe.
CRIS-Team Scopus Importer:2022-05-13
Keywords: Core curriculum (CC); Education and training; ESTRO-EFOMP; Medical Physics Expert (MPE); Radiotherapy physics

The Distribution of Pelvic Nodal Metastases in Prostate Cancer Reveals Potential to Advance and Personalize Pelvic Radiotherapy - Filimonova, Irina; Schmidt, Daniela; Mansoorian, Sina; Weissmann, Thomas; Siavooshhaghighi, Hadi; Kuwert, Torsten; Bert, Christoph; Frey, Benjamin; Distel, Luitpold; Lettmaier, Sebastian; Fietkau, Rainer; Putz, Florian; et al. (Frontiers in Oncology, 2021)
Background: Traditional clinical target volume (CTV) definition for pelvic radiotherapy in prostate cancer consists of large volumes being treated with homogeneous doses without fully utilizing information on the probability of microscopic involvement to guide target volume design and prescription dose distribution. Methods: We analyzed patterns of nodal involvement in 75 patients that received RT for pelvic and paraaortic lymph node metastases (LNs) from prostate cancer in regard to the new NRG-CTV recommendation. Non-rigid registration-based LN mapping and weighted three-dimensional kernel density estimation were used to visualize the average probability distribution for nodal metastases. As independent approach, the mean relative proportion of LNs observed for each level was determined manually and NRG and non-NRG levels were evaluated for frequency of involvement. Computer-automated distance measurements were used to compare LN distances in individual patients to the spatial proximity of nodal metastases at a cohort level. Results: 34.7% of patients had pelvic LNs outside NRG-consensus, of which perirectal was most common (25.3% of all patients) followed by left common iliac nodes near the left psoas major (6.7%). A substantial portion of patients (13.3%) had nodes at the posterior edge of the NRG obturator level. Observer-independent mapping consistently visualized high-probability hotspots outside NRG-consensus in the perirectal and left common iliac regions. Affected nodes in individual patients occurred in highly significantly closer proximity than at cohort-level (mean distance, 6.6 cm vs. 8.7 cm, p < 0.001). Conclusions: Based on this analysis, the common iliac level should extend to the left psoas major and obturator levels should extend posteriorly 5 mm beyond the obturator internus. Incomplete coverage by the NRG-consensus was mostly because of perirectal involvement. We introduce three-dimensional kernel density estimation after non-rigid registration-based mapping for the analysis of recurrence data in radiotherapy. This technique provides an estimate of the underlying probability distribution of nodal involvement and may help in addressing institution- or subgroup-specific differences. Nodal metastases in individual patients occurred in highly significantly closer proximity than at a cohort-level, which supports that personalized target volumes could be reduced in size compared to a “one-size-fits-all” approach and is an important basis for further investigation into individualized field designs.
CRIS-Team Scopus Importer:2021-02-05
Keywords: lymph node metastases; mapping; patterns of recurrence; pelvic radiotherapy; prostate cancer

The OAR Turing-Test Study: A blinded Comparison of expert-Based Organ at Risk Creation and three commercial Auto-Segmentation Solutions - Putz, Florian; Lamrani, Allison; Weissmann, Thomas; Mansoorian, Sina; Frey, Benjamin; Bert, Christoph; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

The Segment Anything foundation model achieves favorable brain tumor auto-segmentation accuracy in MRI to support radiotherapy treatment planning - Putz, Florian; Beirami, Sogand; Schmidt, Manuel; May, Matthias; Grigo, Johanna; Weissmann, Thomas; Schubert, Philipp; Höfler, Daniel; Gomaa, Ahmed; Hassen, Ben Tkhayat; Lettmaier, Sebastian; Frey, Benjamin; et al. (Strahlentherapie und Onkologie, 2024)
Background: Promptable foundation auto-segmentation models like Segment Anything (SA, Meta AI, New York, USA) represent a novel class of universal deep learning auto-segmentation models that could be employed for interactive tumor auto-contouring in RT treatment planning. Methods: Segment Anything was evaluated in an interactive point-to-mask auto-segmentation task for glioma brain tumor auto-contouring in 16,744 transverse slices from 369 MRI datasets (BraTS 2020 dataset). Up to nine interactive point prompts were automatically placed per slice. Tumor boundaries were auto-segmented on contrast-enhanced T1w sequences. Out of the three auto-contours predicted by SA, accuracy was evaluated for the contour with the highest calculated IoU (Intersection over Union, “oracle mask,” simulating interactive model use with selection of the best tumor contour) and for the tumor contour with the highest model confidence (“suggested mask”). Results: Mean best IoU (mbIoU) using the best predicted tumor contour (oracle mask) in full MRI slices was 0.762 (IQR 0.713–0.917). The best 2D mask was achieved after a mean of 6.6 interactive point prompts (IQR 5–9). Segmentation accuracy was significantly better for high- compared to low-grade glioma cases (mbIoU 0.789 vs. 0.668). Accuracy was worse using the suggested mask (0.572). Stacking best tumor segmentations from transverse MRI slices, mean 3D Dice score for tumor auto-contouring was 0.872, which was improved to 0.919 by combining axial, sagittal, and coronal contours. Conclusion: The Segment Anything foundation segmentation model can achieve high accuracy for glioma brain tumor segmentation in MRI datasets. The results suggest that foundation segmentation models could facilitate RT treatment planning when properly integrated in a clinical application.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Artificial intelligence; Deep learning; Glioma; Interactive segmentation; Tumor auto-contouring

Toward a deep learning-based magnetic resonance imaging only workflow for postimplant dosimetry in I-125 seed brachytherapy for prostate cancer - Grigo, Johanna; Karius, Andre; Hanspach, Jannis; Mücke, Lion; Laun, Frederik B.; Huang, Yixing; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph; Putz, Florian (Brachytherapy, 2024)
Background and purpose: The current standard imaging-technique for creating postplans in seed prostate brachytherapy is computed tomography (CT), that is associated with additional radiation exposure and poor soft tissue contrast. To establish a magnetic resonance imaging (MRI) only workflow combining improved tissue contrast and high seed detectability, a deep learning-approach for automatic seed segmentation on MRI-scans was developed. Material and methods: Patients treated with I-125 seed brachytherapy received a postplan-CT and a 1.5 T MRI-scan on nominal day 30 after implantation. For MRI-based seed visualization, DIXON-sequences were acquired and deep learning-based quantitative susceptibility maps (QSM) were generated from 3D-gradient-echo-sequences from 20 patients. Seed segmentations created on CT served as ground truth. For automatic seed segmentation on MRI, a 3D nnU-net model was trained using QSM and DIXON, both solely and combined. Results: Of the implanted seeds 94.8 ± 2.4% were detected with deep learning automatic segmentation entrained on both QSM and DIXON data. Models trained on the individual sequence data-sets performed worse with detection rates of 87.5 ± 2.6% or 88.6 ± 7.5% for QSM and DIXON respectively. The seed centers identified on CT versus QSM and DIXON were on average 1.8 ± 1.3 mm apart. Postimplant dosimetry for evaluation of positioning inaccuracies revealed only small variations of up to 0.4 ± 4.26 Gy in D90 (dose 90% of the prostate receives) between the standard CT-approach and our MRI-only workflow. Conclusion: The proposed deep learning-based MRI-only workflow provided a promisingly accurate and robust seed localization and thus has the potential to compete with current state-of-the-art CT-based postimplant dosimetry in the future.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Magnetic resonance imaging; Magnetic resonance only workflow; Permanent brachytherapy; Postimplant dosimetry; Radiotherapy; Seed brachytherapy

Transient Enlargement in Meningiomas Treated with Stereotactic Radiotherapy - Maksoud, Ziad; Schmidt, Manuel; Huang, Yixing; Rutzner, Sandra; Mansoorian, Sina; Weissmann, Thomas; Bert, Christoph; Distel, Luitpold; Semrau, Sabine; Lettmaier, Sebastian; Eyüpoglu, Ilker Yasin; Fietkau, Rainer; et al. (Cancers, 2022)
To investigate the occurrence of pseudoprogression/transient enlargement in meningiomas after stereotactic radiotherapy (RT) and to evaluate recently proposed volumetric RANO meningioma criteria for response assessment in the context of RT. Sixty-nine meningiomas (benign: 90%, atypical: 10%) received stereotactic RT from January 2005–May 2018. A total of 468 MRI studies were segmented longitudinally during a median follow-up of 42.3 months. Best response and local control were evaluated according to recently proposed volumetric RANO criteria. Transient enlargement was defined as volumetric increase ≥20% followed by a subsequent regression ≥20%. The mean best volumetric response was −23% change from baseline (range, −86% to +19%). According to RANO, the best volumetric response was SD in 81% (56/69), MR in 13% (9/69) and PR in 6% (4/69). Transient enlargement occurred in only 6% (4/69) post RT but would have represented 60% (3/5) of cases with progressive disease if not accounted for. Transient enlargement was characterized by a mean maximum volumetric increase of +181% (range, +24% to +389 %) with all cases occurring in the first year post-RT (range, 4.1–10.3 months). Transient enlargement was significantly more frequent with SRS or hypofractionation than with conventional fractionation (25% vs. 2%, p = 0.015). Five-year volumetric control was 97.8% if transient enlargement was recognized but 92.9% if not accounted for. Transient enlargement/pseudoprogression in the first year following SRS and hypofractionated RT represents an important differential diagnosis, especially because of the high volumetric control achieved with stereotactic RT. Meningioma enlargement during subsequent post-RT follow-up and after conventional fractionation should raise suspicion for tumor progression. <
Keywords: meningioma; volumetric analysis; segmentation; transient enlargement; pseudoprogression; stereotactic radiotherapy; radiosurgery; response assessment

Treatment of arrhythmias by external charged particle beams: a Langendorff feasibility study - Prall, Matthias; Lehmann, H. Immo; Prokesch, Hannah; Richter, Daniel; Graeff, Christian; Kaderka, Robert; Sonnenberg, Karin; Hauswald, Henrik; Weymann, Alexander; Bauer, Julia; Constantinescu, Anna; Haberer, Thomas; et al. (Biomedizinische Technik, 2015)
Hadron therapy has already proven to be successful in cancer therapy, and might be a noninvasive alternative for the ablation of cardiac arrhythmias in humans. We present a pilot experiment investigating acute effects of a 12C irradiation on the AV nodes of porcine hearts in a Langendorff setup. This setup was adapted to the requirements of charged particle therapy. Treatment plans were computed on calibrated CTs of the hearts. Irradiation was applied in units of 5 and 10 Gy over a period of about 3 h until a total dose of up to 160 Gy was reached. Repeated application of the same irradiation field helped to mitigate motion artifacts in the resulting dose distribution. After irradiation, PET scans were performed to verify accurate dose application. Acute AV blocks were identified. No other acute effects were observed. Hearts were kept in sinus rhythm for up to 6 h in the Langendorff setup. We demonstrated that 12C ions can be used to select a small target in the heart and, thereby, influence the electrical conduction system. Second, our pilot study seems to suggest that no adverse effects have to be expected immediately during heavy ion irradiation in performing subsequent experiments with doses of 30-60 Gy and intact pigs.
EVALuna2:18316

Treatment Parameters Optimization to Compensate for Interfractional Anatomy Variability and Intrafractional Tumor Motion - Brevet, Romain; Richter, Daniel; Graeff, Christian; Durante, Marco; Bert, Christoph (Frontiers in Oncology, 2015)
Scanned ion beam therapy of lung tumors is severely limited in its clinical applicability by intrafractional organ motion, interference effects between beam and tumor motion (interplay), as well as interfractional anatomic changes. To compensate for dose deterioration caused by intrafractional motion, motion mitigation techniques, such as gating, have been developed. However, optimization of the treatment parameters is needed to further improve target dose coverage and normal tissue sparing. The aim of this study was to determine treatment-planning parameters that permit to recover good target coverage for each fraction of lung tumor treatments. For 9 lung tumor patients from MD Anderson Cancer Center (Houston, Texas), a total of 70 weekly time-resolved computed tomography (4DCT) datasets, which depict the evolution of the patient anatomy over the several fractions of the treatment, were available. Using the GSI in-house treatment planning system TRiP4D, 4D simulations were performed on each weekly 4DCT for each patient using gating and optimization of a single treatment plan based on a planning CT acquired prior to treatment. The impact on target dose coverage (V 95%,CTV) of variations in focus size and length of the gating window, as well as different additional margins and the number of fields was analyzed. It appeared that interfractional variability could potentially have a larger impact on V 95%,CTV than intrafractional motion. However, among the investigated parameters, the use of a large beam spot size, a short gating window, additional margins, and multiple fields permitted to obtain an average V 95%,CTV of 96.5%. In the presented study, it was shown that optimized treatment parameters have an important impact on target dose coverage in the treatment of moving tumors. Indeed, intrafractional motion occurring during the treatment of lung tumors and interfractional variability were best mitigated using a large focus, a short gating window, additional margins, and three fields.
EVALuna2:18368

Treatment Planning Studies in Patient Data With Scanned Carbon Ion Beams for Catheter-Free Ablation of Atrial Fibrillation - Constantinescu, Anna; Lehmann, H. Immo; Packer, Douglas L.; Bert, Christoph; Durante, Marco; Graeff, Christian (Journal of Cardiovascular Electrophysiology, 2016)
Catheter ablation with isolation of the pulmonary veins is a common treatment option for atrial fibrillation but still has insufficient success rates and carries several interventional risks. These treatment planning studies assessed if high-dose single fraction treatment with scanned carbon ions (12C) can be reliably delivered for AF ablation, while sparing risk structures and considering respiratory and contractile target motion.Time resolved CT scans of complete respiratory and cardiac cycles of 9 and 5 patients, respectively, were obtained. Ablation lesions and organs at risk for beam delivery were contoured. Single fraction intensity-modulated particle therapy with target doses of 25 and 40 Gy were studied and motion influences on these deliveries mitigated. Respiration had a large influence on lesion displacement (<= 2 cm). End expiration could be exploited as a stable gating window. Smaller, but less predictable, heartbeat displacements (< 6 mm) remained to be mitigated because cardiac contraction resulted in insufficient dose coverage (V95 < 90%) if uncompensated. Repeated irradiation (12C beam rescanning) during breath hold was used to accommodate contractile motion, resulting in good dose coverage. Dose depositions to all organs at risk were carefully examined and did not exceed values for X-ray cancer treatment.Treatment planning of 12C with delivery of physical ionizing radiation doses that have been described to induce complete block is feasible for AF ablation, considering human anatomy, dose constraints, and encasing underlying motion patterns from respiration and cardiac contraction at the LA-PV junction into treatment planning.
EVALuna2:18342

Two-ways validation of the feasibility of AI-based synthetic CT for MR-only brain radiotherapy - Masitho, Siti; Szkitsak, Juliane; Grigo, Johanna; Putz, Florian; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-07-22

Unified risk analysis in radiation therapy - Lohmann, Daniel; Shariff, Maya; Schubert, Philipp; Sauer, Tim-Oliver; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2022)
Purpose: The increasing complexity of new treatment methods as well as the Information Technology (IT) infrastructure within radiotherapy require new methods for risk analysis. This work presents a methodology on how to model the treatment process of radiotherapy in different levels. This subdivision makes it possible to perform workflow-specific risk analysis and to assess the impact of IT risks on the overall treatment workflow. Methods: A Unified Modeling Language (UML) activity diagram is used to model the workflows. The subdivision of the workflows into different levels is done with the help of swim lanes. The model created in this way is exported in an xml-compatible format and stored in a database with the help of a Python program. Results: Based on an existing risk analysis, the workflows CT Appointment, Glioblastoma Multiforme, and Deep Inspiration Breath Hold (DIBH) were modeled in detail. Part of the analysis are automatically generated workflow-specific risk matrices including risks of medical devices incorporated into a specific workflow. In addition, SQL queries allow to quickly retrieve e.g., the details of the medical device network installed in a department. Conclusion: Activity diagrams of UML can be used to model workflows in radiotherapy. Through this, a connection between the different levels of the entire workflow can be established and workflow-specific risk analysis is possible.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Activity diagram; IEC 80001-1; Risk analysis; UML

Union of light ion therapy centers in Europe (ULICE EC FP7) - Objectives and achievements of joint research activities - Poetter, Richard; Balosso, Jaques; Baumann, Michael; Bert, Christoph; Davies, Jim; Enghardt, Wolfgang; Fossati, Piero; Harris, Steve; Jones, Bleddyn; Kraemer, Michael; Mayer, Ramona; Mock, Ulrike; et al. (Radiotherapy and Oncology, 2018)
Under the umbrella of the European Network for Light Ion Therapy (ENLIGHT), the project on Union of Light Ion Centers in Europe (ULICE), which was funded by the European Commission (EC/FP7), was carried out from 2009 to 2014. Besides the two pillars on Transnational Access (TNA) and Networking Activities (NA), six work packages formed the pillar on Joint Research Activities (JRA). The current manuscript focuses on the objectives and results achieved within these research work packages: "Clinical Research Infrastructure", "Biologically Based Expert System for Individualized Patient Allocation", "Ion Therapy for Intra-Fractional Moving Targets", "Adaptive Treatment Planning for Ion Radiotherapy", "Carbon Ion Gantry", "Common Database and Grid Infrastructures for Improving Access to Research Infrastructures". The objectives and main achievements are summarized. References to either publications or open access deliverables from the five year project work are given. Overall, carbon ion radiotherapy is still not as mature as photon or proton radiotherapy. Achieved results and open questions are reflected and discussed in the context of the current status of carbon ion therapy and particle and photon beam therapy. Most research topics covered in the ULICE JRA pillar are topical. Future research activities can build upon these ULICE results. Together with the continuous increase in the number of particle therapy centers in the last years ULICE results and proposals may contribute to the further growth of the overall particle therapy field as foreseen with ENLIGHT and new joint initiatives such as the European Particle Therapy Network (EPTN) within the overall radiotherapy community.
EVALuna2:36474

Update of the ESTRO-EFOMP core curriculum for medical physics experts in radiotherapy - Garibaldi, C.; Essers, M.; Heijmen, B.; Bertholet, J.; Koutsouveli, E.; Schwarz, M.; Bert, Christoph; Jornet, N.; Clark, C. H. (RADIOTHERAPY AND ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-11-26

Usability of magnetic resonance images acquired at a novel low-field 0.55 T scanner for brain radiotherapy treatment planning - Grigo, Johanna; Masitho, Siti; Fautz, Hans Peter; Voigt, Raphaela; Schonath, Miriam; Oleszczuk, Annika; Uder, Michael; Heiß, Rafael; Fietkau, Rainer; Putz, Florian; Bert, Christoph (Physics and Imaging in Radiation Oncology, 2023)
Background and Purpose: Low-field magnetic resonance imaging (MRI) may offer specific advantages over high-field MRI, e.g. lower susceptibility-dependent distortions and simpler installation. The study aim was to evaluate if a novel 0.55 T MRI scanner provides sufficient image accuracy and quality for radiotherapy (RT) treatment planning. Material and methods: The geometric accuracy of images acquired at a low-field MRI scanner was evaluated in phantom measurements regarding gradient non-linearity-related distortions. Patient-induced B0-susceptibility changes were investigated via B0-field-mapping in ten volunteers. Patients were positioned in RT-setup using a 3D-printed insert for the head/neck-coil that was tested for sufficient signal-to-noise-ratio (SNR). The suitability of the MRI-system for detection of metastases was evaluated in eleven patients. In comparison to diagnostic images, acquired at ≥1.5 T, three physicians evaluated the detectability of metastases by counting them in low- and high-field-images, respectively. Results: The phantom measurements showed a high imaging fidelity after 3D-distortion-correction with (1.2 ± 0.9) mm geometric distortion in 10 cm radius from isocentre. At the edges remaining distortions were greater than at 1.5 T. The mean susceptibility-induced distortions in the head were (0.05 ± 0.05) mm and maximum 0.69 mm. SNR analysis showed that optimised positioning of RT-patients without signal loss in the head/neck-coil was possible with the RT-insert. No significant differences (p = 0.48) in detectability of metastases were found. Conclusion: The 0.55 T MRI system provided sufficiently geometrically accurate and high-resolution images that can be used for RT-planning for brain metastases. Hence, modern low-field MRI may contribute to simply access MRI for RT-planning after further investigations.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Low-Field-MRI; MRI; Radiotherapy

Variability in catheter reconstruction for multi-catheter interstitial brachytherapy - Kallis, Karoline; Kaltsas, Theodoros; Kreppner, Stephan; Lotter, M.; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Verbesserung der Deep Learning basierten Autodetektion von Hirnmetastasen durch Integration von MRT-Voraufnahmen - Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Dörfler, Arnd; Maier, Andreas; Fietkau, Rainer; et al. (Strahlentherapie und Onkologie, 2022)
Keywords: Deep learning; brain metastasis

Volumetric Regression in Brain Metastases After Stereotactic Radiotherapy: Time Course, Predictors, and Significance - Oft, Dominik; Schmidt, Manuel; Weissmann, Thomas; Roesch, Johannes; Mengling, Veit; Masitho, Siti; Bert, Christoph; Lettmaier, Sebastian; Frey, Benjamin; Distel, Luitpold; Fietkau, Rainer; Putz, Florian (Frontiers in Oncology, 2021)
Background: There is insufficient understanding of the natural course of volumetric regression in brain metastases after stereotactic radiotherapy (SRT) and optimal volumetric criteria for the assessment of response and progression in radiotherapy clinical trials for brain metastases are currently unknown. Methods: Volumetric analysis via whole-tumor segmentation in contrast-enhanced 1 mm³-isotropic T1-Mprage sequences before SRT and during follow-up. A total of 3,145 MRI studies of 419 brain metastases from 189 patients were segmented. Progression was defined using a volumetric extension of the RANO-BM criteria. A subset of 205 metastases without progression/radionecrosis during their entire follow-up of at least 3 months was used to study the natural course of volumetric regression after SRT. Predictors for volumetric regression were investigated. A second subset of 179 metastases was used to investigate the prognostic significance of volumetric response at 3 months (defined as ≥20% and ≥65% volume reduction, respectively) for subsequent local control. Results: Median relative metastasis volume post-SRT was 66.9% at 6 weeks, 38.6% at 3 months, 17.7% at 6 months, 2.7% at 12 months and 0.0% at 24 months. Radioresistant histology and FSRT vs. SRS were associated with reduced tumor regression for all time points. In multivariate linear regression, radiosensitive histology (p=0.006) was the only significant predictor for metastasis regression at 3 months. Volumetric regression ≥20% at 3 months post-SRT was the only significant prognostic factor for subsequent control in multivariate analysis (HR 0.63, p=0.023), whereas regression ≥65% was no significant predictor. Conclusions: Volumetric regression post-SRT does not occur at a constant rate but is most pronounced in the first 6 weeks to 3 months. Despite decreasing over time, volumetric regression continues beyond 6 months post-radiotherapy and may lead to complete resolution of controlled lesions by 24 months. Radioresistant histology is associated with slower regression. We found that a cutoff of ≥20% regression for the volumetric definition of response at 3 months post-SRT was predictive for subsequent control whereas the currently proposed definition of ≥65% was not. These results have implications for standardized volumetric criteria in future radiotherapy trials for brain metastases.
CRIS-Team Scopus Importer:2021-02-05
Keywords: brain metastases; longitudinal analysis; MRI; stereotactic radiosurgery; stereotactic radiotherapy; volumetric analysis; volumetric regression

Volumetric regression in brain metastases after stereotactic RT: Time course and significance - Putz, Florian; Oft, Dominik; Perrin, R.; Mengling, Veit; Weissmann, Thomas; Roesch, Johannes; Mansoorian, Sina; Distel, Luitpold; Bert, Christoph; Fietkau, Rainer (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18